Biocontrol of Listeria monocytogenes and Salmonella Typhimurium in hydroponics: Evaluating the efficacy of plant growth promoting bioinoculants - Grace Akumu; Leslie D. Thompson; Mindy M. Brashears; Catherine R. Simpson; Christopher J. Currey; Angela M. Walla (Food Control, 2026)

Quantifying methane and ammonia emissions from beef cattle finishing systems under sorghum and corn diets - Eduardo A. Santos; Nathan M. Sweet; Harleigh Johnson; Chinthaka Weerasekara; Nathan Malarich; Josefina Lacasa; Cosmin Blaga; Brett D. DePaola; Logan Thompson; Jaymelynn Farney; James Drouillard; Kevin C. Cossel; et al. (Agricultural and Forest Meteorology, 2026)

Novel transfersome-based vaccine delivery for red tilapia: Enhancing immunization against Francisella orientalis using bacteriocin from cell-free supernatants - Patcharapong Thangsunan; Chatchai Rodwihok; Benchawan Kumwan; Pakapon Meachasompop; Prapansak Srisapoome; Pattanapong Thangsunan; Jitraporn Phaksopa; Wararut Buncharoen; Thanisorn Mahatnirunkul; Channarong Rodkhum; Nuttee Suree; Thao Thu Mai; et al. (Fish & Shellfish Immunology, 2026)

Overcoming barriers to achieving a Net Zero agri-food sector: Challenges and solutions - Ryan G. McGuire; Lynda S. Perkins; Katie Lawther; Josh P. Thompson; Ilias Kyriazakis; Jørgen Eivind Olesen; Sharon Huws; Paul N. Williams; Taro Takahashi; Rachel Cassidy; Elizabeth Magowan; John Gilliland; et al. (Environmental Science & Policy, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Time in the city: long-term urban exposure predicts greater exploration and problem solving in wild red foxes - F. Blake Morton; Dylan Thompson-Jones; Kristy A. Adaway; Koko M. Sutter; Catia Matos; Georgia B. Freer; Georgia A.A. Fletcher; Carl D. Soulsbury (Animal Behaviour, 2026)

Erratum to “Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease” [Neurotoxicology 115 (2026) 103495] - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Source-dependent effects of dietary astaxanthins on health and mucosal immunity in Atlantic salmon (Salmo salar) - S.M.Majharul Islam; Mette Sørensen; Gabriel Ossenkamp; Muhammad A.B. Siddik; Monica F. Brinchmann; Jørgen Lerfall; Viviane Verlhac-Trichet; Florence Perera Willora; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2026)

Assessing Cancer Patients’ Exposure to Treatment Misinformation - Naomi D. Parker; Skyler B. Johnson; Andy J. King; Tithi B. Amin; Briony Swire-Thompson; Zhongyue Zhang; Carma L. Bylund (Journal of Cancer Education, 2026)

Heart rate and sub-blubber temperature in harbour seals (Phoca vitulina) measured during the moult and post-moult using implantable loggers - W. D. Paterson; L. L. Chaise; S. E. Moss; R. Milne; C. Gilbert; J. I. Currie; D. Thompson; D. J. McCafferty (Journal of Comparative Physiology B, 2026)
The moult represents an important seasonal change in the physiology of phocid seals. However, physiological measurements are challenging due to the impracticalities of instrumenting moulting animals. The aim of this study was (i) to assess the feasibility of a long-term deployment of fully implantable loggers to measure heart rate (HR) and sub-blubber temperature (T b ) in harbour seals ( Phoca vitulina ) and (ii) to compare HR and T b during moult and post-moult periods. Loggers were surgically implanted on an adult and sub-adult harbour seal in captivity. Animals healed quickly from surgery and loggers provided 65 days of continuous data before removal of the device. Results showed that in the adult when hauled out and in the water HR was lower during the moult compared with the post-moult. For the sub-adult, HR while in the water was also higher during the post-moult, however, when hauled out there was no difference in HR between the moult and post-moult periods. When hauled out, T b was greater for both animals during the moult compared with the post-moult. During haulout events, T b increased over time in both periods and T b in both animals was lower during post moult compared to the moult period. In the sub-adult, T b decreased with time in the water during the moult but showed little change during the post-moult period, whereas no temporal change was evident in the adult during either period. This study demonstrated that fully implantable loggers are a useful research tool allowing measurement of physiological parameters that are otherwise difficult to measure in pinnipeds. Physiological measurements suggested that the requirement to maintain higher skin temperature for hair growth during the moult was offset by lower metabolism to save energy in water, and on land in the case of adults. However, a decrease in body temperature with time in water in the sub-adult indicated that a smaller body size and less well-developed blubber layer is not as effective in reducing heat loss compared to adults. Future physio-logging on pinnipeds throughout their annual lifecycle may therefore benefit from similar techniques used to implant loggers.

Tropicalization of the Temperate Zone: Spatiotemporal Variability of Winter Warming and Declining Freeze Days Across the United States - Vincent M. Brown; Derek T. Thompson; Buren B. DeFee; Michael J. Osland; Barry D. Keim (International Journal of Climatology, 2026)
We investigate changes in cool‐season and winter daily minimum (T min ) and maximum (T max ) temperatures, and the occurrence of freeze days, from 1952 to 2024 across the conterminous United States (CONUS). Emphasis is placed on the tropical‐temperate transition zone (TTTz) in the southeastern CONUS. During winter, ~70% of the land area exhibited T min warming rates exceeding those of T max . The countywide coldest T min became milder across 57% of the CONUS, while the coldest T max showed little change and even cooled east of the Rocky Mountains in the central CONUS. Across the TTTz, 75% of freeze days occur within a ~25–100‐day window, often fewer than 75 days in the southernmost areas. Approximately 80% of counties exhibited significant contractions in freeze‐day concentration, with the largest and most spatially consistent changes occurring in the Southeast, primarily driven by later start dates. Roughly 85% of the CONUS experienced a significant decline in freeze days, with the largest relative declines in regions where average winter T min is above freezing, while parts of the Pacific Northwest showed no significant change. An analysis of freeze day isopleths (30, 45, 60 and 75 days) across 20‐year periods showed that the mean latitude of freeze days has migrated poleward substantially. Between 101° W and 79° W in the TTTz, the 30 freeze‐day isopleth for the late period (2005–2024) was, on average, 122 km (~1.1° latitude) farther north than in the early period (1952–1971). Generally, the largest latitudinal shifts and percentage losses in freeze days occurred across low‐elevation, low‐relief regions at lower latitudes (e.g., the Mississippi River Valley), with abrupt shifts occurring near topographic gradients. Regions with sharp elevational gradients (e.g., Balcones Escarpment, Ouachita Mountains and Tennessee Valley) exhibited smaller temporal changes, likely reflecting the barrier‐like influence of higher terrain on the poleward retreat of freeze days.

Air pollution is linked to divergent cortical thickness patterns in brain regions vulnerable to Alzheimer’s disease - Lauren E. Salminen; Xinhui Wang; Andrew J. Petkus; Christine Fennema-Notestine; Jeremy A. Elman; Donald J. Hagler; Joel D. Kaufman; Joshua Millstein; Meredith N. Braskie; Joshua Liu; Hyung Jin Cho; Deydeep Kothapalli; et al. (NeuroToxicology, 2026)

Developing a methodology to identify personalities in farmed red deer - B.R. Thompson; D.R. Stevens; I.J. Gordon; T.M.R. Maxwell; S. Zydenbos; K.G. Dodds; D. Triadis; P. Gregorini (Applied Animal Behaviour Science, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A cohort study of factors associated with the incidence rate of keratoconjunctivitis in dairy heifers farmed under Mediterranean climatic conditions - Louis H. Maartens; Bruce Gummow; John D. Grewar; Jacqueline Picard; Peter N. Thompson (Preventive Veterinary Medicine, 2026)

Poor Water Quality and Food Insecurity in Ecuador: Disparities in Exposure and Associations With Young Child Feeding Practices - Joshua D. Miller; María Belén Ocampo Ordóñez; Ivonne Headley; Heather Wasser; Amanda L. Thompson (Journal of the Academy of Nutrition and Dietetics, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Correction: Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

Rangewide population genetic analysis of the Wood Turtle (Glyptemys insculpta) - Andrew R. Whiteley; Dana Weigel-Sheedy; Thomas S.B. Akre; Donald J. Brown; Deahn M. Donner; Charlie Eichelberger; Lori Erb; Katharine D. Gipe; Ellery Lassiter; Michael N. Marchand; Tricia Markle; Donald F. McAlpine; et al. (Conservation Genetics, 2026)

An integrated framework for early detection and transmissibility assessment of emerging variants in wastewater - Xingwen Chen; Tin Phan; Wei Lin Lee; Katie Clark; Steven F. Rhode; Samantha Brozak; Bruce Pell; Tsultrim Palden; Mats Leifels; Anna Gitter; Yang Kuang; Stefan Wuertz; et al. (International Journal of Hygiene and Environmental Health, 2026)

The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

An evaluation of alternative buffers for the transport and detection of Moraxella bovis and M. bovoculi on cotton wool swabs - Louis H. Maartens; Bruce Gummow; John D. Grewar; Peter N. Thompson; Jacqueline A. Picard (Research in Veterinary Science, 2026)

Oyster Size Distributions Vary Across Time and Space in the Tampa Bay Estuary, 250–2024 ce - Jaime A. Rogers; Thomas J. Pluckhahn; Kendal Jackson; Gregory S. Herbert; Stephen P. Geiger; Victor D. Thompson (Journal of Biogeography, 2026)
Aim Restoration benchmarks often assume an undisturbed historic range of variability, if they include historic information at all. However, recent research highlights the need for a more nuanced understanding of shifting baselines and how to best incorporate past variabilities in modern management. We investigate trends in oyster size through time (ca. 250–2024 ce ) and space (ca. 1000 km 2 ) in the Tampa Bay Estuary to understand when and where ecologically significant changes to oyster populations occurred. By implementing a multiscalar approach, this study contributes historical ecological data relevant to contemporary restoration and management efforts and provides insights into understanding long‐term socioecological dynamics in Florida's largest open‐water estuary. Location Tampa Bay Estuary, Florida, USA. Time Period ca. 250–2024 ce . Taxon Mollusca; Crassostrea virginica . Methods We measured sizes of over 15,000 oyster shells from archaeological sites and contemporary reefs across four estuarine sub‐basins over approximately 2000 years to assess how mean and maximum shell sizes responded to shifts in climate and human harvesting and settlement patterns. Results We demonstrate a non‐linear decline in oyster sizes through time, including a steep decline in oyster size prior to European colonization and commercial harvest. Changes in oyster size varied across sub‐regions, and there was no consistent response to climatic variability. A moderate rebound in oyster size during the 19th century is evident and coincides with several social factors that alleviated harvest pressures for a relatively short period. However, most of the largest contemporary oysters remain significantly smaller than those in the deeper past. Main Conclusions Archaeological datasets provide relevant historical ecological information for understanding modern era declines in molluscs. Our data reveal that no single baseline exists for oyster size in Tampa Bay. Instead, oyster populations responded in complex ways to climatic variability, ecological stressors and human interactions. Oyster size is a valuable functional trait linked to reproduction and reef resilience, and management targets that reference past demographic states should be framed as dynamic ranges and evaluated at sub‐regional scales.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Clinician Perspectives on the Implementation of a Web-Based Tool to Support Shared Decision-Making for Mid-Adult HPV Vaccination - Christopher W. Wheldon; Sarah A. Alkhatib; Jessica Grace; Idara N. Akpan; Ellen M. Daley; Gregory D. Zimet; Justin Luningham; Jonathan Engler; Erika L. Thompson (Journal of Cancer Education, 2026)
In 2019, the U.S. Advisory Committee on Immunization Practices recommended shared clinical decision-making (SCDM) for HPV vaccination among unvaccinated adults aged 27–45 years (i.e., mid-adult). However, the implementation of this recommendation is challenging. This study assessed a decision tool, HPV Decide, designed to facilitate SCDM for mid-adult HPV vaccination. We used exploratory sequential mixed methods to gather stakeholder and provider perspectives on a beta version of HPV Decide. Qualitative feedback from providers and stakeholders ( N = 24) was collected through semi-structured interviews. Quantitative data from health care providers ( N = 600) on usability in clinical practice was collected via online surveys. Interviewees provided feedback on the preferred delivery method and timing, the need for support and training, and key barriers and facilitators to SCDM. Quantitative data showed that 68.3% of providers were likely to use the tool, 67% believed it could be easily integrated into practice, and 54% thought patients would be interested in using it. Findings suggest that a web-based decision tool to facilitate SCDM for mid-adult HPV vaccination is both acceptable and feasible for integration into clinical practice. Providers expressed strong preferences for clinic-based access and electronic delivery. Clinicians supported the integration of a web-based decision tools into clinical practice to enhance shared decision-making.

Association of Milk Fat Intake on BMI Change and Nutrient Intake in WIC-Enrolled Toddlers - Rachel C. Grau; Lorrene D. Ritchie; Anisha Patel; Hannah R. Thompson (Journal of Nutrition Education and Behavior, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Corrigendum to “Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar)” [Aquaculture Volume 612, Part 1, 15 January 2026, 743142]. - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Mulching promotes soil health and carbon sequestration in arid urban landscapes - Juan P. Frene; Pramod Acharya; Marisa Thompson; Amrit D. Adhikari; Rajan Ghimire (Urban Ecosystems, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Identification and Characterisation of a Lethal Infectious Spleen and Kidney Necrosis Virus ( ISKNV ) From Indonesian Nile Tilapia Samples - Vanvimon Saksmerprome; Sarocha Jitrakorn; Kanokwan Dekham; Worakorn Phumiphanjarphak; Kim D. Thompson; Janina Costa; Matthijs Metselaar; Puey Ounjai; Pakorn Aiewsakun (Journal of Fish Diseases, 2026)
Infectious spleen and kidney necrosis virus (ISKNV), a member of the species Megalocytivirus pagrus1 , poses a significant threat to global aquaculture and has recently emerged as a major pathogen in farmed tilapia. This study reports the identification and characterisation of an ISKNV strain, designated ISKNV‐VS456, isolated from a lethal outbreak in Indonesian farmed tilapia. A Nile tilapia challenge experiment confirmed the virus's high pathogenicity, causing 100% mortality by 10 days post‐infection (dpi), with the kidney identified as a key site of viral replication. Infected fish exhibited clinical signs such as edema, skin haemorrhages, and organ haemorrhages, while histopathological analysis showed extensive damage in the kidney and spleen. The whole genome of ISKNV‐VS456 is 111,605 bp long, containing 124 open reading frames, consistent with a typical ISKNV genome. Several virulence‐related genes were detected, including ORF022L , ORF069L , ORF071L , ORF103R , and ORF111L . Phylogenetic analysis of the major capsid protein ( mcp ) gene placed ISKNV‐VS456 within the ISKNV‐I subgenotype, which is associated with high virulence in tilapia. This study provides the first whole‐genome sequence of a lethal Megalocytivirus pagrus1 strain ISKNV‐VS456 from Indonesian farmed tilapia ( Oreochromis niloticus ) in Indonesia, contributing to a better understanding of the virus in Southeast Asia, where the disease is most severe.

Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar) - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Association between late-life air pollution exposure and medial temporal lobe atrophy in older women - Xinhui Wang; Lauren E. Salminen; Andrew J. Petkus; Ira Frahmand; Joshua Millstein; Daniel P. Beavers; Mark A. Espeland; Guray Erus; Meredith N. Braskie; Paul M. Thompson; Margaret Gatz; Helena C. Chui; et al. (NeuroToxicology, 2026)

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

Development of a neutralization ccombody, synthetic hagfish antibody, for viral hemorrhagic septicemia virus (VHSV) targeting glycoprotein G - Abigail Joy D. Rodelas-Angelia; Mark Rickard N. Angelia; Seung Pyo Jeong; Young Rim Kim; Myoung Gwang Choi; Hyoung Jun Kim; Se Ryun Kwon; Kim D. Thompson; Tae Sung Jung (Fish & Shellfish Immunology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Characterization of bovine oviductal organoids: Polarity, cryopreservation, hormonal stimulation, and extracellular vesicles - Riley E. Thompson-Brandhagen; Mindy A. Meyers; Brandi Dunn; Nico G. Menjivar; Jennifer Palmer; D. N. Rao Veeramachaneni; Dawit Tesfaye; Fiona K. Hollinshead (Cell and Tissue Research, 2026)

Deep neural networks and genome-wide associations reveal the polygenic architecture of local brain aging - Nicholas J. Kim; Ayati Mishra; Nahian F. Chowdhury; Samuel D. Anderson; Owen M. Vega; Nikhil N. Chaudhari; Kenneth H. Buetow; Paul M. Thompson; Andrei Irimia (GeroScience, 2025)
Local brain age (LBA) is a regional metric of brain aging that offers a spatially resolved alternative to global brain age, but whose genetic basis is unexplored. This study reports the first genome-wide association study of cortical LBA, as estimated by a deep neural network from the T 1 -weighted magnetic resonance images of 41,708 cognitively normal adults in the UK Biobank. We identified 1,212 single-nucleotide polymorphisms (SNPs) significantly associated with LBA in at least one brain region. Genes mapped to these SNPs are involved in developmental, metabolic, immune, and cytoskeletal pathways. Dimensionality reduction of SNP association profiles uncovered three clusters linked to morphogenetic, cytoskeletal, and immuno-epigenetic processes, helping to relate neuroanatomic, immunosenescent and epigenetic mechanisms of brain aging. Top variants are mapped to KCNK2 , NUAK1 , GMNC , MSL2 , and to other genes implicated in neurodevelopment and neurodegeneration. Spatial clustering of LBA-associated variants in default mode, limbic, and motor network regions parallel regional vulnerability to Alzheimer’s disease and frontotemporal dementia. These findings establish a polygenic architecture for regional brain aging and support LBA as a genetically informed phenotype for studying aging-related neurodegeneration. Our results suggest that cortical aging is not governed by isolated loci but by coordinated genetic programs—rooted in development, metabolism, and cellular structure—that confer lifelong patterns of regional brain vulnerability and resilience. This first genetic dissection of spatially specific brain aging reveals a polygenic landscape of coordinated genetic programs, developmentally encoded and metabolically maintained during senescence. This study reframes aging as an anatomically specific genetic process reflecting the varying structural vulnerabilities observed across neurodegenerative diseases.

Corrigendum to “Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression” [Fish Shellfish Immunol. 149 (2024) 109549] - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2025)

Characterization of toxins in soils around cassava mills within the sedimentary formation of Southwestern Nigeria - Akintayo O. Ojo; Oluwaseun Ajibola; Abdulwasiu O. Ambali; Mandu D. Thompson (Arabian Journal of Geosciences, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

A Qualitative Exploration of Parent and School Staff Perceptions of Freshly Prepared Meals and Food Waste Implications in California Elementary Schools - Katharina C. Fiedler; Reka Vasicsek; Maya Ezekiel; Celeste Felix; Danielle L. Lee; Hannah Thompson; Wendi Gosliner; Stephanie Willits; Kristine Madsen; Lorrene D. Ritchie (Journal of Nutrition Education and Behavior, 2025)

Performance of soy-winter wheat relay intercropping under various water conditions - Jennifer B. Thompson; Thomas F. Döring; Sonoko D. Bellingrath-Kimura; Jing Yu; Moritz Reckling (Field Crops Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

Identity-by-descent segments in large samples - Seth D. Temple; Elizabeth A. Thompson (Theoretical Population Biology, 2025)

Identification of false methane plumes for orbital imaging spectrometers: A case study with EMIT - Chuchu Xiang; David R. Thompson; Robert O. Green; Jay E. Fahlen; Andrew K. Thorpe; Philip G. Brodrick; Red Willow Coleman; Amanda M. Lopez; Clayton D. Elder (Remote Sensing of Environment, 2025)

The Survivors Overcoming and Achieving Resiliency (SOAR) Program: Improving Dietary Guideline Adherence Among Breast Cancer Survivors in a Virtual Teaching Kitchen - D. Riccardi; J. Hubbard; S. Pflanzer; H. Gray; Z. Thompson; S. Pabbathi (Journal of the Academy of Nutrition and Dietetics, 2025)

Longer WIC Participation Is Associated With Higher Diet Quality and Consumption of WIC-Eligible Foods Among Children 2-5 Years Old - Lauren E. Au; Hannah R. Thompson; Lorrene D. Ritchie; Brenda Sun; Thea P. Zimmerman; Shannon E. Whaley; Amanda Reat; Kavitha Sankavaram; Christine Borger (Journal of the Academy of Nutrition and Dietetics, 2025)

Probiotic and postbiotic effects of Bacillus velezensis AAHM-BV2354 on boosting immunity, growth performance, antioxidant activity and resistance to Edwardsiella tarda infection in pangasius (Pangasianodon hypophthalmus) - Nugroho Wiratama; Benchawan Kumwan; Pakapon Meachasompop; Yosapon Adisornprasert; Prapansak Srisapoome; Kim D. Thompson; Phornphan Phrompanya; Patcharapong Thangsunan; Pattanapong Thangsunan; Kanokporn Saenphet; Supap Saenphet; Wararut Buncharoen; et al. (Fish & Shellfish Immunology, 2025)

Effects of immersion vaccination in striped catfish (Pangasianodon hypophthalmus) using a cationic lipid-based mucoadhesive nanovaccine against Edwardsiella ictaluri - Sirikorn Kitiyodom; Manoj Tukaram Kamble; Jakarwan Yostawonkul; Pimwarang Sukkarun; Kim D. Thompson; Nopadon Pirarat (Fish & Shellfish Immunology, 2025)

Development and characterization of an innovative Flavobacterium oreochromis antigen-encapsulated hydrogel bead for enhancing oral vaccine delivery in hybrid red tilapia (Oreochromis spp.) - Patcharapong Thangsunan; Pattanapong Thangsunan; Thanisorn Mahatnirunkul; Wararut Buncharoen; Kanokporn Saenphet; Supap Saenphet; Jitraporn Phaksopa; Kim D. Thompson; Prapansak Srisapoome; Benchawan Kumwan; Pakapon Meachasompop; Nuttee Suree; et al. (Fish & Shellfish Immunology, 2025)

Trends in Fomepizole Use for Acetaminophen Poisoning in the United States; 2013–2024 - Mitchell D’Aloia; Dale Smith; Randy Boley; Emily Schamber; Dillon Thorpe; Trevonne M. Thompson; Neeraj Chhabra (Journal of Medical Toxicology, 2025)
Background Fomepizole has been suggested as adjunctive therapy for severe acetaminophen poisoning though clinical efficacy is unknown. We sought to determine trends in the use of fomepizole for acetaminophen poisoning. Methods This is a cross-sectional analysis of hospitalized patients with acetaminophen poisoning from January 2013 through December 2024, using Epic Cosmos, a research database of 298 million patients nationally. We identified encounters involving acetaminophen poisoning by International Classification of Diseases, version 10 (ICD-10-CM) code. Data extracted included administration of N-acetylcysteine (NAC) and fomepizole, demographic data, and outcomes of death and liver transplantation. Data were analyzed using descriptive statistics to identify trends and multivariable logistic regression to determine associations with death. Results There were 114,111 hospital encounters involving acetaminophen poisoning with 64,957 (56.92%) receiving NAC, and 1,552 (1.36%) receiving fomepizole. In 2013, 0.44% of NAC-treated acetaminophen poisoning cases also received fomepizole. This rose to 6.27% in 2024. From 2013 to 2019, the proportion of NAC-treated acetaminophen cases receiving fomepizole was stable, but from 2019 to 2024, there was a 1029.64% increase in fomepizole use. Regression modeling indicated increased odds for death (OR = 5.88, aOR = 5.32 [95% CI: 4.52, 6.27]) among those who received fomepizole in addition to NAC, indicating increased fomepizole use in patients with severe toxicity. Conclusion Fomepizole use in acetaminophen poisoning has risen dramatically since 2019, particularly among patients at highest risk for death and liver transplantation. It is of critical importance to determine the efficacy of fomepizole for acetaminophen poisoning.

Estimated health outcomes of breast cancer screening in the national breast and cervical cancer early detection program by race/ethnicity - Donatus U. Ekwueme; Kelly A. Reagan; Szu-Yu Kao; Sabitha Dasari; Kristy M. Kenney; Manxia Wu; Trevor D. Thompson; Jacqueline W. Miller (Cancer Causes & Control, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Machine vision-based assessment of fall color changes in apple leaves and its relationship with nitrogen concentration - Achyut Paudel; Jostan Brown; Priyanka Upadhyaya; Atif Bilal Asad; Safal Kshetri; Joseph R. Davidson; Cindy Grimm; Ashley Thompson; Bernardita Sallato; Matthew D. Whiting; Manoj Karkee (Computers and Electronics in Agriculture, 2025)

Frequency of Attendance to a Behavioral Intervention on Health-related Outcomes in a Multicomponent Food as Medicine Intervention - Marcela D. Radtke; Lan Xiao; Wei-ting Chen; Steven Chen; Ben Emmert-Aronson; Ariana Thompson-Lastad; Elizabeth Markle; Lisa G. Rosas; June Tester (Journal of Nutrition Education and Behavior, 2025)

The Greatest Extinction Event in 66 Million Years? Contextualising Anthropogenic Extinctions - Jack H. Hatfield; Bethany J. Allen; Tadhg Carroll; Christopher D. Dean; Shuyu Deng; Jonathan D. Gordon; Thomas Guillerme; James P. Hansford; Jennifer F. Hoyal Cuthill; Philip D. Mannion; Inês S. Martins; Alexander R. D. Payne; et al. (Global Change Biology, 2025)
Biological communities are changing rapidly in response to human activities, with the high rate of vertebrate species extinction leading many to propose that we are in the midst of a sixth mass extinction event. Five past mass extinction events have commonly been identified across the Phanerozoic, with the last occurring at the end of the Cretaceous, 66 million years ago (Ma). However, life on Earth has always changed and evolved, with most species ever to have existed now extinct. The question is, are human activities increasing the rate and magnitude of extinction to levels rarely seen in the history of life? Drawing on the literature on extinctions primarily over the last 66 million years (i.e., the Cenozoic), we ask: (1) what comparisons can meaningfully be drawn? and (2) when did the Earth last witness an extinction event on this scale? We conclude that, although challenging to address, the available evidence suggests that the ongoing extinction episode still falls a long way short of the devastation caused by the bolide impact 66 Ma, but that it has likely surpassed most other Cenozoic events in magnitude, with the possible exception of the Eocene–Oligocene transition (34 Ma), about which much uncertainty remains. Given the number of endangered and at‐risk species, the eventual magnitude of the current event will depend heavily on humanity's response and how we interact with the rest of the biosphere over the coming millennia.

Assessing the Effectiveness of 3D-Printed Ceramic Structures for Coral Restoration: Growth, Survivorship, and Biodiversity Using Visual Surveys and eDNA - Vriko Yu; Alison D. Corley; Horace Lau; Philip D. Thompson; Zhongyue Wilson Wan; Jane C. Y. Wong; Zoe Kwan Ting Wong; Louise Wai Hung Li; Shelby E. McIlroy; David M. Baker (Journal of Marine Science and Engineering, 2025)
Coral reef degradation has spurred the development of artificial structures to mitigate losses in coral cover. These structures serve as substrates for coral transplantation, with the expectation that growing corals will attract reef-associated taxa—while the substrate’s ability to directly support biodiversity is often neglected. We evaluated a novel 3D-printed modular tile made of porous terra cotta, designed with complex surface structures to enhance micro- and cryptic biodiversity, through a restoration project in Hong Kong. Over four years, we monitored 378 outplanted coral fragments using diver assessments and photography, while biodiversity changes were assessed through visual surveys and eDNA metabarcoding. Coral survivorship was high, with 88% survival after four years. Visual surveys recorded seven times more fish and almost 60% more invertebrates at the restoration site compared to a nearby unrestored area. eDNA analyses revealed a 23.5% higher eukaryote ASV richness at the restoration site than the unrestored site and 13.3% greater richness relative to a natural reference coral community. This study highlights the tiles’ dual functionality: (1) supporting coral growth and (2) enhancing cryptic biodiversity, an aspect often neglected in traditional reef restoration efforts. Our findings underscore the potential of 3D-printed ceramic structures to improve both coral restoration outcomes and broader reef ecosystem recovery.

Human health risk assessment of three smoke flavoring primary products - G. Brorby; A. Franzen; C. Thompson; D. Wikoff; C. Doepker (Food and Chemical Toxicology, 2025)

Collapse and restoration of mature forest habitat in California - Gavin M. Jones; Brandon M. Collins; Lacey E. Hankin; Ronan Hart; Marc D. Meyer; Jon Regelbrugge; Zachary L. Steel; Craig Thompson (Biological Conservation, 2025)

In-situ formation of glyphosate and AMPA in activated sludge from phosphonates used as antiscalants and bleach stabilizers in households and industry - L. Engelbart; S. Bieger; K. Thompson; L. Fischer; T. Bader; M. Kramer; S.B. Haderlein; A.M. Röhnelt; P.R. Martin; D. Buchner; R. Bloch; H. Rügner; et al. (Water Research, 2025)

Determining alkalinity, carbon loading, and degradation of aqueous amine in CO2 capture processes using heuristic methods - Bradley D. Irvin; Trevor Jones; Jonathan V. Pelgen; Zhen Fan; Keemia Abad; Saloni Bhatnagar; Reynolds A. Frimpong; Heather Nikolic; Jesse Thompson; Kunlei Liu (International Journal of Greenhouse Gas Control, 2025)

Evaluation of immune responses and protection in Asian seabass (Lates calcarifer Bloch, 1790) against Vibrio vulnificus using immersion and oral nanoemulsion vaccines - Chatchai Rodwihok; Kim D. Thompson; Prapansak Srisapoome; Patcharapong Thangsunan; Pattanapong Thangsunan; Wararut Buncharoen; Kanokporn Saenphet; Supap Saenphet; Pakapon Meachasompop; Benchawan Kumwan; Jasper Kit Tangal; Nugroho Wiratama; et al. (Fish & Shellfish Immunology, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Continental Patterns of Phenotypic Variation Along Replicated Urban Gradients: A Mega‐Analysis - M. J. Thompson; J. G. A. Martin; C. Biard; J. Bleu; C. J. Branston; P. Capilla‐Lasheras; N. J. Dingemanse; D. M. Dominoni; M. Eens; T. Eeva; K. L. Evans; C. Isaksson; et al. (Ecology Letters, 2025)
Individual variation among and within natural populations can have eco‐evolutionary implications by, for example, affecting species interactions or evolutionary potential. Urban systems present a unique opportunity to evaluate how environmental change shapes variation since urban phenotypic differentiation is widely documented on contemporary timescales. We introduce and test three hypotheses to determine how urbanisation affects phenotypic variation at different population levels. Combining 21 long‐term datasets in a mega‐analysis approach, we synthesise how urbanisation impacts variation in tarsus length and lay date among and within subpopulations of great and blue tits ( Parus major , Cyanistes caeruleus ) at a continental scale. Our synthesis reveals that urbanisation is associated with increased phenotypic variation within subpopulations by 11% on average, and by as much as 25% across the species and traits examined. We also find some evidence (for tarsus length in great tits) that urbanisation increases differentiation between subpopulations. We did not, however, find that urbanisation increases differences between subpopulations in their within‐subpopulation variation. Our synthesis provides novel insights into how urban contexts impact individual diversity at different spatial scales and we highlight future directions that could establish the genetic and environmental effects that underlie these continental patterns of urban phenotypic variation.

Effectiveness of a new cationic lipid-based nanovaccine for enhancing immersion vaccination against Flavobacterium oreochromis in red tilapia (Oreochromis sp.) - Sirikorn Kitiyodom; Manoj Tukaram Kamble; Jakarwan Yostawonkul; Kim D. Thompson; Nopadon Pirarat (Fish & Shellfish Immunology, 2025)

Publisher Correction: Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)

Investigation of blood–brain barrier penetration and pharmacokinetics of a new formulation of cyanide antidote dimethyl trisulfide - Lóránd Kiss; Fruzsina R. Walter; Gábor Katona; Ana Raquel Santa-Maria; Ashley C. Whiteman; Christian T. Rios; Kyler D. Kelley; Breanna Nelson; David E. Thompson; Ildikó Csóka; Piroska Szabó-Révész; Mária A. Deli; et al. (Toxicology and Environmental Health Sciences, 2025)
Objective During cyanide poisoning, the rescue of vital organs like the brain is urgent. However, due to the presence of the blood–brain barrier (BBB), the currently available cyanide antidotes cannot reach the brain. Dimethyl trisulfide (DMTS) is a potent cyanide antidote and has excellent BBB permeability. Nonetheless, its formulation and application are challenging due to its highly lipophilic profile. In this work, a novel DMTS formulation, called FF-DMTS, was investigated. Its effect on in vitro DMTS permeability through BBB models, cellular viability, and in vivo absorption were tested. Methods The particle size was measured in FF-DMTS formulation. The permeability of DMTS in this new formulation was tested in BBB-PAMPA and in primary triple co-culture models of BBB. The effect of FF-DMTS on cellular viability was determined. To test the membrane and barrier integrity transendothelial electrical resistance (TEER) and cell layer impedance measurements, immunofluorescent stainings and the fluorescein permeability technique were applied. The pharmacokinetics of DMTS were revealed in blood and brain tissue. Results The average size of micelles in FF-DMTS was 16 nm. The permeability of DMTS through BBB-PAMPA and cell culture model was 7.68 × 10 –6 and 23.81 × 10 –6 cm/s, respectively. The FF-DMTS disturbed the barrier integrity of brain endothelial cells without causing any alteration in cellular viability until 300 µg/ml DMTS concentration. After administration of 150 mg/kg DMTS to mice, its absorption into the blood was rapid (5 min) and the plasma concentration of DMTS reached 5.2 µg/ml. The DMTS was also detected in brain, where its peak concentration was 495 ng/g brain tissue after 10 min of intramuscular administration. Furthermore, even 2 h later, DMTS was detected in brain. Conclusions Here, we showed that the novel FF-DMTS formulation has good permeability through BBB and a remarkable pharmacokinetic profile. Therefore, further investigation of the efficacy of FF-DMTS for treating cyanide intoxication is important.

Characterisation of tyre wear particle transport from road runoff to sea in coastal environments - Florence N.F. Parker-Jurd; Geoffrey D. Abbott; Daniel C. Conley; Cijo M. Xavier; Florian Pohl; Richard C. Thompson (Marine Pollution Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Equity in unilateral value chain policies: A monitoring framework for the EUDR and beyond - Constance L. McDermott; Thomas Addoah; Tawiah Agyarko-Kwarteng; Rebecca Asare; Alex Assanvo; Mairon Bastos Lima; Helen Bellfield; Amanda Berlan; Sophia Carodenuto; Toby Gardner; Rachael D. Garrett; Caitlin Hafferty; et al. (Forest Policy and Economics, 2025)

Evaluation of a hydrogel platform for encapsulated multivalent Vibrio antigen delivery to enhance immune responses and disease protection against vibriosis in Asian seabass (Lates calcarifer) - Anurak Uchuwittayakul; Kim D. Thompson; Pattanapong Thangsunan; Jitraporn Phaksopa; Wararut Buncharoen; Kanokporn Saenphet; Benchawan Kumwan; Pakapon Meachasompop; Supap Saenphet; Nugroho Wiratama; Thanisorn Mahatnirunkul; Phunsin Kantha; et al. (Fish & Shellfish Immunology, 2025)

Registry versus claims-based index dates for studies of cancer diagnosis in administrative data - Sarah E. Soppe; Sharon Peacock Hinton; Jamie C. Halula; Jennifer L. Lund; Chris D. Baggett; Sandi L. Pruitt; Megan A. Mullins; Ellis C. Dillon; Matthew E. Barclay; Matthew Thompson; Nicholas Pettit; Georgios Lyratzopoulos; et al. (Cancer Causes & Control, 2025)

Nonnative Species Richness and Dominance Reveal Differing Support for Invasion Theory at a Continental Extent - Lily M. Thompson; William K. Annis; Stephen R. Midway; Julian D. Olden; Brandon K. Peoples (Global Ecology and Biogeography, 2025)
Aim Empirical tests of conceptual hypotheses describing species invasions often differ depending on the spatial scale (spatial resolution and extent of study area) at which they were conducted. Some of this disparity may arise from tradeoffs in data quality necessitating the use of different indices of community invadedness among scales. Local‐scale studies typically use fine‐resolution, descriptive measures of community invadedness (‘dominance’, the proportion nonnative individuals) at limited spatial extents, while macroscale studies often aggregate datasets to cover large spatial extents but use coarser spatial resolution and less descriptive indices (nonnative species richness). We investigated the consequences of using different indices to represent community invadedness at different spatial scales, and explored the implications for hypothesis testing when nonnative richness and dominance are not related. Location 23,793 stream segments within 17 regional watersheds, conterminous United States. Time Period 2000–2023. Major Taxa Studied Freshwater fishes. Methods Using a large‐extent, fine‐resolution dataset, we evaluated the correlation between nonnative species richness and dominance in communities, and compared empirical support for prominent invasion hypotheses (biotic resistance, disturbance facilitation) in identical Bayesian hierarchical models with community invadedness represented by each metric. Results Nonnative richness and dominance were weakly correlated, allowing us to classify communities into four archetypes based on relationships between the two indices. Empirical support for both invasion hypotheses differed between the two indices of community invadedness both overall and within regional watersheds. Main Conclusions Nonnative species richness and dominance describe different facets of the invasion process and may under‐ or over‐represent community invadedness when considered alone. Empirical disparity between models estimating the two metrics may be an important source of scale‐dependent inference in invasion ecology. When assembling datasets for macroscale studies, retaining fine spatial resolution as much as possible will allow researchers opportunities to use more descriptive and potentially complementary indices of community invadedness.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

One well-planned and executed exchange is better than two: Lessons learned from a reciprocal fisheries learning exchange between Madagascar and Mexico - Katie R. Thompson; Steve Rocliffe; Alejandro Castillo López; Tinah Martin; S. Hoyt Peckham; Christian Portillo; Xavier Vincke; Lekelia D. Jenkins (Marine Policy, 2025)

Nest location and pheromone concentrations interact to influence female nest choice in sea lamprey - Skye D. Fissette; Tyler J. Buchinger; Sonam Tamrakar; Henry T. Thompson; Weiming Li (Animal Behaviour, 2025)

A cross-sectional study of keratoconjunctivitis among dairy cattle farms subject to Mediterranean climatic conditions - L. H. Maartens; P. N. Thompson; J. D. Grewar; J. Picard; B. Gummow (Tropical Animal Health and Production, 2025)
The epidemiology of bovine keratoconjunctivitis (BK) is complex and involves several conjunctival microbiota as well as host and environmental factors. Data about BK in dairy cattle are scarce, and even scarcer for dairy cattle in Mediterranean climates. We determined the BK prevalence among dairy cattle in Southern Africa’s Mediterranean climatic zone by examining 1,675 dairy cattle across 28 herds. Conjunctival swabs were analysed using real-time PCR. Risk factor data were collected by questionnaire and evaluated by multivariable logistic regression. The BK prevalence was 19.4%, (95% CI: 15.0 – 24.8%). Mesomycoplasma bovoculi was demonstrated in 75.7% of the sampled eyes (95% CI: 62.8 – 85.2%) across all farms. Moraxella bovis (18.3%, 95% CI: 11.9 – 27.0%) and Moraxella bovoculi (8.6%, 95% CI: 4.6 – 15.6%) were detected on 89% and 64% of the farms, respectively. Mycoplasmopsis bovis was rarely encountered. Moraxella bovoculi was significantly associated with BK (OR: 2.7, 95% CI: 1.3 – 5.6, Wald P : 0.01). Prevalence varied significantly by age and breed. Shade availability (OR: 2.5, 95% CI: 1.4 – 4.4, Wald P < 0.01), sanitation frequency, (OR: 0.4, 95% CI: 0.2 – 1.0, Wald P : 0.05), fly burden (OR: 2.1, 95% CI: 1.3 – 3.6, Wald P < 0.01) and introduced cattle (OR: 2.0, 95% CI: 1.1 – 3.5, Wald P : 0.02) were significantly associated with the prevalence of BK. Closed herds with proper biosecurity, fly control via sound management practices, and access to shade are recommended for preventing BK in dairy herds farmed in a Mediterranean climate.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

The application of digital tools for knowledge sharing in agriculture: A longitudinal case study from four Australian grower groups - A. Ollerenshaw; H. Thompson; H. Luke; P. Cooke; F. Best; N. Scholz; D. Fear; N. Craig; J. Telfer; A. Wright; S. Kruger (Computers and Electronics in Agriculture, 2025)

Continuing Long‐Term Shifts in Larval Fish Phenology in the Southern California Current Ecosystem Are Matched by Rapid Advances in the North - Kathryn S. Chen; Colleen M. Petrik; Rebecca G. Asch; Andrew R. Thompson; Toby D. Auth (Global Change Biology, 2025)
Changing environmental conditions are leading to shifts in the timing of seasonal events globally. In the ocean, environmental cues affecting larval fish (ichthyoplankton) abundance may not be synchronized with factors optimizing larval and juvenile survival, making the study of ichthyoplankton phenology in the context of a changing environment critical. In the southern California Current Ecosystem (CCE), a major eastern boundary current upwelling system, significant long‐term shifts in larval fish phenology have been previously observed. To assess the stability of these estimates and extend them to the northern CCE, we evaluated multidecadal trends in ichthyoplankton abundance for 57 species from the California Cooperative Oceanic Fisheries Investigations (CalCOFI) and 25 species from the Newport Hydrographic Line (NH Line). We show that on average, larval fish phenology in the southern CCE has continued to advance with an estimated rate of −0.18 ± 0.05 day year −1 from 1951 to 2022, while phenology in the northern CCE has advanced at a rate of −0.48 ± 0.26 day year −1 from 1996 to 2023. Thirty‐nine percent of species showed significant advancing phenology, 12% exhibited delayed phenology, and 49% showed no long‐term linear change. A comparison analysis showed that species in these groups had similar rates of change between the two locations for the 1997–2017 period. Phenological shifts in the southern CCE tracked changes in the phenology of upper ocean temperature, zooplankton, and upwelling. These variables poorly explained shifts in the northern CCE, where short‐term effects of the El Niño–Southern Oscillation and the 2014–2016 marine heatwave on ichthyoplankton phenology were observed for some species. This research highlights regional variability and continuing phenological shifts in one of the world's most productive marine ecosystems.

Stormwater controls for channel stability: Focusing on bed material transport prevents degradation - S. Towsif Khan; T. Wynn-Thompson; D. Sample (Journal of Environmental Management, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

Community Outreach, Engagement, and Mentoring Program for Underrepresented Scholars in Cancer Health Disparities - Lorna H. McNeill; Cassandra L. Harris; Terrence R. Adams; Berta R. Salazar; Crystal L. Roberson; Leonetta B. Thompson; Kamisha H. Escoto; Kayce D. Solari Williams; Shine Chang; Tzuan A. Chen; Birnur Buzcu-Guven; Lorraine R. Reitzel (Journal of Cancer Education, 2025)

Analysis of Oncology and Radiation Therapy Representation on the National Board of Medical Examiners Official Practice Material for the United States National Standardized Medical Board Examinations - Mary T. Mahoney; Lauren C. Linkowski; Trudy C. Wu; Jie Jane Chen; Beth K. Neilsen; Petria S. Thompson; Michael D. Mix; Karna T. Sura; Malcolm D. Mattes (Journal of Cancer Education, 2025)
Radiation therapy (RT) is a critical component of multidisciplinary cancer care, but has inconsistent curricular exposure. We characterize the radiation oncology (RO) content on the standardized undergraduate medical examinations by comparing its context and prevalence with other domains in oncology. National Board of Medical Examiners (NBME) self-assessments and sample questions for the United States Medical Licensing Exam (USMLE) Steps 1–3 and NBME clinical science shelf examinations were accessed ( n = 3878). Questions were inductively analyzed for content pertaining to oncology and treatment modalities of RT, systemic therapy (ST), and surgical intervention (SI). Questions were coded using USMLE Physician Tasks/Competencies and thematic analysis. Descriptive statistics and analyses using the Kruskal–Wallis test are reported. A total of 337 questions (8.6%) within the USMLE and shelf exams included oncology content, with 101 questions (2.6%) referencing at least one cancer treatment modality ( n = 35 RT, 45 ST, 57 SI). Treatment questions were more common on USMLE Step 2 CK ( n = 35/101, 32%) compared to Step 1 ( n = 23/101, 23%) and Step 3 ( n = 8/101, 8%) ( p < 0.001). RT was significantly less likely to be the correct answer (2/35, 6%) compared to ST (4/45, 9%) and SI (18/57, 32%) ( p = 0.003). Therapeutic oncology questions are uncommon on the examination material, with an under-representation of radiation-related content, and contextual bias favoring surgical approaches. We advocate for greater RO involvement in the content creation of such examinations to help trainees better understand multidisciplinary cancer care.

Cleansing our waters: how riffle fish communities in the Spring River of Kansas responded to pollution legislation, mining remediation, and improved water quality - Alexandra D. King; James E. Whitney; Kali L. Boroughs; Joshua A. Holloway; Aliyah N. Clemens; Austin D. Thompson (Environmental Management, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

Spatial Scale and the Underestimation of Stream Fish Community Invadedness - Lily M. Thompson; William K. Annis; Stephen R. Midway; Julian D. Olden; Brandon K. Peoples (Global Ecology and Biogeography, 2025)
Scale‐Dependency of Native Status Classifying populations as native or nonnative requires well‐defined range boundaries for species. While many studies define native status according to large biogeographic realms, natural dispersal barriers often limit species distributions at regional or smaller spatial extents. As such, native/nonnative definitions are inherently scale‐dependent and estimates of community invadedness thus depend on the spatial resolution at which native status is defined. For example, nonnative species can be introduced among realms, among regions within realms, and among ecological provinces within regions (hereafter, simply “provinces”). By explicitly considering the scale‐dependency of native/nonnative status definitions, we can more effectively compare results across studies, more comprehensively evaluate the degree of invasion levels, and more objectively communicate the native status of a species. Location 30,034 stream segments, conterminous United States. Time Period 2000–2023. Major Taxa Studied Freshwater fishes. Quantifying Fish Community Invadedness Across US Streams We illustrate the importance of scale‐dependent native status definitions by quantifying nonnative species richness and relative abundance in stream fish communities across the United States, finding that provincially nonnative species are nearly four times as prevalent as extra‐realm nonnative species, and represented approximately 10% of all individuals in average community surveys. Implications Unrealistically broad native status definitions underestimate community invadedness. Dismissing regionally and provincially nonnative species can have severe ecological consequences, including displacement and hybridisation with native species and the loss of unique communities through biotic homogenisation. These consequences may undermine efforts to maintain and protect distinct local biodiversity and conserve endemic species.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The cost of operational complexity: A causal assessment of pre-fire mitigation and wildfire suppression - Jesse D. Young; Erin Belval; Benjamin Gannon; Yu Wei; Christopher O'Connor; Christopher Dunn; Bradley M. Pietruszka; David Calkin; Matthew Thompson (Forest Policy and Economics, 2024)

Nitrogen and Spacing Requirements for Advanced Chipping Selections ND7799c-1 and ND7519-1 - Jed D. Grow; Asunta L. Thompson; Gary A. Secor; Andrew P. Robinson (American Journal of Potato Research, 2024)
Adoption of new cultivars is challenging for commercial growers. To understand the best nitrogen fertilization rate (90, 134, 179, and 224 kg N ha -1 ) and within-row spacing (15, 23 and 31 cm) for two potential potato cultivar releases from North Dakota State University, a study was carried out in 2019 and 2020 in North Dakota. The advanced chipping selections ND7799c-1 and ND7519-1 were compared to a chip industry standard, Dakota Pearl. In 2019, ND7799c-1 grown at 23 cm within-row spacing had similar marketable yield to Dakota Pearl. In 2020, ND7519-1 at all within-row spacings, and ND7799c-1 at 15 and 23 cm within-row spacing, yielded similarly to Dakota Pearl. Nitrogen rate did not affect yield or chipping quality in 2019 or 2020. The advanced selections had lower sucrose and glucose levels one month after harvest compared to Dakota Pearl in 2020. ND7799c-1 stored for 8 months, and ND7519-1 for 6 months, before chip quality declined. This research demonstrates the potential for ND7799c-1 and ND7519-1 to be successful chip processing cultivars for the Northern Plains.

Multi‐Trophic Level Responses to Marine Heatwave Disturbances in the California Current Ecosystem - Tz‐Chian Chen; Mati Kahru; Michael R. Landry; Mark D. Ohman; Andrew R. Thompson; Michael R. Stukel (Ecology Letters, 2024)
Marine heatwaves (MHWs) caused by multiple phenomena with days to months duration are increasingly common disturbances in ocean ecosystems. We investigated the impacts of MHWs on pelagic communities using spatially resolved time‐series of multiple trophic levels from the Southern California Current Ecosystem. Indices of phytoplankton biomass mostly declined during MHWs because of reduced nutrient supply (excepting Prochlorococcus ) and were generally more sensitive to marine heatwave intensity than duration. By contrast, mesozooplankton (as estimated by zooplankton displacement volume) were somewhat more strongly correlated with MHW duration than intensity. Zooplankton anomalies were also positively correlated with fucoxanthin (diatom) anomalies, highlighting possible bottom‐up influences during MHWs. Mobile consumers (forage fish) showed more complex responses, with fish egg abundance declining during MHWs but not correlating with any MHW characteristics. Our findings provide partial evidence of how MHW characteristics can shape variable ecological responses due to the differing life spans and behaviours of different trophic levels.

Species identification of modern and archaeological shark and ray skeletal tissues using collagen peptide mass fingerprinting - Michael Buckley; Ellie-May Oldfield; Cristina Oliveira; Clara Boulanger; Andrew C. Kitchener; Nicole R. Fuller; Traci Ardren; Victor D. Thompson; Scott M. Fitzpatrick; Michelle J. LeFebvre (Frontiers in Marine Science, 2024)
Introduction Elasmobranchs, such as sharks and rays, are among the world’s most endangered vertebrates, with over 70% loss in abundance over the past 50 years due to human impacts. Zooarchaeological baselines of elasmobranch diversity, distribution, and exploitation hold great promise for contributing essential historical contexts in the assessment of contemporary patterns in their taxonomic diversity and vulnerability to human-caused extinction. Yet, the historical ecology of elasmobranchs receives relatively less archaeological attention compared to that of ray-finned fishes or marine mammals, largely due to issues of taxonomic resolution across zooarchaeological identifications. Methods We explore the use of Zooarchaeology by Mass Spectrometry (ZooMS) for species identification in this unstudied group, using an archaeological case study from the marine environments of the Florida Keys, a marine biodiversity hotspot that is home to an array of elasmobranch species and conservation efforts. By comparison with 39 modern reference species, we could distinguish 12 taxa within the zooarchaeological assemblage from the Clupper archaeological site (Upper Matecumbe Key) that included nine sharks, two rays and a sawfish. Results and discussion The results indicate that, through additional complexity of the collagen peptide mass fingerprint, obtained due to the presence of the cartilaginous type II collagen, ZooMS collagen peptide mass fingerprinting provides exceptionally high taxonomic resolution in this group, yielding species-level identifications in all cases where sufficient reference material was used. This case study also highlights the added value of ZooMS for taxa that are more difficult to distinguish in zooarchaeological analyses, such as vertebrae of the Atlantic sharpnose shark ( Rhizoprionodon terraenovae ) and the hammerhead sharks ( Sphyrna spp.) in the Florida Keys. Therefore, the application of collagen peptide mass fingerprinting to elasmobranchs offers great potential to improve our understanding of their archaeological past and historical ecology.

Distribution, abundance, and reproductive stages of salps, doliolids, and chaetognaths in different water masses of the shelf and open ocean of the Southwestern Atlantic Ocean between 31° and 38° S - Gustavo A. Thompson; Graciela N. Molinari; Martin D. Ehrlich; Maria C. Daponte (Journal of Marine Systems, 2024)

Passive immunoprophylaxis with Ccombodies against Vibrio parahaemolyticus in Pacific white shrimp (Penaeus vannamei) - Wanna Sirimanapong; Prawporn Thaijongrak; Chiranan Sudpraseart; Dennis Berbulla Bela-ong; Abigail Joy D. Rodelas-Angelia; Mark Rickard N. Angelia; Seungbeom Hong; Jaesung Kim; Kim D. Thompson; Tae Sung Jung (Fish & Shellfish Immunology, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Corrigendum: Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Insect meal in aquafeeds: A sustainable path to enhanced mucosal immunity in fish - S.M. Majharul Islam; Muhammad A.B. Siddik; Mette Sørensen; Monica F. Brinchmann; Kim D. Thompson; David S. Francis; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Leveraging the biotechnological promise of the hagfish variable lymphocyte receptors: tools for aquatic microbial diseases - Dennis B. Bela-ong; Jaesung Kim; Kim D. Thompson; Tae Sung Jung (Fish & Shellfish Immunology, 2024)

The American College of Medical Toxicology (ACMT) Commitment to Diversity, Equity, and Inclusion in Medical Toxicology - Peter D. Akpunonu; Richard J. Church; Kavita M. Babu; Trevonne M. Thompson (Journal of Medical Toxicology, 2024)

Construction of a tropical cyclone size dataset using reanalysis data - Derek T. Thompson; Barry D. Keim; Vincent M. Brown (International Journal of Climatology, 2024)
This paper details the creation of a tropical cyclone (TC) size dataset using the NCEP/NCAR Reanalysis I dataset for landfalling TCs along the United States coastline from 1948 to 2022. The radius of the outermost closed isobar (ROCI) is used as the size parameter. The dataset comprises landfall ROCI for 220 TCs. Storms are split into three zones (Texas–Alabama, Florida and Georgia–Maine) to determine if TC size varies geographically. Results showed a significant difference in landfall size, with Florida storms larger on average than the Texas–Alabama storms. Additionally, TC size increased with increasing intensity from tropical storm to Category 3, and storms tended to be larger later in the hurricane season, but there was no significant trend in landfall size over the 75‐year period. ROCI exhibited statistically significant positive correlations with longitude and wind speed and a negative correlation with the outermost closed isobar's pressure. The dataset's creation is an example of how reanalysis datasets can be used to develop a TC size climatology.

Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Effects of arginine vasopressin on human anxiety and associations with sex, dose, and V1a-receptor genotype - R. R. Thompson; D. Price; D. Burris; A. Cloutier; J. K. Rilling (Psychopharmacology, 2024)

Characterization of macadamia ringspot-associated virus, a novel Orthotospovirus associated with Macadamia integrifolia in South Africa - Ronel Roberts; Nicola Robbertse; Genevieve D. Thompson; David A. Read (European Journal of Plant Pathology, 2024)
South Africa is the largest producer of macadamias in the world, producing an estimated 61,288 tons nut-in-shell in 2022. In order to ensure the sustainability of the industry, it is important that research focuses on the control and eradication of economically important pests and diseases. Macadamia trees in the Mpumalanga Lowveld of South Africa have for some time shown severe chlorosis, which coincides with a significant drop in production, with losses of up to 60% being recorded. The disease has since been coined Macadamia Chlorosis Disease (MCD). In an attempt to determine whether MCD may be associated with a virus, high-throughput Illumina sequencing was performed on RNA extracted from both diseased and healthy trees collected from farms in Mpumalanga. Subsequent data analyses could not link a specific virus to MCD, however, reads spanning the full genome of a novel virus belonging to the Orthotospovirus genus were obtained. An RT-PCR assay was optimized for the detection of this virus and subsequent surveys linked the virus to ringspot symptoms which are commonly observed on different macadamia cultivars. The virus has to date been identified from orchards in Mpumalanga, Limpopo and KwaZulu-Natal. Other viruses described in the genus are known to cause severe crop losses and it is therefore important that the virus, provisionally named macadamia ringspot-associated virus (MRSV), be further studied to determine whether association with this virus can lead to yield losses, and whether appropriate control strategies must be implemented to prevent the spread of MRSV.

Climate‐related variation of metabolic rate across the distribution of a broadly tolerant invasive forest pest - Sean D. Powers; Lily M. Thompson; Dylan Parry; Kristine L. Grayson; Eloy Martinez; Salvatore J. Agosta (Journal of Biogeography, 2024)
Aim Metabolic rate is a widely studied physiological species trait related to energetics, climate, and geographical distributions. Hypotheses have been proposed to explain variation in metabolic rate, but evidence has been mixed due to the limited sampling scope of intraspecific studies. Successful biological invasions offer a unique opportunity to examine the development of intraspecific physiological variation and how it relates to climate, invasive spread and species range limits. The aim of this study was to determine if metabolic rate variation across the spongy moth invasive range was consistent with a pattern of adaptation to local climate. Location Northeastern United States of America. Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae). Methods Larvae were sourced from 14 populations across the invasion front and interior of the current L. d. dispar invasive range and were reared at a constant temperature. Routine metabolic rates (RMR) of larvae were assayed at three ecologically relevant temperatures. These data were analysed to determine if there were differences in RMR and temperature sensitivity of RMR among populations. Population‐level variation in RMR was then analysed as a function of local climate and geographical position to test for patterns consistent with local adaptation. Results Larval RMR showed significant variation among populations across all assay temperatures, but there was no difference in temperature sensitivity (i.e. slope). This variation followed a positive latitudinal cline with RMR increasing from the southern range to the north. This cline also showed a significant relationship with local climate variables. Main Conclusions Larval metabolic rate variation was consistent with a pattern of adaptation by L. d. dispar to divergent climates across its invasive range. These results indicated that thermal adaptation of whole‐organism physiology may play a key role in promoting species spread and expansion for biological invasions like L. d. dispar .

Grazing herbivores reduce herbaceous biomass and fire activity across African savannas - A. Tyler Karp; Sally E. Koerner; Gareth P. Hempson; Joel O. Abraham; T. Michael Anderson; William J. Bond; Deron E. Burkepile; Elizabeth N. Fillion; Jacob R. Goheen; Jennifer A. Guyton; Tyler R. Kartzinel; Duncan M. Kimuyu; et al. (Ecology Letters, 2024)
Fire and herbivory interact to alter ecosystems and carbon cycling. In savannas, herbivores can reduce fire activity by removing grass biomass, but the size of these effects and what regulates them remain uncertain. To examine grazing effects on fuels and fire regimes across African savannas, we combined data from herbivore exclosure experiments with remotely sensed data on fire activity and herbivore density. We show that, broadly across African savannas, grazing herbivores substantially reduce both herbaceous biomass and fire activity. The size of these effects was strongly associated with grazing herbivore densities, and surprisingly, was mostly consistent across different environments. A one‐zebra increase in herbivore biomass density (~100 kg/km 2 of metabolic biomass) resulted in a ~53 kg/ha reduction in standing herbaceous biomass and a ~0.43 percentage point reduction in burned area. Our results indicate that fire models can be improved by incorporating grazing effects on grass biomass.

Ocean surface radiation measurement best practices - Laura D. Riihimaki; Meghan F. Cronin; Raja Acharya; Nathan Anderson; John A. Augustine; Kelly A. Balmes; Patrick Berk; Roberto Bozzano; Anthony Bucholtz; Kenneth J. Connell; Christopher J. Cox; Alcide G. di Sarra; et al. (Frontiers in Marine Science, 2024)
Ocean surface radiation measurement best practices have been developed as a first step to support the interoperability of radiation measurements across multiple ocean platforms and between land and ocean networks. This document describes the consensus by a working group of radiation measurement experts from land, ocean, and aircraft communities. The scope was limited to broadband shortwave (solar) and longwave (terrestrial infrared) surface irradiance measurements for quantification of the surface radiation budget. Best practices for spectral measurements for biological purposes like photosynthetically active radiation and ocean color are only mentioned briefly to motivate future interactions between the physical surface flux and biological radiation measurement communities. Topics discussed in these best practices include instrument selection, handling of sensors and installation, data quality monitoring, data processing, and calibration. It is recognized that platform and resource limitations may prohibit incorporating all best practices into all measurements and that spatial coverage is also an important motivator for expanding current networks. Thus, one of the key recommendations is to perform interoperability experiments that can help quantify the uncertainty of different practices and lay the groundwork for a multi-tiered global network with a mix of high-accuracy reference stations and lower-cost platforms and practices that can fill in spatial gaps.

Immersion of nanostructured lipid carriers loaded with 17-alpha methyltestosterone for masculinization of red tilapia (Oreochromis sp.) - Jakarwan Yostawonkul; Sirikorn Kitiyodom; Manoj Tukaram Kamble; Kittipat Supchukun; Nattika Saengkrit; Pimwarang Sukkarun; Seema Vijay Medhe; Kim D. Thompson; Suwimon Boonrungsiman; Sasithon Temisak; Roland A. Fleck; Teerapong Yata; et al. (Aquaculture, 2024)

Pharmacokinetic models for first-in-human dose selection of immune-activating products in oncology - Haleh Saber; Matthew D. Thompson; John K. Leighton (Regulatory Toxicology and Pharmacology, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Deep learning of estuary salinity dynamics is physically accurate at a fraction of hydrodynamic model computational cost - Galen Gorski; Salme Cook; Amelia Snyder; Alison P. Appling; Theodore Thompson; Jared D. Smith; John C. Warner; Simon N. Topp (Limnology and Oceanography, 2024)
Salinity dynamics in the Delaware Bay estuary are a critical water quality concern as elevated salinity can damage infrastructure and threaten drinking water supplies. Current state‐of‐the‐art modeling approaches use hydrodynamic models, which can produce accurate results but are limited by significant computational costs. We developed a machine learning (ML) model to predict the 250 mg L −1 Cl − isochlor, also known as the “salt front,” using daily river discharge, meteorological drivers, and tidal water level data. We use the ML model to predict the location of the salt front, measured in river miles (RM) along the Delaware River, during the period 2001–2020, and we compare predictions of the ML model to the hydrodynamic Coupled Ocean–Atmosphere‐Wave‐Sediment Transport (COAWST) model. The ML model predicts the location of the salt front with greater accuracy (root mean squared error [RMSE] = 2.52 RM) than the COAWST model does (RMSE = 5.36); however, the ML model struggles to predict extreme events. Furthermore, we use functional performance and expected gradients, tools from information theory and explainable artificial intelligence, to show that the ML model learns physically realistic relationships between the salt front location and drivers (particularly discharge and tidal water level). These results demonstrate how an ML modeling approach can provide predictive and functional accuracy at a significantly reduced computational cost compared to process‐based models. In addition, these results provide support for using ML models in operational forecasting, scenario testing, management decisions, hindcasting, and resulting opportunities to understand past behavior and develop hypotheses.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

The influence of micro-scale thermal habitat on the movements of juvenile white sharks in their Southern California aggregation sites - Emily Spurgeon; Marten L. Thompson; Mitchell D. Alexander; James M. Anderson; Patrick T. Rex; Brian Stirling; Kevin Abbott; Christopher G. Lowe (Frontiers in Marine Science, 2024)
While juvenile white sharks (JWS) can display regional endothermy, the need to maintain internal temperatures within an energetically favorable range likely drives thermoregulatory movements to maximize growth and foraging efficiency. Many JWS from the northeastern Pacific population aggregate seasonally in nearshore nursery habitats throughout the Southern California Bight and historic data show that inter-seasonal movement patterns may be heavily dependent on ambient water temperature. However, the degree to which micro-scale (e.g., ~10 m 2 ) water temperature heterogeneity influences JWS three-dimensional movement within nearshore aggregation sites is unknown. High-resolution temperature and passive acoustic-telemetry geo-positional data were used to quantify how temperature and vertical thermal stratification influenced JWS movement using several modeling approaches. JWS selected for water temperatures between 16 – 22°C and depths shallower than 2 m. Sharks occupied deeper waters during dawn and dusk periods, and their distance from the seafloor and spatial orientation of their depth distribution was significantly related to the thermal structure of the water column across the monitored area. Tagged sharks remained above a 16°C thermal threshold and altered their horizontal and vertical distributions accordingly. While high-resolution movement and environmental data provide improved predictability of micro-scale habitat use and distribution, other variables such as prey distribution, behavior, and competition would further improve habitat use models for this highly mobile species.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Understanding vessel noise across a network of marine protected areas - Megan F McKenna; Timothy J Rowell; Tetyana Margolina; Simone Baumann-Pickering; Alba Solsona-Berga; Jeffrey D Adams; John Joseph; Ella B Kim; Annebelle CM Kok; Anke Kügler; Marc O Lammers; Karlina Merkens; et al. (Environmental Monitoring and Assessment, 2024)
Protected areas are typically managed as a network of sites exposed to varying anthropogenic conditions. Managing these networks benefits from monitoring of conditions across sites to help prioritize coordinated efforts. Monitoring marine vessel activity and related underwater radiated noise impacts across a network of protected areas, like the U.S. National Marine Sanctuary system, helps managers ensure the quality of habitats used by a wide range of marine species. Here, we use underwater acoustic detections of vessels to quantify different characteristics of vessel noise at 25 locations within eight marine sanctuaries including the Hawaiian Archipelago and the U.S. east and west coasts. Vessel noise metrics, including temporal presence and sound levels, were paired with Automatic Identification System (AIS) vessel tracking data to derive a suite of robust vessel noise indicators for use across the network of marine protected areas. Network-wide comparisons revealed a spectrum of vessel noise conditions that closely matched AIS vessel traffic composition. Shifts in vessel noise were correlated with the decrease in vessel activity early in the COVID-19 pandemic, and vessel speed reduction management initiatives. Improving our understanding of vessel noise conditions in these protected areas can help direct opportunities for reducing vessel noise, such as establishing and maintaining noise-free periods, enhancing port efficiency, engaging with regional and international vessel quieting initiatives, and leveraging co-benefits of management actions for reducing ocean noise.

Life goes on: Spatial heterogeneity promotes biodiversity in an urbanized coastal marine ecosystem - Shelby E. McIlroy; Isis Guibert; Anand Archana; Wing Yi Haze Chung; J. Emmett Duffy; Rinaldi Gotama; Jerome Hui; Nancy Knowlton; Matthieu Leray; Chris Meyer; Gianni Panagiotou; Gustav Paulay; et al. (Global Change Biology, 2024)
Both human populations and marine biodiversity are concentrated along coastlines, with growing conservation interest in how these ecosystems can survive intense anthropogenic impacts. Tropical urban centres provide valuable research opportunities because these megacities are often adjacent to mega‐diverse coral reef systems. The Pearl River Delta is a prime exemplar, as it encompasses one of the most densely populated and impacted regions in the world and is located just northwest of the Coral Triangle. However, the spatial and taxonomic complexity of this biodiversity, most of which is small, cryptic in habitat and poorly known, make comparative analyses challenging. We deployed standardized settlement structures at seven sites differing in the intensity of human impacts and used COI metabarcoding to characterize benthic biodiversity, with a focus on metazoans. We found a total of 7184 OTUs, with an average of 665 OTUs per sampling unit; these numbers exceed those observed in many previous studies using comparable methods, despite the location of our study in an urbanized environment. Beta diversity was also high, with 52% of the OTUs found at just one site. As expected, we found that the sites close to point sources of pollution had substantially lower diversity (44% less) relative to sites bathed in less polluted oceanic waters. However, the polluted sites contributed substantially to the total animal diversity of the region, with 25% of all OTUs occurring only within polluted sites. Further analysis of Arthropoda, Annelida and Mollusca showed that phylogenetic clustering within a site was common, suggesting that environmental filtering reduced biodiversity to a subset of lineages present within the region, a pattern that was most pronounced in polluted sites and for the Arthropoda. The water quality gradients surrounding the PRD highlight the unique role of in situ studies for understanding the impacts of complex urbanization pressures on biodiversity.

Features of the highway road network that generate or retain tyre wear particles - Florence N. F. Parker-Jurd; Geoffrey D. Abbott; Bill Guthery; Gustav M. C. Parker-Jurd; Richard C. Thompson (Environmental Science and Pollution Research, 2024)

Systemic and mucosal immune responses in red tilapia (Oreochromis sp.) following immersion vaccination with a chitosan polymer-based nanovaccine against Aeromonas veronii - Pimwarang Sukkarun; Sirikorn Kitiyodom; Manoj Tukaram Kamble; Anurak Bunnoy; Surintorn Boonanuntanasarn; Teerapong Yata; Suwimon Boonrungsiman; Kim D. Thompson; Channarong Rodkhum; Nopadon Pirarat (Fish & Shellfish Immunology, 2024)

Variability of corticospinal and spinal reflex excitability for the ankle dorsiflexor tibialis anterior across repeated measurements in people with and without incomplete spinal cord injury - J. A. Brangaccio; A. M. Phipps; D. E. Gemoets; J. M. Sniffen; Aiko K. Thompson (Experimental Brain Research, 2024)
To adequately evaluate the corticospinal and spinal plasticity in health and disease, it is essential to understand whether and to what extent the corticospinal and spinal responses fluctuate systematically across multiple measurements. Thus, in this study, we examined the session-to-session variability of corticospinal excitability for the ankle dorsiflexor tibialis anterior (TA) in people with and without incomplete spinal cord injury (SCI). In neurologically normal participants, the following measures were obtained across 4 days at the same time of day ( N = 13) or 4 sessions over a 12-h period ( N = 9, at 8:00, 12:00, 16:00, and 20:00): maximum voluntary contraction (MVC), maximum M-wave and H-reflex ( M max and H max ), motor evoked potential (MEP) amplitude, and silent period (SP) after MEP. In participants with chronic incomplete SCI ( N = 17), the same measures were obtained across 4 days. We found no clear diurnal variation in the spinal and corticospinal excitability of the TA in individuals with no known neurological conditions, and no systematic changes in any experimental measures of spinal and corticospinal excitability across four measurement days in individuals with or without SCI. Overall, mean deviations across four sessions remained in a range of 5–13% for all measures in participants with or without SCI. The study shows the limited extent of non-systematic session-to-session variability in the TA corticospinal excitability in individuals with and without chronic incomplete SCI, supporting the utility of corticospinal and spinal excitability measures in mechanistic investigation of neuromodulation interventions. The information provided through this study may serve as the reference in evaluating corticospinal plasticity across multiple experimental sessions.

River drainage rearrangements and the phylogeographic pattern of the annual fish Austrolebias arachan (Cyprinodontiformes, Rivulidae) - Marcelo Loureiro; Sofía Stareczek; Alejandro D'anatro; Andrew W. Thompson; Guillermo Ortí (Zoologica Scripta, 2024)
Palaeogeographical and climatic processes are among the main factors affecting biological diversity and distribution patterns. In freshwater systems, major dispersal processes are caused by river drainage rearrangements where the direction of flow of a stream changes, allowing range expansions and connection of previously isolated communities. In the Neotropical region, this process has been known to connect part of the southwestern Amazon basin with La Plata basin during the formation of the Bolivian Orocline, and La Plata basin with Atlantic coastal basins since the split from Africa. Several species of annual fishes of the genus Austrolebias are known to inhabit seasonal ponds both in the Rio Negro basin (southern tip of Brazilian shield, Lower Uruguay ecoregion), and the headwaters of rivers draining into the Merín lagoon (coastal drainages, Laguna dos Patos ecoregion). The aim of this article was to analyse the phylogeographic pattern of Austrolebias arachan in the context of putative river rearrangements. Two hypotheses were tested: (a) the spatial configuration of river basins determines the genetic structure and distribution of this species, and (b) coastal drainages captured sections of upland shield river drainages. We analysed a fragment of the mitochondrial cytochrome b gene and a fragment of a nuclear intron locus. Results support the prediction of the first hypothesis: geographic variation within A. arachan is structured according to geography. The second hypothesis was in part confirmed: the migration analyses showed that Rio Negro basin populations could have acted as a source for Laguna Merin basin. However, migration estimates also support gene flow in the opposite direction. The cytochrome b haplotype network configuration and its phylogenetic pattern suggests at least two independent events of capture, with divergence time estimated at the onset of Pleistocene glacial cycles.

Momma's larvae: Maternal oceanographic experience and larval size influence early survival of rockfishes - H. William Fennie; Noah Ben‐Aderet; Steven J. Bograd; Garfield T. Kwan; Jarrod A. Santora; Isaac D. Schroeder; Andrew R. Thompson (Fisheries Oceanography, 2024)
Identifying factors that affect larval mortality is critical for understanding the drivers of fish population dynamics. Although larval fish mortality is high, small changes in mortality rates can lead to large changes in recruitment. Recent studies suggest maternal provisioning can dramatically affect the susceptibility of larvae to starvation and predation, the major sources of early‐life mortality. We measured otolith core width‐at‐extrusion and validated that this is a proxy for larval size‐at‐extrusion for eight species of rockfishes (genus Sebastes ) to examine the influence of initial larval size on larval growth and survival and to understand how oceanographic conditions experienced by gestating females affect larval size (i.e., quality). Otolith core width‐at‐extrusion was significantly positively related to larval rockfish recent growth rate (5/7 species with sufficient sample size) and survival (all eight species). This suggests that individuals that are larger at extrusion generally grow faster and are more likely to survive early life stages. Otolith core width‐at‐extrusion was positively related to higher presence of Pacific Subarctic Upper Water and was negatively related to warmer, saline waters at the depths gestating mothers inhabited during the months prior to larval collection. In addition, otolith core width was larger further from fishing ports, possibly because these locations were historically less fished, contained more older, larger females, and/or had inherently better habitat quality (higher Pacific Subarctic Upper Water) than sites closer to shore. These results indicate that the environmental conditions female rockfish experience during gestation drive the size of the larvae they produce and impact larval growth and survival.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Ice core evidence for an orbital-scale climate transition on the Northwest Tibetan Plateau - L.G. Thompson; T.-D. Yao; M.E. Davis; E. Mosley-Thompson; H.-A. Synal; G. Wu; J.F. Bolzan; S. Kutuzov; E. Beaudon; M.R. Sierra-Hernández; J. Beer (Quaternary Science Reviews, 2024)

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

Intruding into a conversation: how behavioral manipulation could support management of Xylella fastidiosa and its insect vectors - Sabina Avosani; Rachele Nieri; Valerio Mazzoni; Gianfranco Anfora; Zeinab Hamouche; Caterina Zippari; Maria Luisa Vitale; Vincenzo Verrastro; Eustachio Tarasco; Ilaria D’Isita; Salvatore Germinara; Thomas F. Döring; et al. (Journal of Pest Science, 2024)
Behavioral manipulation (BM) is a multimodal control approach based on the interference with the stimuli mediating insect perception and interaction with the surroundings. BM could represent a win–win strategy for the management of vector-borne plant pathogens as the bacterium Xylella fastidiosa , since it could reduce the number of vectors alighting on host plants and, consequently, the chances for transmission to occur. In this review, we summarized current knowledge and highlighted gaps in information on (i) how insect vectors of X. fastidiosa in general, and more specifically the meadow spittlebug Philaenus spumarius , locate and accept the host plant ; and (ii) how behavioral manipulation techniques could be applied to disrupt the vector–host plant interaction. Finally, we discussed how diverse BM strategies could be combined with other integrated pest management tools to protect olive groves from inoculation with the fastidious bacterium.

Comparison of the Benthic Prey Community and Diet of Adult Mummichogs (Fundulus heteroclitus) Along a Tidal Creek Gradient - Jessica S. Thompson; Heather D. Harwell (Estuaries and Coasts, 2024)

Comparison of threatened Neosho madtom (Noturus placidus) densities between riverscapes differing in anthropogenic stressors, with a particular focus on recovery from mining-derived metal pollution - Kali L. Boroughs; James E. Whitney; Alexandra D. King; Joshua A. Holloway; Aliyah N. Clemens; Austin D. Thompson (Environmental Biology of Fishes, 2024)

A critical re‐analysis of constraints on the timing and rate of Laurentide Ice Sheet recession in the northeastern United States - Christopher T. Halsted; Paul R. Bierman; Jeremy D. Shakun; P. Thompson Davis; Lee B. Corbett; Jason S. Drebber; John C. Ridge (Journal of Quaternary Science, 2024)
We review geochronological data relating to the timing and rate of Laurentide Ice Sheet recession in the northeastern United States and model ice margin movements in a Bayesian framework using compilations of previously published organic 14 C ( n = 133) and in situ cosmogenic 10 Be ( n = 95) ages. We compare the resulting method‐specific chronologies with glacial varve records that serve as independent constraints on the pace of ice recession to: (1) construct a synthesis of deglacial chronology throughout the region; and (2) assess the accuracy of each chronometer for constraining the timing of deglaciation. Near the Last Glacial Maximum terminal moraine zone, 10 Be and organic 14 C ages disagree by thousands of years and limit determination of the initial recession to a date range of 24–20 ka. We infer that 10 Be inherited from pre‐glacial exposure adds 2–6 kyr to many exposure ages near the terminal moraines, whereas macrofossil 14 C ages are typically 4–8 kyr too young due to a substantial lag between ice recession and sufficient organic material accumulation for dating in some basins. Age discrepancies between these chronometers decrease with distance from the terminal moraine, due to less 10 Be inherited from prior exposure and a reduced lag between ice recession and organic material deposition. 14 C and 10 Be ages generally agree at locations more than 200 km distal from the terminal moraines and suggest a mostly continuous history of ice recession throughout the region from 18 to 13 ka with a variable pace best documented by varves.

Molecular transformations and self-association in anthocyanin pigment patterns - Wei-Yu Hsu; Patrick D. Shipman; Stephen Thompson (Journal of Biosciences, 2023)

Catalyzing progress in the blue economy through joint marine microbiome research across the Atlantic - Alice C. Ortmann; Kelly D. Goodwin; Henk Bolhuis; René Groben; Thulani Makhalanyane; Jeff Bowman; Shawn Robinson; Fabiano Thompson (Frontiers in Marine Science, 2023)
International agreements recognize the importance of cooperative scientific research to conserve and promote sustainable development of a shared Atlantic Ocean. In 2022, the All-Atlantic Ocean Research and Innovation Alliance Declaration was signed. The All-Atlantic Declaration continues and extends relationships forged by the Galway Statement on Atlantic Ocean Cooperation and the Belém Statement on Atlantic Ocean Research and Innovation Cooperation. These efforts are consistent with programs, actions, and aims of the United Nations Decade of Ocean Science for Sustainable Development. In preparation for implementation of the All-Atlantic Declaration, members of the Marine Microbiome Working Group and the Marine Biotechnology Initiative for the Atlantic under the Galway and Belém Statements respectively, joined forces to call for cooperation across the Atlantic to increase marine microbiome and biotechnology research to promote ocean health and a sustainable bioeconomy. This article reviews the goals of the marine microbiome and biotechnology initiatives under the Galway and Belém Statements and outlines an approach to implement those goals under the All-Atlantic Declaration through a Blue Biotech and Marine Microbiome (BBAMM) collaboration.

Harnessing water fleas for water reclamation: A nature-based tertiary wastewater treatment technology - Muhammad Abdullahi; Iestyn Stead; Sophie Bennett; Rafael Orozco; Mohamed Abou-Elwafa Abdallah; Sara Jabbari; Lynne E. Macaskie; Alexandra Tzella; Stefan Krause; Bushra Al-Duri; Robert G. Lee; Ben Herbert; et al. (Science of The Total Environment, 2023)

Differential responses to habitat structure and degradation by two Grassbirds (Fam. Locustellidae) syntopic in floodplain grassland - Israt Jahan; Philip D. Round; Paul M. Thompson; Tommaso Savini; George A. Gale (Wetlands Ecology and Management, 2023)

Treatment of Fusarium Infection of the Central Nervous System: A Review of Past Cases to Guide Therapy for the Ongoing 2023 Outbreak in the United States and Mexico - Martin Hoenigl; Jeffrey D. Jenks; Matthias Egger; Marcio Nucci; George R. Thompson (Mycopathologia, 2023)
Introduction Fusariosis of the central nervous system (CNS) is extremely uncommon. Treatment and outcome data from previously published cases may provide some guidance in light of the ongoing fungal meningitis outbreak in 2023 involving Fusarium spp. in the United States and Mexico. Methods We reviewed the published literature describing cases of invasive fusariosis of the (CNS) that included data on patient demographic characteristics, treatment, and outcome. Results Twenty-six cases met inclusion criteria. The mean age was 36 years, 55% involved females, 60% had underlying hematologic malignancy, and another 16% were on immunosuppressants. The majority of infections were from Fusarium solani species complex. Overall 72% of patients died. The majority received monotherapy with amphotericin B, although some received voriconazole monotherapy or combination therapy with amphotericin B plus voriconazole with or without adjuvant surgery. Among the survivors, 3 received amphotericin B monotherapy, 2 voriconazole monotherapy, 1 combination therapy of both, and one surgery only. Conclusion The overall mortality rate in published cases of fusariosis of the CNS was high, although—unlike during the current outbreak—the preponderance of patients were severely immunocompromised. While historically the majority were treated with amphotericin B monotherapy, some recent patients were treated with voriconazole monotherapy or combination therapy with amphotericin B plus voriconazole. Current guidelines recommend monotherapy with voriconazole or lipid formulations of amphotericin B or combination of both for the treatment of invasive fusariosis, which is in line with the findings from our literature review and should be considered during the ongoing 2023 outbreak.

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Correction: Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)

Genetic insights into pepper-bark tree (Warburgia salutaris) reproduction in South Africa - K. L. Glennon; J. J. Le Roux; D. I. Thompson (Conservation Genetics, 2023)
Genetic diversity in over-exploited and threatened species has important, but often neglected, implications for conservation. In South Africa, the bark of the regionally endangered pepper-bark tree, Warburgia salutaris , is extensively harvested for subsistence medicine. We developed 11 polymorphic microsatellite markers to examine the genetic diversity and structure among 227 W. salutaris individuals sampled from across much of its range in South Africa’s Kruger National Park (KNP) and 31 trees growing in local nurseries. We also tested the cross-amplification success of these markers in two closely related species, Warburgia elongata (IUCN listed as Endangered) and W. stuhlmannii (IUCN listed as Vulnerable). Contrary to our expectations, we found evidence of clonality and for high genetic diversity in all wild KNP sub-populations of W. salutaris . We identified between 114 and 149 unique multi-locus genotypes in the 258 individuals included in our analyses. Bayesian assignment tests identified three distinct genetic clusters that are represented by the sampled KNP sub-population of W. salutaris , with minimal geographic structure and some admixture. Three genetic clusters were also identified among all sampled individuals, i.e., KNP and nursery trees. Nursery W. salutaris germplasm comprised unique genotypes with similar levels of observed heterozygosity to the wild population. High levels of clonality and reported self-incompatibility, along with short distance pollination, likely explain the lack of recent sexual recruitment (i.e., reduced fruit set and lack of seedlings) in the wild population. These findings will be useful to identify sub-populations where genets may be sampled to maximize genetic diversity within subpopulations for restoration throughout KNP.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

The Structural Response of the Human Head to a Vertex Impact - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Andrew M. Dwyer; Nigel R. Jones; Claire F. Jones (Annals of Biomedical Engineering, 2023)
In experimental models of cervical spine trauma caused by near-vertex head-first impact, a surrogate headform may be substituted for the cadaveric head. To inform headform design and to verify that such substitution is valid, the force-deformation response of the human head with boundary conditions relevant to cervical spine head-first impact models is required. There are currently no biomechanics data that characterize the force-deformation response of the isolated head supported at the occiput and compressed at the vertex by a flat impactor. The effect of impact velocity (1, 2 or 3 m/s) on the response of human heads ( N = 22) subjected to vertex impacts, while supported by a rigid occipital mount, was investigated. 1 and 2 m/s impacts elicited force-deformation responses with two linear regions, while 3 m/s impacts resulted in a single linear region and skull base ring fractures. Peak force and stiffness increased from 1 to 2 and 3 m/s. Deformation at peak force and absorbed energy increased from 1 to 2 m/s, but decreased from 2 to 3 m/s. The data reported herein enhances the limited knowledge on the human head’s response to a vertex impact, which may allow for validation of surrogate head models in this loading scenario.

A taxonomy-free diatom eDNA-based technique for assessing lake trophic level using lake sediments - Rose Gregersen; John K. Pearman; Javier Atalah; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Georgia Thomson-Laing; Lucy Thompson; Susanna A. Wood (Journal of Environmental Management, 2023)

CD4+ T lymphocyte responses to viruses and virus-relevant stimuli in teleost fish - Dennis Berbulla Bela-ong; Kim D. Thompson; Hyoung Jun Kim; Seong Bin Park; Tae Sung Jung (Fish & Shellfish Immunology, 2023)

Insight into characteristics and pathogenicity of five rapidly growing non-tuberculous Mycobacterium species isolated from the Siamese fighting fish, Betta splendens - Nguyen Dinh-Hung; Ha Thanh Dong; Saengchan Senapin; Khaettareeya Pimsannil; Kim D. Thompson; Andrew P. Shinn; Chayanit Soontara; Wanna Sirimanapong; Satid Chatchaiphan; Channarong Rodkhum (Aquaculture, 2023)

Devaluation Effects in Food-Specific Response Inhibition Training: A Conceptual Replication - L. Tzavella; C.R. Pennington; K.S. Button; F. Abdullahi; E. Aboaba; Z. Abutayeh; N. Bushell; A. Caddle; S. Chi Chan; A. Denman; C. Gabe-Jones; M. Mushongah; et al. (Appetite, 2023)

Parent-reported Fruit and Vegetable Home Availability and Accessibility in an Online Obesity Prevention Program for Pre-adolescent Black Girls - C. Callender; S. Musaad; D. Thompson (Journal of the Academy of Nutrition and Dietetics, 2023)

Sub-tropical benthic/epiphytic dinoflagellates of Aotearoa New Zealand and Rangitāhua Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; J. Sam Murray; Emillie M F Passfield; Roberta D'Archino; Wendy Nelson; Tomohiro Nishimura; Lucy Thompson; Tom Trnski (Harmful Algae, 2023)

Development of a 5-HT7 receptor antibody for the rat: the good, the bad, and the ugly - Janice M. Thompson; Will Tragge; Emma D. Flood; Stefan Schulz; Erika Lisabeth; Stephanie W. Watts (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Our laboratory has a vested interest in measuring the location and expression of the 5-hydroxytryptamine (5-HT, serotonin) 7 (5-HT 7 ) receptor in the rat. Determining tissue-specific receptor expression would aid in validating understood and potentially new tissues that support the 5-HT 7 receptor-mediated fall in blood pressure, an event we are committed to understand. We contracted with 7TM Antibodies to develop deliberately and rigorously a rat 5-HT 7 (r5-HT 7 ) receptor specific antibody. Three antigens, two targeting the third internal loop and one the C terminus, were used in three rabbits to generate antibodies. As a positive control, HEK293(T or AD) cells were transfected with a plasmid for the r5-HT 7 receptor also expressing a C terminus 3xFLAG tag. Naïve rat tissues were also used in Western and immunohistochemical analyses. Nine antibodies (3 from three different rabbits) detected a ~ 75 kDa protein absent in homogenates of vector control HEK293T cells. Only antibodies that recognized the C terminus of the 5-HT 7 receptor [ERPERSEFVLQNSDH(Abu)GKKGHDT; antibodies 3, 6, and 9] positively and concentration-dependently identified the r5-HT 7 receptor expressed in Westerns of transfected HEK293T cells. These same C terminus antibodies also successfully detected the r5-HT 7 receptor in immunocytochemical test of the transfected HEK293AD cells, colocalizing with the detected FLAG sequence. In naive tissue, antibody 6 performed the best, identifying specific bands in the brain cortex in Western analysis. These same antibodies produced a more diverse band profile in the vena cava, identifying 6 major proteins. In immunohistochemical experiments, the same C-terminus antibodies, with antibody 3 performing the best, detected the 5-HT 7 receptor in rat veins. This deliberate work has given rise to at least three antibodies that can be used with good confidence in r5-HT 7 transfected cells, two antibodies that can be used in immunohistochemical analyses of rat tissues and in Westerns of rat brain; we are less confident of the use of these same antibodies in rat veins.

Kinetic Modeling and Parameter Estimation of a Prebiotic Peptide Reaction Network - Hayley Boigenzahn; Leonardo D. González; Jaron C. Thompson; Victor M. Zavala; John Yin (Journal of Molecular Evolution, 2023)

Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)
Objective Multicomponent interventions are recommendable to achieve the greatest mental health benefits, but are difficult to evaluate due to their complexity. Defining long-term outcomes, arising from a Theory of Change (ToC) and testing them in a pilot phase, is a useful approach to plan a comprehensive and meaningful evaluation later on. This article reports on the pilot results of an outcome evaluation of a complex mental health intervention and examines whether appropriate evaluation measures and indicators have been selected ahead of a clustered randomised control trial (cRCT). Methods The MENTUPP pilot is an evidence-based intervention for Small and Medium Enterprises (SMEs) active in three work sectors and nine countries. Based on our ToC, we selected the MENTUPP long-term outcomes, which are reported in this article, are measured with seven validated scales assessing mental wellbeing, burnout, depression, anxiety, stigma towards depression and anxiety, absenteeism and presenteeism. The pilot MENTUPP intervention assessment took place at baseline and at 6 months follow-up. Results In total, 25 SMEs were recruited in the MENTUPP pilot and 346 participants completed the validated scales at baseline and 96 at follow-up. Three long-term outcomes significantly improved at follow-up ( p < 0.05): mental wellbeing, symptoms of anxiety, and personal stigmatising attitudes towards depression and anxiety. Conclusions The results of this outcome evaluation suggest that MENTUPP has the potential to strengthen employees’ wellbeing and decrease anxiety symptoms and stigmatising attitudes. Additionally, this study demonstrates the utility of conducting pilot workplace interventions to assess whether appropriate measures and indicators have been selected. Based on the results, the intervention and the evaluation strategy have been optimised.

Variation in hysterectomy prevalence and trends among U.S. States and Territories—Behavioral Risk Factor Surveillance System, 2012–2020 - Sameer V. Gopalani; Sabitha R. Dasari; Emily E. Adam; Trevor D. Thompson; Mary C. White; Mona Saraiya (Cancer Causes & Control, 2023)

Prenatal and postnatal exposure to polychlorinated biphenyls alter follicle numbers, gene expression, and a proliferation marker in the rat ovary - Kathy M. De La Torre; Yuna Lee; Adira Safar; Mary J. Laws; Daryl D. Meling; Lindsay M. Thompson; Madeline Streifer; Karen E. Weis; Lori T. Raetzman; Andrea C. Gore; Jodi A. Flaws (Reproductive Toxicology, 2023)

Horse fly and deer fly (Diptera: Tabanidae) species and abundance following logging in northwestern Ontario - Janette Buckley; James A. Schaefer; John L. Ringrose; Marco Raponi; Ian D. Thompson; Philip A. Wiebe; Art R. Rodgers; John M. Fryxell; David V. Beresford (Forest Ecology and Management, 2023)

Thermal hydraulic and mechanical modelling of the full-scale in situ test (FISST) - V. Tsitsopoulos; D. Holton; P. Appleyard; S. Thompson; S. Baxter; M. Niskanen (Engineering Geology, 2023)

Transitions in modes of coastal adaptation: addressing blight, engagement and sustainability - Sally Brown; Emma L. Tompkins; Natalie Suckall; Jon French; Ivan D. Haigh; Eli Lazarus; Robert J. Nicholls; Edmund C. Penning-Rowsell; Charlie E. L. Thompson; Ian Townend; Sien van der Plank (Frontiers in Marine Science, 2023)
Coastal defences have long provided protection from erosion and flooding to cities, towns and villages. In many parts of the world, continued defence is being questioned due to both environmental, sustainability and economic considerations. This is exemplified in England and Wales, where strategic Shoreline Management Plans envisage realignment of many protected coasts, often with low population densities, over the coming decades. The policy transition from protection to realignment is often resisted by affected communities and can have high political costs. Whilst some preparations for such transitions have been made, the communities affected are often not fully aware of the implications of policy change, and this brings the potential for blight. In this paper, we investigate the challenges of implementing transitions in coastal policy within England and Wales. The analysis is based on data obtained from three workshops held in 2019 that were attended by council members, engineers, planners, scientists and other relevant professionals. Five conditions are found to promote contention: (i) policy actors with competing priorities and different decision making time frames (immediate to decadal to a century); (ii) divergence between regulations and ad hoc political decisions (e.g. in relation to the demand for new housing); (iii) limited or non-existent funding to support policy transition; (iv) community expectation that protection is forever; and (v) a disconnection between people and ongoing coastal change. Our research indicates that transitions can be better supported through: (1) integrated multi-scalar preparedness for coastal change; (2) an accessible evidence base and future vision to nurture political confidence in adaptation; and (3) defined, time-bound and accessible diverse funding streams to achieve transitions. Critically, these generic actions need to be embedded within the local political and planning system to facilitate transition to more sustainable coasts and their communities.

Compositional shifts of alpine plant communities across the high Andes - F. Cuesta; J. Carilla; L. D. LLambí; P. Muriel; M. V. Lencinas; R. I. Meneses; K. J. Feeley; H. Pauli; N. Aguirre; S. Beck; A. Bernardi; S. Cuello; et al. (Global Ecology and Biogeography, 2023)
Aim Climate change is transforming mountain summit plant communities worldwide, but we know little about such changes in the High Andes. Understanding large‐scale patterns of vegetation changes across the Andes, and the factors driving these changes, is fundamental to predicting the effects of global warming. We assessed trends in vegetation cover, species richness (SR) and community‐level thermal niches (CTN) and tested whether they are explained by summits' climatic conditions and soil temperature trends. Location High Andes. Time period Between 2011/2012 and 2017/2019. Major taxa studied Vascular plants. Methods Using permanent vegetation plots placed on 45 mountain summits and soil temperature loggers situated along a ~6800 km N‐S gradient, we measured species and their relative percentage cover and estimated CTN in two surveys (intervals between 5 and 8 years). We then estimated the annual rate of changes for the three variables and used generalized linear models to assess their relationship with annual precipitation, the minimum air temperatures of each summit and rates of change in the locally recorded soil temperatures. Results Over time, there was an average loss of vegetation cover (mean = −0.26%/yr), and a gain in SR across summits (mean = 0.38 species m 2 /yr), but most summits had significant increases in SR and vegetation cover. Changes in SR were positively related to minimum air temperature and soil temperature rate of change. Most plant communities experienced shifts in their composition by including greater abundances of species with broader thermal niches and higher optima. However, the measured changes in soil temperature did not explain the observed changes in CTN. Main conclusions High Andean vegetation is changing in cover and SR and is shifting towards species with wider thermal niche breadths. The weak relationship with soil temperature trends could have resulted from the short study period that only marginally captures changes in vegetation through time.

Tilapia lake virus disease: Vaccine strategies to control the threat to tilapia aquaculture - Sreeja Lakshmi; David Smith; Ha Thanh Dong; Kim D. Thompson; Preetham Elumalai (Reviews in Aquaculture, 2023)
Since the first report of a novel disease caused by tilapia lake virus (TiLV) in 2014, the disease (TiLVD) has gained considerable attention as one of the most devastating viral diseases in tilapia aquaculture globally. The virus is both highly virulent and transmissible and has been detected in many countries worldwide. It poses a severe threat to the global tilapia aquaculture industry, food security and many people's livelihoods in low and middle‐income countries. The absence of effective treatment strategies and inadequate biosecurity measures means the virus's rapid spread is likely to continue. Vaccination has proven to be an effective approach to preventing and controlling disease in finfish aquaculture. The vaccine's efficacy and the delivery system's suitability are essential for evoking an appropriate immune response against the pathogen. The purpose of this review is to provide an overview of the strategies being used to develop vaccines for TiLVD. Nanovaccines, which offer a new approach to prevent TiLVD in farmed tilapia, are also discussed.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Sex-specific preservation of neuromuscular function and metabolism following systemic transplantation of multipotent adult stem cells in a murine model of progeria - Seth D. Thompson; Kelsey L. Barrett; Chelsea L. Rugel; Robin Redmond; Alexia Rudofski; Jacob Kurian; Jodi L. Curtin; Sudarshan Dayanidhi; Mitra Lavasani (GeroScience, 2023)
Onset and rates of sarcopenia, a disease characterized by a loss of muscle mass and function with age, vary greatly between sexes. Currently, no clinical interventions successfully arrest age-related muscle impairments since the decline is frequently multifactorial. Previously, we found that systemic transplantation of our unique adult multipotent muscle-derived stem/progenitor cells (MDSPCs) isolated from young mice—but not old—extends the health-span in DNA damage mouse models of progeria, a disease of accelerated aging. Additionally, induced neovascularization in the muscles and brain—where no transplanted cells were detected—strongly suggests a systemic therapeutic mechanism, possibly activated through circulating secreted factors. Herein, we used ZMPSTE24-deficient mice, a lamin A defect progeria model, to investigate the ability of young MDSPCs to preserve neuromuscular tissue structure and function. We show that progeroid ZMPST24-deficient mice faithfully exhibit sarcopenia and age-related metabolic dysfunction. However, systemic transplantation of young MDSPCs into ZMPSTE24-deficient progeroid mice sustained healthy function and histopathology of muscular tissues throughout their 6-month life span in a sex-specific manner. Indeed, female—but not male—mice systemically transplanted with young MDSPCs demonstrated significant preservation of muscle endurance, muscle fiber size, mitochondrial respirometry, and neuromuscular junction morphometrics. These novel findings strongly suggest that young MDSPCs modulate the systemic environment of aged animals by secreted rejuvenating factors to maintain a healthy homeostasis in a sex-specific manner and that the female muscle microenvironment remains responsive to exogenous regenerative cues in older age. This work highlights the age- and sex-related differences in neuromuscular tissue degeneration and the future prospect of preserving health in older adults with systemic regenerative treatments.

Effects of currents and temperature on ecosystem productivity in Unimak Pass, Alaska, a premier seabird and biodiversity hotspot - William J. Sydeman; Sarah Ann Thompson; Marisol García-Reyes; Caitlin Kroeger; Brian Hoover; Sonia D. Batten; Nora A. Rojek (Progress in Oceanography, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

Oral delivery of a Streptococcus agalactiae vaccine to Nile tilapia (Oreochromis niloticus) using a novel cationic-based nanoemulsion containing bile salts - Dharacha Suwanbumrung; Sudthirak Wongkhieo; Wisawat Keaswejjareansuk; Piroonrat Dechbumroong; Manoj Tukaram Kamble; Teerapong Yata; Sirikorn Kitiyodom; Channarong Rodkhum; Kim D. Thompson; Katawut Namdee; Nopadon Pirarat (Fish & Shellfish Immunology, 2023)

Revisiting hydro-ecological impacts of climate change on a restored floodplain wetland via hydrological / hydraulic modelling and the UK Climate Projections 2018 scenarios - Julian R. Thompson; Hannah M. Clilverd; Jiaxuan Zheng; Honeyeh Iravani; Carl D. Sayer; Catherine M. Heppell; Jan C. Axmacher (Wetlands, 2023)
The hydro-ecological impacts of 40 UK Climate Projections 2018 scenarios on a restored lowland England river floodplain are assessed using a MIKE SHE / MIKE 11 model. Annual precipitation declines for 60% of scenarios (range: -26%–21%, with small, <5%, declines for the central probability level). Potential evapotranspiration increases for all probability levels except the most extreme, very unlikely, 10% level (range: -4%–43%, central probability 9%–20%) Mean, peak and low river discharges are reduced for all but the extreme 90% probability level. Reduced frequency of bankfull discharge dominates (at least halved for the central probability level). Floodplain inundation declines for over 97% of 320 scenario-events. Winter water table levels still intercept the surface, while mean and summer low levels are reduced. Declines in mean summer floodplain water table levels for the central probability level (0.22 m and 0.28 m for the 2050s and 2080s, respectively) are twice as large as those in the more dynamic riparian area. Declines reach 0.39 m for some 10% probability level scenarios. Simulated hydrological changes differ subtly from a previous assessment using earlier UK climate projections. A soil aeration stress index demonstrates that, under baseline conditions, prolonged high winter floodplain water tables drive long periods of low root-zone oxygen, in turn favouring vegetation communities adapted to waterlogged conditions. Climate change reduces aeration stress and the extent of appropriate conditions for these plant communities in favour of communities less tolerant of wet conditions.

Identifying the drivers of silky shark distribution and an evaluation of protection measures - Shona Murray; Jessica J. Meeuwig; Christopher D. H. Thompson; David Mouillot (Environmental Biology of Fishes, 2023)
The silky shark ( Carcharhinus falciformi s) has experienced a significant population decline associated with intense targeted and incidental fishing pressure. Large marine protected areas (MPAs) are increasingly advocated for the conservation of oceanic species like silky sharks, recognising that the benefits of MPAs to such species depend on a comprehensive understanding of their distribution, abundance and life history. We combined mid-water stereo-baited remote underwater video system (BRUVS) records with environmental, geographic and anthropogenic variables to document the distribution and abundance of silky shark populations, identify the most important predictors of their presence, abundance and body size, and determine if their abundance is greater within MPAs than in locations not designated as MPAs. From 1418 deployments of mid-water BRUVS across three ocean basins, 945 silky sharks were identified at 18 locations, with young-of-year ( < 87 cm TL) observed at four of these. Our study revealed generally low abundances of silky sharks as recorded on mid-water BRUVS across their cosmopolitan distribution, although our models identified seamounts as hotspots of abundance. Human pressure was a significant variable within our models, with proximity to human populations and ports being key drivers of silky shark abundance and body size. We did not observe a higher abundance of silky sharks inside MPAs compared to locations not designated as MPAs, suggesting that these MPAs have not been placed in areas where silky sharks remain relatively abundant. We therefore recommend expanding the current MPA network in line with the 30 × 30 initiative to more effectively protect key habitats such as seamounts.

Evidence for density‐dependent effects on body composition of a large omnivore in a changing Greater Yellowstone Ecosystem - Andrea Corradini; Mark A. Haroldson; Francesca Cagnacci; Cecily M. Costello; Daniel D. Bjornlie; Daniel J. Thompson; Jeremy M. Nicholson; Kerry A. Gunther; Katharine R. Wilmot; Frank T. van Manen (Global Change Biology, 2023)
Understanding the density‐dependent processes that drive population demography in a changing world is critical in ecology, yet measuring performance–density relationships in long‐lived mammalian species demands long‐term data, limiting scientists' ability to observe such mechanisms. We tested performance–density relationships for an opportunistic omnivore, grizzly bears ( Ursus arctos , Linnaeus, 1758) in the Greater Yellowstone Ecosystem, with estimates of body composition (lean body mass and percent body fat) serving as indicators of individual performance over two decades (2000–2020) during which time pronounced environmental changes have occurred. Several high‐calorie foods for grizzly bears have mostly declined in recent decades (e.g., whitebark pine [ Pinus albicaulis , Engelm, 1863]), while increasing human impacts from recreation, development, and long‐term shifts in temperatures and precipitation are altering the ecosystem. We hypothesized that individual lean body mass declines as population density increases (H1), and that this effect would be more pronounced among growing individuals (H2). We also hypothesized that omnivory helps grizzly bears buffer energy intake from changing foods, with body fat levels being independent from population density and environmental changes (H3). Our analyses showed that individual lean body mass was negatively related to population density, particularly among growing‐age females, supporting H1 and partially H2. In contrast, population density or sex had little effect on body fat levels and rate of accumulation, indicating that sufficient food resources were available on the landscape to accommodate successful use of shifting food sources, supporting H3. Our results offer important insights into ecological feedback mechanisms driving individual performances within a population undergoing demographic and ecosystem‐level changes. However, synergistic effects of continued climate change and increased human impacts could lead to more extreme changes in food availability and affect observed population resilience mechanisms. Our findings underscore the importance of long‐term studies in protected areas when investigating complex ecological relationships in an increasingly anthropogenic world.

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Development of a bivalent mucoadhesive nanovaccine to prevent francisellosis and columnaris diseases in Nile tilapia (Oreochromis niloticus) - Anurak Bunnoy; Kim D. Thompson; Patcharapong Thangsunan; Putita Chokmangmeepisarn; Teerapong Yata; Nopadon Pirarat; Sirikorn Kitiyodom; Pattanapong Thangsunan; Pimwarang Sukkarun; Pochara Prukbenjakul; Naphat Panthukumphol; Manami Morishita; et al. (Fish & Shellfish Immunology, 2023)

Impact of the 2014–2016 marine heatwave on US and Canada West Coast fisheries: Surprises and lessons from key case studies - Christopher M. Free; Sean C. Anderson; Elizabeth A. Hellmers; Barbara A. Muhling; Michael O. Navarro; Kate Richerson; Lauren A. Rogers; William H. Satterthwaite; Andrew R. Thompson; Jenn M. Burt; Steven D. Gaines; Kristin N. Marshall; et al. (Fish and Fisheries, 2023)
Marine heatwaves are increasingly affecting marine ecosystems, with cascading impacts on coastal economies, communities, and food systems. Studies of heatwaves provide crucial insights into potential ecosystem shifts under future climate change and put fisheries social‐ecological systems through “stress tests” that expose both vulnerabilities and resilience. The 2014–16 Northeast Pacific heatwave was the strongest and longest marine heatwave on record and resulted in profound ecological changes that impacted fisheries, fisheries management, and human livelihoods. Here, we synthesize the impacts of the 2014–2016 marine heatwave on US and Canada West Coast fisheries and extract key lessons for preparing global fisheries science, management, and industries for the future. We set the stage with a brief review of the impacts of the heatwave on marine ecosystems and the first systematic analysis of the economic impacts of these changes on commercial and recreational fisheries. We then examine ten key case studies that provide instructive examples of the complex and surprising challenges that heatwaves pose to fisheries social‐ecological systems. These reveal important insights into improving the resilience of monitoring and management and increasing adaptive capacity to future stressors. Key recommendations include: (1) expanding monitoring to enhance mechanistic understanding, provide early warning signals, and improve predictions of impacts; (2) increasing the flexibility, adaptiveness, and inclusiveness of management where possible; (3) using simulation testing to help guide management decisions; and (4) enhancing the adaptive capacity of fishing communities by promoting engagement, flexibility, experimentation, and failsafes. These advancements are important as global fisheries prepare for a changing ocean.

“The People's Summit”: A case for lived experience of food environments as a critical source of evidence to inform the follow-up to the 2021 UN Food Systems Summit - M. Spires; J. Battersby; N. Cohen; M. Daivadanam; K.M. Demmler; D. Mattioni; R. Pradeilles; C. Thompson; C. Turner; C. Venegas Hargous; S. Wertheim-Heck; W. Wills; et al. (Global Food Security, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Correction to: Site-specific zone delineation for varying Maize Hybrids based on field variability: a multi-hybrid planting application case study in eastern Nebraska - Rachel Stevens; Joe D. Luck; John T. Evans IV; Laura J. Thompson (Precision Agriculture, 2023)

Site-specific zone delineation for varying Maize Hybrids based on field variability: a multi-hybrid planting application case study in eastern Nebraska - Rachel Stevens; Joe D. Luck; John T. Evans IV; Laura J. Thompson (Precision Agriculture, 2023)

It's all in the mud - The use of sediment geochemistry to estimate contemporary water quality in lakes - Sean Waters; Javier Atalah; Lucy Thompson; Georgia Thomson-Laing; John K. Pearman; Jonathan Puddick; Jamie D. Howarth; Lizette Reyes; Marcus J. Vandergoes; Susanna A. Wood (Applied Geochemistry, 2023)

Phylogeography of the blacklegged tick ( Ixodes scapularis ) throughout the USA identifies candidate loci for differences in vectorial capacity - Julia C. Frederick; Alec T. Thompson; Prisha Sharma; Guha Dharmarajan; Isobel Ronai; Risa Pesapane; Ryan C. Smith; Kellee D. Sundstrom; Jean I. Tsao; Holly C. Tuten; Michael J. Yabsley; Travis C. Glenn (Molecular Ecology, 2023)
The blacklegged tick ( Ixodes scapularis ( Journal of the Academy of Natural Sciences of Philadelphia , 1821, 2 , 59)) is a vector of Borrelia burgdorferi sensu stricto ( s.s .) ( International Journal of Systematic Bacteriology , 1984, 34 , 496), the causative bacterial agent of Lyme disease, part of a slow‐moving epidemic of Lyme borreliosis spreading across the northern hemisphere. Well‐known geographical differences in the vectorial capacity of these ticks are associated with genetic variation. Despite the need for detailed genetic information in this disease system, previous phylogeographical studies of these ticks have been restricted to relatively few populations or few genetic loci. Here we present the most comprehensive phylogeographical study of genome‐wide markers in I. scapularis , conducted by using 3RAD (triple‐enzyme restriction‐site associated sequencing) and surveying 353 ticks from 33 counties throughout the species' range. We found limited genetic variation among populations from the Northeast and Upper Midwest, where Lyme disease is most common, and higher genetic variation among populations from the South. We identify five spatially associated genetic clusters of I. scapularis . In regions where Lyme disease is increasing in frequency, the I. scapularis populations genetically group with ticks from historically highly Lyme‐endemic regions. Finally, we identify 10 variable DNA sites that contribute the most to population differentiation. These variable sites cluster on one of the chromosome‐scale scaffolds for I. scapularis and are within identified genes. Our findings illuminate the need for additional research to identify loci causing variation in the vectorial capacity of I. scapularis and where additional tick sampling would be most valuable to further understand disease trends caused by pathogens transmitted by I. scapularis .

A positive temperature‐dependent effect of elevated CO 2 on growth and lipid accumulation in the planktonic copepod, Calanus finmarchicus - David M. Fields; Jeffrey A. Runge; Cameron R. S. Thompson; Caroline M. F. Durif; Steven D. Shema; Reidun M. Bjelland; Maura Niemisto; Michael T. Arts; Anne Berit Skiftesvik; Howard I. Browman (Limnology and Oceanography, 2023)
Calanus finmarchicus were reared from eggs to adults at 12°C and 16°C with non‐limiting food in combination with ambient (600 μ atm) and high (1100 μ atm) p CO 2 . These conditions are likely to be encountered by the species at the southern margins of its biogeographical range by the end of the century. Dry weight (DW), carbon (C) and nitrogen (N) mass, oil‐sac volume (OSV), fatty acid composition (FA), and oxygen consumption rates (OCR) were measured on newly molted stage CV copepodites and recently molted adult females. By focusing our measurements on these precise events in the life cycle, we were able to obtain a more accurate comparison of growth and respiration across treatments. Copepods raised at 12°C had a significantly greater DW, OSV, and C and N mass than those raised at 16°C High p CO 2 , independent of temperature, was associated with a further increase in the DW and C content of the copepods. Interactive effects of temperature and p CO 2 resulted in a larger OSV at low temperature and high p CO 2 . Mass‐specific respiration rates were significantly lower at lower temperatures and elevated p CO 2 suggesting that the increase in mass (DW, C, and OSV) resulted from reduced metabolic cost. The composition of fatty acids in the copepods varied mainly with temperature. Two fatty acids varied with p CO 2 : 16:0 tended to decrease with higher p CO 2 and 18:3n−3 tended to increase with higher p CO 2 . These observations suggest that elevated p CO 2 /lower pH in future oceans may have a beneficial effect on C. finmarchicus .

From the Lebombo Monocline to the Mozambique Deep Basin, using combined wide-angle and reflection seismic data - M. Moulin; A. Leprêtre; F. Verrier; P. Schnürle; M. Evain; P. de Clarens; J. Thompson; N. Dias; A. Afilhado; A. Loureiro; D. Aslanian (Tectonophysics, 2023)

Surface Biology and Geology imaging spectrometer: A case study to optimize the mission design using intrinsic dimensionality - K. Cawse-Nicholson; A.M. Raiho; D.R. Thompson; G.C. Hulley; C.E. Miller; K.R. Miner; B. Poulter; D. Schimel; F.D. Schneider; P.A. Townsend; S.K. Zareh (Remote Sensing of Environment, 2023)

Design Considerations for Intratracheal Delivery Devices to Achieve Proof-of-Concept Dry Powder Biopharmaceutical Delivery in Mice - Myla Manser; Vidthiya Jeyanathan; Mangalakumari Jeyanathan; Xueya Feng; Myrna B. Dolovich; Zhou Xing; Emily D. Cranston; Michael R. Thompson (Pharmaceutical Research, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Prevalence of neonicotinoid insecticides in paired private-well tap water and human urine samples in a region of intense agriculture overlying vulnerable aquifers in eastern Iowa - Darrin A. Thompson; Dana W. Kolpin; Michelle L. Hladik; Hans-Joachim Lehmler; Shannon M. Meppelink; Matthew C. Poch; John D. Vargo; Victor A. Soupene; Nafis Md Irfan; Morgan Robinson; Kurunthachalam Kannan; Laura E. Beane Freeman; et al. (Chemosphere, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Environmental variability and krill abundance in the central California current: Implications for ecosystem monitoring - Jeffrey G. Dorman; William J. Sydeman; Sarah Ann Thompson; Joseph D. Warren; Helen J. Killeen; Brian A. Hoover; John C. Field; Jarrod A. Santora (Frontiers in Marine Science, 2023)
Krill are a direct conduit between primary productivity and recreationally and commercially important higher trophic level species globally. Determining how krill abundance varies with temporal environmental variation is key to understanding their function in coastal-pelagic food webs, as well as applications in fisheries management. We used nine years (2012–19 and 2021) of late spring/early summer hydroacoustic-trawl survey data in the California Current Ecosystem (CCE), coupled with new target strength models of two krill species ( Euphausia pacifica and Thysanoessa spinifera ), to investigate how adult krill biomass varied during a decade of unusual ocean climate variability. We estimate a mean biomass of 1.75–2.0 million metric tons on the central and northern California continental shelf. Overall, relative krill biomass was ~30% lower during 2015 and 2016, corresponding to a major warming event, and ~30% higher in 2013 and 2018, years of exceptionally strong upwelling. Variation in biomass was related to the prior year’s environmental conditions derived from our seasonal Multivariate Ocean Climate Index (MOCI), and E. pacifica and T. spinifera showed similar covariation during the study period. Biomass co-varied at different spatial scales and across sampling devices, suggesting that multiple indicators of abundance (and dispersion) are available and should be applied in ecosystem monitoring and modeling of krill and krill-dependent predators in the California Current ecosystem.

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Health Literacy Correlates to HPV Vaccination Among US Adults Ages 27–45 - Annalynn M. Galvin; Ashvita Garg; Stacey B. Griner; Jonathan D. Moore; Erika L. Thompson (Journal of Cancer Education, 2023)

Determining sex in golden eagle (Aquila chrysaetos) nestlings - G. Peniche; D. J. Shaw; S. G. Dures; S. Ciavaglia; D. B. A. Thompson; N. E. Anderson; A. L. Meredith (European Journal of Wildlife Research, 2023)
Incorporating sex ratios of nestlings into population viability studies increases knowledge of overall health of endangered populations. Currently, a reliable non-invasive method to identify the sex of golden eagle nestlings is not available; however, claims are commonly made based on morphology. Ten biometric measurements from 43 Scottish golden eagles aged 2–7.5 weeks were assessed to see if sex could actually be determined using this non-invasive methodology. Sex was confirmed via molecular analysis of blood samples. Discrete and principal component analyses of the different biometrics could not correctly determine individual nestling sex. Therefore, despite being more invasive, molecular sexing remains the recommended tool of choice for accurate sex identification of Scottish golden eagle nestlings younger than 7.5 weeks of age. This has important implications for golden eagle field studies where empirical morphological measurements are frequently and typically taken, but we have shown are not reliable in determining the sex of such young nestlings.

Strategies to enhance tilapia immunity to improve their health in aquaculture - Bei Wang; Kim D. Thompson; Eakapol Wangkahart; Jidapa Yamkasem; Melba G. Bondad‐Reantaso; Puntanat Tattiyapong; Jichan Jian; Win Surachetpong (Reviews in Aquaculture, 2023)
Various emerging and re‐emerging diseases, such as streptococcosis, tilapia lake virus disease and infectious spleen and kidney necrosis virus disease, have had a significant economic impact on the tilapia industry over the last decade. These diseases have resulted in high levels of morbidity and mortality, production losses and trade restrictions. In the absence of effective husbandry management, disease prevention strategies and appropriate biosecurity measures, infectious diseases will continue to challenge the sustainability of global tilapia aquaculture. Strategies used to reduce the impact of disease include feeding probiotic and prebiotic supplements to enhance tilapia health and to modulate the fish's gut microbiota to improve gut health. Herbal medicines and immunostimulants are also used to enhance immunity to disease, while vaccines are available, or are under development, for a number of economically important pathogens affecting tilapia culture. This review provides an overview of the benefits of enhancing the immune response of tilapia to improve their health, and in turn reduce the levels of pathogens within tilapia farming systems.

Genetic features of the marine polychaete Sirsoe methanicola from metagenomic data - Shen Jean Lim; Luke R. Thompson; Kelly D. Goodwin (Frontiers in Marine Science, 2023)
The methane ice worm Sirsoe methanicola is the only marine polychaete species observed to colonize the methane hydrates of the Gulf of Mexico. Methane hydrates are ephemeral features of deep-sea cold seeps, and finding worm-colonized hydrates is rare; thus, little is known about these organisms. Recent metagenomic analysis predicted prokaryotic taxa and pathways from S. methanicola gut contents and worm fragments. Here, we increase the genetic information known about S. methanicola by assembling its nuclear rRNA genes (18S rRNA and 28S rRNA), mitochondrial genome (mitogenome), and other protein-coding genes from metagenomic data. Assembled 18S rRNA and 28S rRNA gene sequences of S. methanicola were near-identical to previously reported S. methanicola sequences. The 17,403-bp mitogenome of S. methanicola is the first mitogenome sequence of the family Hesionidae , consisting of 39.03% G+C content, 13 protein-coding genes, 24 tRNAs (including two split trnM genes), and 2 rRNA genes. Protein-coding genes in the S. methanicola metagenomes assigned to the phylum Annelida were involved in cell adhesion, signaling, ubiquitin system, metabolism, transport, and other processes. From the metagenomes, we also found 42 homologs of the cytochrome P450 (CYP) superfamily putatively involved in polycyclic aromatic hydrocarbon (PAH) metabolism. Our results encourage further studies into the genetic adaptations of S. methanicola to its methane hydrate habitat, especially in the context of deep-sea ecology and nutrient cycling.

Evaluation of seasonal site-level demography and management for northern bobwhite using integrated population models - Emily A. Sinnott; Frank R. Thompson; Mitch D. Weegman; Thomas R. Thompson; Alisha R. Mosloff; R. Kyle Hedges; Frank L. Loncarich (Ecological Modelling, 2023)

Genomic and phylogenetic characterization of wheat yellows virus, a novel tenuivirus infecting wheat in South Africa - David A. Read; Ronel Roberts; Goddy Prinsloo; Genevieve D. Thompson (Archives of Virology, 2023)

Deterministic processes drive national‐scale patterns in lake surface sediment bacteria and eukaryotic assemblage composition - John K. Pearman; Janet Adamson; Georgia Thomson‐Laing; Lucy Thompson; Sean Waters; Marcus J. Vandergoes; Jamie D. Howarth; Susanna A. Wood (Limnology and Oceanography, 2023)
Biological communities within lake surface sediments play a vital role in biogeochemical cycling and ecosystem services. Knowledge on abundance‐occupancy patterns and assembly processes across large spatial scales and over multiple environmental gradients is limited, yet essential to aid in protection and restoration. In the present study, surface sediment samples were collected from 296 lakes across a wide spatial scale and covering multiple interacting environmental gradients including size, depth, altitude, and trophic state. A suite of physicochemical parameters were used to characterize the environmental conditions and bacterial and eukaryotic assemblages were determined using 16S and 18S rRNA metabarcoding. The majority (~ 55%) of amplicon sequence variants were only found in a single lake with eukaryotes having a more restricted distribution than bacteria. Deterministic processes were inferred to be dominant for both bacteria (78%) and eukaryotes (51%), with variable selection being especially important for bacteria (49%). Variation partitioning indicated that land use in the catchment, which is strongly related to trophic state, was the most important environmental factor in explaining the assemblage composition. This nationwide study across broad gradients provides new insights into the ecology of bacteria and eukaryotes in lake surface sediments and a platform to better understand the effects of multiple environmental stressors on lake sediment assemblages.

Mapping lesion, structural disconnection, and functional disconnection to symptoms in semantic aphasia - Nicholas E. Souter; Xiuyi Wang; Hannah Thompson; Katya Krieger-Redwood; Ajay D. Halai; Matthew A. Lambon Ralph; Michel Thiebaut de Schotten; Elizabeth Jefferies (Brain Structure and Function, 2022)
Patients with semantic aphasia have impaired control of semantic retrieval, often accompanied by executive dysfunction following left hemisphere stroke. Many but not all of these patients have damage to the left inferior frontal gyrus, important for semantic and cognitive control. Yet semantic and cognitive control networks are highly distributed, including posterior as well as anterior components. Accordingly, semantic aphasia might not only reflect local damage but also white matter structural and functional disconnection. Here, we characterise the lesions and predicted patterns of structural and functional disconnection in individuals with semantic aphasia and relate these effects to semantic and executive impairment. Impaired semantic cognition was associated with infarction in distributed left-hemisphere regions, including in the left anterior inferior frontal and posterior temporal cortex. Lesions were associated with executive dysfunction within a set of adjacent but distinct left frontoparietal clusters. Performance on executive tasks was also associated with interhemispheric structural disconnection across the corpus callosum. In contrast, poor semantic cognition was associated with small left-lateralized structurally disconnected clusters, including in the left posterior temporal cortex. Little insight was gained from functional disconnection symptom mapping. These results demonstrate that while left-lateralized semantic and executive control regions are often damaged together in stroke aphasia, these deficits are associated with distinct patterns of structural disconnection, consistent with the bilateral nature of executive control and the left-lateralized yet distributed semantic control network.

A Review of the Compressive Stiffness of the Human Head - Darcy W. Thompson-Bagshaw; Ryan D. Quarrington; Claire F. Jones (Annals of Biomedical Engineering, 2022)
Synthetic surrogate head models are used in biomechanical studies to investigate skull, brain, and cervical spine injury. To ensure appropriate biofidelity of these head models, the stiffness is often tuned so that the surrogate’s response approximates the cadaveric response corridor. Impact parameters such as energy, and loading direction and region, can influence injury prediction measures, such as impact force and head acceleration. An improved understanding of how impact parameters affect the head’s structural response is required for designing better surrogate head models. This study comprises a synthesis and review of all existing ex vivo head stiffness data, and the primary factors that influence the force–deformation response are discussed. Eighteen studies from 1972 to 2019 were identified. Head stiffness statistically varied with age (pediatric vs. adult), loading region, and rate. The contact area of the impactor likely affects stiffness, whereas the impactor mass likely does not. The head’s response to frontal impacts was widely reported, but few studies have evaluated the response to other impact locations and directions. The findings from this review indicate that further work is required to assess the effect of head constraints, loading region, and impactor geometry, across a range of relevant scenarios.

Steelhead trout (Oncorhynchus mykiss) fed probiotic during the earliest developmental stages have enhanced growth rates and intestinal microbiome bacterial diversity - Ian S. Hines; Kevin D. Santiago-Morales; Clay S. Ferguson; Jireh Clarington; Meaghan Thompson; Meghann Rauschenbach; Uri Levine; David Drahos; Frank O. Aylward; Stephen A. Smith; David D. Kuhn; Ann M. Stevens (Frontiers in Marine Science, 2022)
Sustainable aquaculture practices can help meet the increasing human demand for seafood, while easing pressures on natural fish populations. Studies aimed at increasing fish production in aquaculture have included supplementary dietary probiotics that often promote general health and enhanced growth rates by altering the microbiome of the host. Steelhead trout ( Oncorhynchus mykiss ) is anadromous, like salmon, and it is a subspecies of rainbow trout capable of rapid growth, making it an attractive fish to the aquaculture industry. In this study, the impact of feeding a Bacillus subtilis probiotic on the bacterial microbiome of steelhead trout was examined temporally across several stages of animal development, from eggs (day -19) through 184 days after hatching, in relation to physiological measures. Diets included: commercial feed only as a control (A), continually-fed probiotic top-coated on commercial feed (B), commercial then switch to probiotic feed (C), or probiotic then switch to commercial feed (D). Validation of probiotic concentrations on feed and in fish tissues was performed using CFU/g and qPCR, respectively. Fish growth was measured and samples for intestinal microbiome analyses were collected at multiple timepoints during fish development. Fish fed diet D yielded higher weights than the other three diets, with little impact on other biometric parameters. However, bacterial microbiome analysis indicated an increasing trend of overall alpha diversity from the egg stage to day 29 for fish fed the various diets with diet D having the highest diversity. Fish fed diets A and D maintained a high alpha diversity beyond day 29 in contrast to a decreased trend for fish still being fed probiotics in diets B and C. The fish fed diets B and C harbored a significantly higher relative abundance of Bacillus sp. in their total microbiomes (feces + mucosa). Interestingly, the mucosal-only microbiome indicated little variation between the four groups of fish. Feeding the probiotic earlier in development, during the hatchery phase, to influence bacterial microbiome composition in the intestine (rather than later after the microbiome has been established) appears to be a more effective aquaculture practice by enhancing microbiome diversity while enabling higher fish yields.

Assessing progress in data reporting by tuna Regional Fisheries Management Organizations - Kristina N. Heidrich; Maria José Juan‐Jordá; Hilario Murua; Christopher D. H. Thompson; Jessica J. Meeuwig; Dirk Zeller (Fish and Fisheries, 2022)
Tuna Regional Fisheries Management Organizations (RFMOs) are responsible for conservation and sustainable management of transboundary tuna resources in Exclusive Economic Zones and Areas Beyond National Jurisdiction (ABNJ). The data collected and analyses performed by tuna RFMOs are one of the main sources of scientific information supporting the management, sustainable use and conservation of biodiversity in the ABNJ. An understanding of the scope and availability of data provided by tuna RFMOs is timely, given the expected establishment of a new legally binding high seas agreement to protect marine biodiversity in the ABNJ. We examined official catch statistics and stock assessments that are accessible in the public domain for the five tuna RFMOs, and evaluated their taxonomic, spatial and temporal resolution. We found that the Atlantic and Indian Ocean tuna RFMOs report catches for a greater number of taxa compared to Pacific RFMOs. There are substantial gaps in the taxonomic resolution of sharks and rays and ‘other teleosts’, and only about half of the reported global catches are georeferenced, despite existing mandatory requirements. Additionally, the estimation and reporting of discards in all tuna RFMOs remains incomplete. Tuna RFMOs have made progress in implementing stock assessments for a wide range of taxa including targeted species with high economic value but also functionally important non‐target species with lower economic value. However, assessments should be expanded to cover other bycatch species. We emphasize the importance of accessible and accurate statistics, for supporting the research and societal oversight needed under any future ABNJ biodiversity treaty.

Lake Erie field trials to advance autonomous monitoring of cyanobacterial harmful algal blooms - Paul A. Den Uyl; Luke R. Thompson; Reagan M. Errera; James M. Birch; Christina M. Preston; William Ussler; Colleen E. Yancey; Subba Rao Chaganti; Steven A. Ruberg; Gregory J. Doucette; Gregory J. Dick; Christopher A. Scholin; et al. (Frontiers in Marine Science, 2022)
Biomolecular analyses are used to investigate the dynamics of cyanobacterial harmful algal blooms (cyanoHABs), with samples collected during monitoring often analyzed by qPCR and sometimes amplicon and metagenomic sequencing. However, cyanoHAB research and monitoring programs face operational constraints due to the reliance on human resources for sample collections. To address this impediment, a third-generation Environmental Sample Processor (3G ESP) integrated with a long-range autonomous underwater vehicle (LRAUV) was tested during seasonal blooms of Microcystis in western Lake Erie (WLE) in 2018 and 2019. The LRAUV-3G ESP successfully performed flexible, autonomous sampling across a wide range of cyanoHAB conditions, and results indicated equivalency between autonomous and manual methods. No significant differences were found between LRAUV-3G ESP and manual sample collection and handling methods in the 12 parameters tested. Analyzed parameters included concentrations of total cyanobacteria and microcystin toxin gene via qPCR; relative abundances of bacterial amplicon sequence variants (ASVs) from 16S rRNA gene amplicon sequencing; and community diversity measures from both 16S amplicon and metagenomic sequencing. The LRAUV-3G ESP provided additional sampling capacity and revealed differences between field seasons for bacterial taxa and concentrations of total cyanobacteria and microcystin toxin gene. Metagenomic analysis of multiple microcystin toxin genes corroborated the use of the mcyE gene as a proxy for the genomic potential of WLE cyanoHABs to produce microcystin. Overall, this study provides support for the use of autonomous ‘omics capability in WLE to help expand the spatial and temporal coverage of cyanoHAB monitoring operations.

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Dextran Mass Ratio Controls Particle Drying Dynamics in a Thermally Stable Dry Powder Vaccine for Pulmonary Delivery - Myla Manser; Blair A. Morgan; Xueya Feng; Rod G. Rhem; Myrna B. Dolovich; Zhou Xing; Emily D. Cranston; Michael R. Thompson (Pharmaceutical Research, 2022)

Evaluation and characterisation of metal sorption and retention by drinking water treatment residuals (WTRs) for environmental remediation - K. A. H. Arab; D. F. Thompson; I. W. Oliver (International Journal of Environmental Science and Technology, 2022)
Drinking water treatment residuals (WTRs) are wastes generated when water is clarified using aluminium or iron salts. They are increasingly being considered as a resource with potential reuse value, particularly in relation to soil or water remediation. Adsorption–desorption capacity of Al-based (Al-WTR) and Fe-based (Fe-WTR) materials was investigated here for Pb and Zn, both separately and in combination, as a preliminary trial to assess their utility for immobilising contaminant metals in environmental settings. Maximum adsorption observed at the highest test solution concentrations imposed (400 mg/L) was similar for each WTR type and each metal; Al-WTRs sorbed Zn at 3579 mg/kg and Pb at 4025 mg/kg, while Fe-WTRs sorbed Zn and Pb at 3579 mg/kg and 3980 mg/kg, respectively. Equilibrium adsorption data were tested against Langmuir, Freundlich, and Temkin isotherm models, which indicated a substantial reserve capacity for further Pb sorption and that multiple sorption mechanisms were involved. Subsequent desorption tests with 0.001 M CaCl 2 solution indicated that > 89.76% of sorbed metal remained sorbed. When in solution together, both metals were strongly sorbed by WTRs, but a slight preference for Pb was observed. The results indicate that WTRs would be very effective immobilising agents if placed in contaminated soil or if used to treat contaminated waters.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Risk of clear-cell adenocarcinoma of the vagina and cervix among US women with potential exposure to diethylstilbestrol in utero - Mary C. White; Hannah K. Weir; Ashwini V. Soman; Lucy A. Peipins; Trevor D. Thompson (Cancer Causes & Control, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Establishing haematological and biochemical reference intervals for free-ranging Scottish golden eagle nestlings (Aquila chrysaetos) - Peniche G.; Shaw D.J.; Thompson D.B.A.; Brain J.C.; Reid R.; Weston E.; Benn S.; Anderson D.; Grant J.; Pate L.; Anderson N.E.; Meredith A.L. (European Journal of Wildlife Research, 2022)
Health assessment of individuals is an important aspect of monitoring endangered wildlife populations. Haematological and biochemical values are a common health assessment tool, and whilst reference values are well established for domestic species, they are often not available for wild animal species. This study established 31 haematological and biochemical reference intervals for golden eagle ( Aquila chrysaetos ) nestlings in Scotland, in order to improve the understanding of the species’ health and support conservation efforts. Reference intervals were created from 47 nestlings (ages 2–7.5 weeks old) across 37 nests, to date, the largest sample of wild individuals of this species and age cohort sampled for these purposes. Upper reference intervals for concentrations of lymphocytes, total protein, cholesterol, triglycerides, uric acid, and monocytes, calculated in this study, are higher than those found for adult raptors and the interval span is higher than that observed in adult raptors for concentrations of AST, albumin, eosinophil, LDH, and monocyte count. Statistically significant positive correlations were found with age and concentrations of haemoglobin, lymphocytes, serum pH, and creatine kinase, and significant negative correlations with age for concentrations of thrombocytes, heterophils, total protein, globulin, and lactate dehydrogenase. Packed cell volume was significantly higher for females than males, and concentration of calcium and eosinophils were higher for individuals in good body condition than those in moderate body condition. The reference intervals produced by this study will be of important use to the veterinary and conservation management communities and will aid the long-term monitoring of the Scottish golden eagle population health.

The impact of age, sex, cardio-respiratory fitness, and cardiovascular disease risk on dynamic cerebral autoregulation and baroreflex sensitivity - Joseph D. Maxwell; Daniel J. Bannell; Aine Brislane; Sophie E. Carter; Gemma D. Miller; Kirsty A. Roberts; Nicola D. Hopkins; David A. Low; Howard H. Carter; Andrew Thompson; Jurgen A. H. R. Claassen; Dick H. J. Thijssen; et al. (European Journal of Applied Physiology, 2022)
Background Humans display an age-related decline in cerebral blood flow and increase in blood pressure (BP), but changes in the underlying control mechanisms across the lifespan are less well understood. We aimed to; (1) examine the impact of age, sex, cardiovascular disease (CVD) risk, and cardio-respiratory fitness on dynamic cerebral autoregulation and cardiac baroreflex sensitivity, and (2) explore the relationships between dynamic cerebral autoregulation (dCA) and cardiac baroreflex sensitivity (cBRS). Methods 206 participants aged 18–70 years were stratified into age categories. Cerebral blood flow velocity was measured using transcranial Doppler ultrasound. Repeated squat-stand manoeuvres were performed (0.10 Hz), and transfer function analysis was used to assess dCA and cBRS. Multivariable linear regression was used to examine the influence of age, sex, CVD risk, and cardio-respiratory fitness on dCA and cBRS. Linear models determined the relationship between dCA and cBRS. Results Age, sex, CVD risk, and cardio-respiratory fitness did not impact dCA normalised gain, phase, or coherence with minimal change in all models ( P > 0.05). cBRS gain was attenuated with age when adjusted for sex and CVD risk (young–older; β = − 2.86 P < 0.001) along with cBRS phase (young–older; β = − 0.44, P < 0.001). There was no correlation between dCA normalised gain and phase with either parameter of cBRS. Conclusion Ageing was associated with a decreased cBRS, but dCA appears to remain unchanged. Additionally, our data suggest that sex, CVD risk, and cardio-respiratory fitness have little effect.

Novel DNA‐based in situ hybridization method to detect Desmozoon lepeophtherii in Atlantic salmon tissues - Ana Herrero; Oswaldo Palenzuela; Hamish Rodger; Chris Matthews; Mar Marcos‐López; James E. Bron; Mark P. Dagleish; Kim D. Thompson (Journal of Fish Diseases, 2022)
The microsporidian Desmozoon lepeophtherii Freeman and Sommerville, 2009 is considered significant in the pathogenesis of gill disease in Atlantic salmon ( Salmo salar Linnaeus, 1758). Due to the difficulty in detecting D. lepeophtherii in tissue sections, infections are normally diagnosed by molecular methods, routine haematoxylin and eosin (H&E) stained gill tissue sections and the use of other histochemical stains and labels to confirm the presence of spores. An in situ hybridization (ISH) protocol specific for D. lepeophtherii was developed using DIG‐labelled oligonucleotide probes. Diseased Atlantic salmon gills were analysed by ISH, calcofluor white (CW) and H&E. All methods showed high levels of specificity (100%) in their ability to detect D. lepeophtherii , but the sensitivity was higher with ISH (92%), compared with CW (64%) and the presence of microvesicles on H&E stained sections (52%). High levels of D. lepeophtherii spores were significantly associated ( p D. lepeophtherii ‐associated pathology in the gills, with Ct values below 19 and over 100 microsporidia/10 mm 2 of gill tissue (from the ISH counts) seemingly necessary for the development of microvesicles. The ISH method has the advantage over other histological techniques in that it allows all life stages of the microsporidian to be detected in infected salmon gill tissue sections.

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Plume Layer Influences the Amazon Reef Sponge Microbiome Primary Producers - Otávio H. B. Pinto; Till L. V. Bornemann; Rafael S. Oliveira; Tayna D. Frederico; Betania F. Quirino; Alexander J. Probst; Mayanne A. M. de Freitas; Fabiano L. Thompson; Ricardo H. Kruger (Frontiers in Marine Science, 2022)
Symbiont relationships between corals and photosynthetic microorganisms sustain coral reef existence. However, the Great Amazon Reef System (GARS) stays under a plume layer that attenuates the entry of light, and instead of corals, sponges are the major reef epifauna, for which little is known about the function of the associated microbiome. Here, we used genome-resolved metagenomics to investigate how the sponge microbiome supports its host and overcomes the reduced light availability, recovering 205 MAGs from Agelas and Geodia sponges with completeness >70% and contamination <10%. Beta diversity estimates based on the 16S rRNA genes indicated the microbiomes of Amazon and Caribbean sponges to be distinct (P<0.01), with heterotrophic lifestyles being prevalent in Amazon sponge microbiomes (P<0.05). Nevertheless, genes indicating the carbon fixation pathways 3-Hydroxypropionate/4-Hydroxybutyrate cycle, 3-Hydroxypropionate bicycle, Reductive Tricarboxylic Acid Cycle, and Calvin-Benson-Bassham cycle could be recovered in low abundance. The presence of Cyanobacteria, represented by both 16S rRNA analyses and low-quality MAGs indicated light incidence on the reef. The metabolic profile shows that the GARS sponge microbiome had genes for sulfate reduction, sulfur oxidation, nitric oxide reduction, ammonia oxidation, nitrate reduction, nitrite ammonification, nitrite oxidation, and nitrite reduction, indicating that the microbiome might play a role in detoxification of the holobiont. We conclude, that neither the plume-limited photosynthesis of the sponge microbiome nor the primary producers sustain the organic carbon input for the sponges, which likely live off plume-associated organic carbon and their heterotrophic microbiota.

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

The Effect of Axial Compression and Distraction on Cervical Facet Cartilage Apposition During Shear and Bending Motions - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2022)
During cervical spine trauma, complex intervertebral motions can cause a reduction in facet joint cartilage apposition area (CAA), leading to cervical facet dislocation (CFD). Intervertebral compression and distraction likely alter the magnitude and location of CAA, and may influence the risk of facet fracture. The aim of this study was to investigate facet joint CAA resulting from intervertebral distraction (2.5 mm) or compression (50, 300 N) superimposed on shear and bending motions. Intervertebral and facet joint kinematics were applied to multi rigid-body kinematic models of twelve C6/C7 motion segments (70 ± 13 year, nine male) with specimen-specific cartilage profiles. CAA was qualitatively and quantitatively compared between distraction and compression conditions for each motion; linear mixed-effects models ( α = 0.05) were applied. Distraction significantly decreased CAA throughout all motions, compared to the compressed conditions ( p

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Applying assessments of adaptive capacity to inform natural‐resource management in a changing climate - Lindsey L. Thurman; John E. Gross; Claudia Mengelt; Erik A. Beever; Laura M. Thompson; Gregor W. Schuurman; Christopher L. Hoving; Julian D. Olden (Conservation Biology, 2022)
Adaptive capacity (AC)—the ability of a species to cope with or accommodate climate change—is a critical determinant of species vulnerability. Using information on species’ AC in conservation planning is key to ensuring successful outcomes. We identified connections between a list of species’ attributes (e.g., traits, population metrics, and behaviors) that were recently proposed for assessing species’ AC and management actions that may enhance AC for species at risk of extinction. Management actions were identified based on evidence from the literature, a review of actions used in other climate adaptation guidance, and our collective experience in diverse fields of global‐change ecology and climate adaptation. Selected management actions support the general AC pathways of persist in place or shift in space, in response to contemporary climate change. Some actions, such as genetic manipulations, can be used to directly alter the ability of species to cope with climate change, whereas other actions can indirectly enhance AC by addressing ecological or anthropogenic constraints on the expression of a species’ innate abilities to adapt. Ours is the first synthesis of potential management actions directly linked to AC. Focusing on AC attributes helps improve understanding of how and why aspects of climate are affecting organisms, as well as the mechanisms by which management interventions affect a species’ AC and climate change vulnerability. Adaptive‐capacity‐informed climate adaptation is needed to build connections among the causes of vulnerability, AC, and proposed management actions that can facilitate AC and reduce vulnerability in support of evolving conservation paradigms.

Early Immune Modulation in European Seabass (Dicentrarchus labrax) Juveniles in Response to Betanodavirus Infection - Mariana Vaz; Damiana Pires; Pedro Pires; Marco Simões; Ana Pombo; Paulo Santos; Beatriz do Carmo; Ricardo Passos; Janina Z. Costa; Kim D. Thompson; Teresa Baptista (Fishes, 2022)
The early host–pathogen interaction between European seabass (Dicentrarchus labrax) and Betanodavirus was examined by using juvenile fish infected intramuscularly with RGNNV (red-spotted grouper nervous necrosis virus). The time course selected for sampling (0–144 h post-infection (hpi)) covered the early stages of infection, with hematological, antioxidant and immunological responses examined. Early activation of the host’s immune system was seen in the first few hours post-infection (6 to 9 hpi), as evidenced by an increase in tnfα, cd28 and c3 expression in the head kidney of infected fish. Most hematological parameters that were examined showed significant differences between sampling times, including differences in the number of thrombocytes and various leukocyte populations. The plasma lysozyme concentration decreased significantly over the course of the trial, and most antioxidant parameters examined in the liver showed significant differences over the infection period. At 144 hpi, peak expression of tnfα and il-1β coincided with the appearance of disease symptoms, peak levels of virus in the brain and high levels of fish mortality. The results of the study show the importance of analyzing the early interactions between European seabass and Betanodavirus to establish early indicators of infection to prevent more severe outcomes of the infection from occurring.

Fisheries Surveys Are Essential Ocean Observing Programs in a Time of Global Change: A Synthesis of Oceanographic and Ecological Data From U.S. West Coast Fisheries Surveys - Natalya D. Gallo; Noelle M. Bowlin; Andrew R. Thompson; Erin V. Satterthwaite; Briana Brady; Brice X. Semmens (Frontiers in Marine Science, 2022)
As climate change and other anthropogenic impacts on marine ecosystems accelerate in the 21st century, there is an increasing need for sustained ocean time series. A robust and collaborative network of regional monitoring programs can detect early signs of unanticipated changes, provide a more holistic understanding of ecosystem responses, and prompt faster management actions. Fisheries-related surveys that collect fisheries-independent data (hereafter referred to as “fisheries surveys”) are a key pillar of sustainable fisheries management and are ubiquitous in the United States and other countries. From the perspective of ocean observing, fisheries surveys offer three key strengths: (1) they are sustained due to largely consistent funding support from federal and state public sector fisheries agencies, (2) they collect paired physical, chemical, and biological data, and (3) they have large and frequently overlapping spatial footprints that extend into the offshore region. Despite this, information about fisheries survey data collection can remain poorly known to the broader academic and ocean observing communities. During the 2019 CalCOFI Symposium, marking the 70th anniversary of the California Cooperative Oceanic Fisheries Investigations (CalCOFI), representatives from 21 ocean monitoring programs on the North American West Coast came together to share the status of their monitoring programs and examine opportunities to leverage efforts to support regional ecosystem management needs. To increase awareness about collected ocean observing data, we catalog these ongoing ocean time series programs and detail the activities of the nine major federal or state fisheries surveys on the U.S. West Coast. We then present three case studies showing how fisheries survey data contribute to the understanding of emergent ecosystem management challenges: marine heatwaves, ocean acidification, and contaminant spills. Moving forward, increased cross-survey analyses and cooperation can improve regional capacity to address emerging challenges. Fisheries surveys represent a foundational blueprint for ecosystem monitoring. As the international community moves toward a global strategy for ocean observing needs, fisheries survey programs should be included as data contributors.

Skin mucus proteins of rainbow trout ( Oncorhynchus mykiss ) in response to mucosal vaccination and challenge with Flavobacterium psychrophilum - R. Hoare; K. Shahin; K. McLean; A. Adams; K. D. Thompson (Journal of Fish Diseases, 2022)

Diverse state‐level marine aquaculture policy in the United States: Opportunities and barriers for industry development - Sarah E. Lester; Rebecca R. Gentry; Hayley R. Lemoine; Halley E. Froehlich; Luke D. Gardner; Mae Rennick; Elizabeth O. Ruff; Kimberly D. Thompson (Reviews in Aquaculture, 2022)
Marine aquaculture (mariculture) plays a relatively small role in the United States’ domestic seafood production, despite considerable scope for industry development and high volumes of imported farmed seafood resulting in a significant trade deficit. Currently, most mariculture in the United States occurs in nearshore waters or land‐based tanks and is regulated and guided using state‐level policy, with a relative absence of national coordinating mechanisms to link the patchwork of state policies. There is no comprehensive evaluation showing how different state policies may be enabling or impeding mariculture development. In response, we provide the first systematic overview of state‐level mariculture policy for the 23 coastal marine states in the United States. We compiled information for 16 aquaculture and mariculture policy attributes, including legislation, regulations and management characteristics, particularly those that could enable mariculture development. We found considerable heterogeneity in how states govern and regulate mariculture. As examples, 48% of states have an aquaculture development act, 35% have spatial zoning specifically for mariculture and only 26% have a government‐provided mariculture best management practices document. We examined the relationship between enabling policies and metrics of mariculture output (e.g. production value, number of farms), and while the effect of enabling policy is often equivocal, certain features stand out as important (e.g. government‐provided best management practices). Overall, this policy synthesis suggests approaches that may be influential in enabling mariculture development, which could inform new state‐level policies, an effective overarching federal policy in the United States, or policies in other countries seeking to support an expanded mariculture industry.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Combined effects of older age and HIV disease on changes in everyday functioning over one year - Jennifer L. Thompson; Steven Paul Woods; Luis D. Medina; Troy A. Webber (Journal of NeuroVirology, 2022)

Less than six generations to save the chacoan peccary - Micaela Camino; Jeffrey Thompson; Pablo Arriaga Velasco-Aceves; Sebastián Cirignoli; Riccardo Tiddi; Sara Cortez; Silvia D. Matteucci; Mariana Altrichter (Biodiversity and Conservation, 2022)

Genomic characterization of grapevine viruses N and O: novel vitiviruses from South Africa - David A. Read; Genevieve D. Thompson; Nathan Le Cordeur; Dirk Swanevelder; Gerhard Pietersen (Archives of Virology, 2022)

Birds of a Feather Eat Plastic Together: High Levels of Plastic Ingestion in Great Shearwater Adults and Juveniles Across Their Annual Migratory Cycle - Anna R. Robuck; Christine A. Hudak; Lindsay Agvent; Gwenyth Emery; Peter G. Ryan; Vonica Perold; Kevin D. Powers; Johanna Pedersen; Michael A. Thompson; Justin J. Suca; Michael J. Moore; Craig A. Harms; et al. (Frontiers in Marine Science, 2022)
Limited work to date has examined plastic ingestion in highly migratory seabirds like Great Shearwaters ( Ardenna gravis ) across their entire migratory range. We examined 217 Great Shearwaters obtained from 2008–2019 at multiple locations spanning their yearly migration cycle across the Northwest and South Atlantic to assess accumulation of ingested plastic as well as trends over time and between locations. A total of 2328 plastic fragments were documented in the ventriculus portion of the gastrointestinal tract, with an average of 9 plastic fragments per bird. The mass, count, and frequency of plastic occurrence (FO) varied by location, with higher plastic burdens but lower FO in South Atlantic adults and chicks from the breeding colonies. No fragments of the same size or morphology were found in the primary forage fish prey, the Sand Lance ( Ammodytes spp., n = 202) that supports Great Shearwaters in Massachusetts Bay, United States, suggesting the birds directly ingest the bulk of their plastic loads rather than accumulating via trophic transfer. Fourier-transform infrared spectroscopy indicated that low- and high-density polyethylene were the most common polymers ingested, within all years and locations. Individuals from the South Atlantic contained a higher proportion of larger plastic items and fragments compared to analogous life stages in the NW Atlantic, possibly due to increased use of remote, pelagic areas subject to reduced inputs of smaller, more diverse, and potentially less buoyant plastics found adjacent to coastal margins. Different signatures of polymer type, size, and category between similar life stages at different locations suggests rapid turnover of ingested plastics commensurate with migratory stage and location, though more empirical evidence is needed to ground-truth this hypothesis. This work is the first to comprehensively measure the accumulation of ingested plastics by Great Shearwaters over the last decade and across multiple locations spanning their yearly trans-equatorial migration cycle and underscores their utility as sentinels of plastic pollution in Atlantic ecosystems.

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

Spatiotemporal variation in harbor porpoise distribution and foraging across a landscape of fear - Laura D. Williamson; Beth E. Scott; Megan R. Laxton; Fabian E. Bachl; Janine B. Illian; Kate L. Brookes; Paul M. Thompson (Marine Mammal Science, 2022)
Understanding spatiotemporally varying animal distributions can inform ecological understanding of species' behavior (e.g., foraging and predator/prey interactions) and support development of management and conservation measures. Data from an array of echolocation‐click detectors (C‐PODs) were analyzed using Bayesian spatiotemporal modeling to investigate spatial and temporal variation in occurrence and foraging activity of harbor porpoises ( Phocoena phocoena ) and how this variation was influenced by daylight and presence of bottlenose dolphins ( Tursiops truncatus ). The probability of occurrence of porpoises was highest on an offshore sandbank, where the proportion of detections with foraging clicks was relatively low. The porpoises' overall distribution shifted throughout the summer and autumn, likely influenced by seasonal prey availability. Probability of porpoise occurrence was lowest in areas close to the coast, where dolphin detections were highest and declined prior to dolphin detection, leading potentially to avoidance of spatiotemporal overlap between porpoises and dolphins. Increased understanding of porpoises' seasonal distribution, key foraging areas, and their relationship with competitors can shed light on management options and potential interactions with offshore industries.

Understanding the farm data lifecycle: collection, use, and impact of farm data on U.S. commercial corn and soybean farms - Nathanael M. Thompson; Nathan D. DeLay; James R. Mintert (Precision Agriculture, 2021)
Enthusiasm regarding the “digital agriculture” revolution is widespread, yet objective research on how commercial farms actually use data and data services remains limited. The purpose of this research is to better understand the current positioning of U.S. commercial corn and soybean farms within the farm data lifecycle, including the collection, use, and impact of farm data. Using survey data from a sample of 800 commercial-scale U.S. corn and soybean farms, the factors associated with progression within the farm data lifecycle are examined. Results indicate that the majority of commercial U.S. corn and soybean farms collect data, indicate that the data they collect influences their decisions, and perceive positive yield benefits as a result of their data-informed decisions. However, farms vary in intensity of their data usage. Investments in data management and analysis resources are associated with progression within the farm data lifecycle. These investments comprise software products that manage and analyze data, including creating GPS maps, layering different data sources, and generating recommendations. Investments in human capital, either in on-farm employees with designated data responsibilities or in trusted off-farm service providers, are also associated with progression within the farm data lifecycle. Farms that have not yet invested in these types of data management and data analysis resources may be forfeiting the potential benefits associated with using their farm’s data to improve on-farm decision making.

Detection and diversity of grapevine virus L from a Vitis cultivar collection in Stellenbosch, South Africa - David A. Read; Genevieve D. Thompson; Dirk Swanevelder; Gerhard Pietersen (European Journal of Plant Pathology, 2021)

Estimating Facet Joint Apposition with Specimen-Specific Computer Models of Subaxial Cervical Spine Kinematics - Ryan D. Quarrington; Darcy W. Thompson-Bagshaw; Claire F. Jones (Annals of Biomedical Engineering, 2021)

Efficacy of heat‐killed and formalin‐killed vaccines against Tilapia tilapinevirus in juvenile Nile tilapia ( Oreochromis niloticus ) - Thao Thu Mai; Pattanapon Kayansamruaj; Suwimon Taengphu; Saengchan Senapin; Janina Z. Costa; Jorge del‐Pozo; Kim D. Thompson; Channarong Rodkhum; Ha Thanh Dong (Journal of Fish Diseases, 2021)
Tilapia tilapinevirus (also known as tilapia lake virus, TiLV) is considered to be a new threat to the global tilapia industry. The objective of this study was to develop simple cell culture‐based heat‐killed (HKV) and formalin‐killed (FKV) vaccines for the prevention of disease caused by TiLV. The fish were immunized with 100 µl of either HKV or FKV by intraperitoneal injection with each vaccine containing 1.8 × 10 6 TCID 50‐ inactivated virus. A booster vaccination was carried out at 21‐day post‐vaccination (dpv) using the same protocol. The fish were then challenged with a lethal dose of TiLV at 28 dpv. The expression of five immune genes ( IgM , IgD , IgT , CD4 and CD8 ) in the head kidney and spleen of experimental fish was assessed at 14 and 21 dpv and again after the booster vaccination at 28 dpv. TiLV‐specific IgM responses were measured by ELISA at the same time points. The results showed that both vaccines conferred significant protection, with relative percentage survival of 71.3% and 79.6% for HKV and FKV, respectively. Significant up‐regulation of IgM and IgT was observed in the head kidney of fish vaccinated with HKV at 21 dpv, while IgM , IgD and CD4 expression increased in the head kidney of fish receiving FKV at the same time point. After booster vaccination, IgT and CD8 transcripts were significantly increased in the spleen of fish vaccinated with the HKV, but not with FKV. Both vaccines induced a specific IgM response in both serum and mucus. In summary, this study showed that both HKV and FKV are promising injectable vaccines for the prevention of disease caused by TiLV in Nile tilapia.

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Ecological niche differentiation among six annual Lythrum species in Mediterranean temporary pools - Antoine Gazaix; Patrick Grillas; Guillaume Papuga; Hugo Fontes; Florent Sabatier; Virginie Pons; Perrine Gauthier; John D. Thompson (Oecologia, 2021)

High-pressure crystal structure and equation of state of ferromagnesian jeffbenite: implications for stability in the transition zone and uppermost lower mantle - Fei Wang; Elizabeth C. Thompson; Dongzhou Zhang; Ercan E. Alp; Jiyong Zhao; Joseph R. Smyth; Steven D. Jacobsen (Contributions to Mineralogy and Petrology, 2021)

Proteomic characterization of serum proteins from Atlantic salmon ( Salmo salar L.) from an outbreak with cardiomyopathy syndrome - Janina Z. Costa; Jorge del Pozo; Kevin McLean; Neil Inglis; Philippe Sourd; Andrei Bordeianu; Kim D. Thompson (Journal of Fish Diseases, 2021)
Cardiomyopathy syndrome (CMS), caused by piscine myocarditis virus (PMCV), is a serious challenge to Atlantic salmon ( Salmo salar L.) aquaculture. Regrettably, husbandry techniques are the only tool to manage CMS outbreaks, and no prophylactic measures are available at present. Early diagnosis of CMS is therefore desirable, preferably with non‐lethal diagnostic methods, such as serum biomarkers. To identify candidate biomarkers for CMS, the protein content of pools of sera (4 fish/pool) from salmon with a CMS outbreak (3 pools) and from clinically healthy salmon (3 pools) was compared using liquid chromatography–electrospray ionization–tandem mass spectrometry (LC‐ESI‐MS/MS). Overall, seven proteins were uniquely identified in the sera of clinically healthy fish, while 27 proteins were unique to the sera of CMS fish. Of the latter, 24 have been associated with cardiac disease in humans. These were grouped as leakage enzymes (creatine kinase, lactate dehydrogenase, glycogen phosphorylase and carbonic anhydrase); host reaction proteins (acute‐phase response proteins—haptoglobin, fibrinogen, α2‐macroglobulin and ceruloplasmin; and complement‐related proteins); and regeneration/remodelling proteins (fibronectin, lumican and retinol). Clinical evaluation of the suitability of these proteins as biomarkers of CMS, either individually or as part of a panel, is a logical next step for the development of early diagnostic tools for CMS.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Novel viruses associated with plants of the family Amaryllidaceae in South Africa - David A. Read; Ronel Roberts; Dirk Swanevelder; Gerhard Pietersen; Genevieve D. Thompson (Archives of Virology, 2021)

Cystic fibrosis improves COVID-19 survival and provides clues for treatment of SARS-CoV-2 - Edward H. Abraham; Guido Guidotti; Eliezer Rapaport; David Bower; Jack Brown; Robert J. Griffin; Andrew Donnelly; Ellen D. Waitzkin; Kenon Qamar; Mark A. Thompson; Sukumar Ethirajan; Kent Robinson (Purinergic Signalling, 2021)
Systemic pools of ATP are elevated in individuals homozygous for cystic fibrosis (CF) as evidenced by elevated blood and plasma ATP levels. This elevated ATP level seems to provide benefit in the presence of advanced solid tumors (Abraham et al., Nature Medicine 2(5):593–596, 1996). We published in this journal a paper showing that IV ATP can elevate the depleted ATP pools of advanced cancer patients up to levels found in CF patients with subsequent clinical, biochemical, and quality of life (QOL) improvements (Rapaport et al., Purinergic Signalling 11(2): 251–262, 2015). We hypothesize that the elevated ATP levels seen in CF patients may be benefiting CF patients in another way: by improving their survival after contracting COVID-19. We discuss here the reasoning behind this hypothesis and suggest how these findings might be applied clinically in the general population.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Pancreatic cancer pathology viewed in the light of evolution - Michaël Noë; Seung-Mo Hong; Laura D. Wood; Elizabeth D. Thompson; Nicholas J. Roberts; Michael G. Goggins; Alison P. Klein; James R. Eshleman; Scott E. Kern; Ralph H. Hruban (Cancer and Metastasis Reviews, 2021)
One way to understand ductal adenocarcinoma of the pancreas (pancreatic cancer) is to view it as unimaginably large numbers of evolving living organisms interacting with their environment. This “evolutionary view” creates both expected and surprising perspectives in all stages of neoplastic progression. Advances in the field will require greater attention to this critical evolutionary prospective.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Genome sequence of Vibrio fluvialis 362.3 isolated from coral Mussismilia braziliensis reveals genes related to marine environment adaptation - Livia M. R. Vidal; Aline R. P. Gonçalves; Tainá M. Venas; Gizele D. Garcia; Diogo A. Tschoeke; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2021)

Challenging the Need for Deep Seabed Mining From the Perspective of Metal Demand, Biodiversity, Ecosystems Services, and Benefit Sharing - K. A. Miller; K. Brigden; D. Santillo; D. Currie; P. Johnston; K. F. Thompson (Frontiers in Marine Science, 2021)
The extraction of minerals from the seabed of the deep oceans is of increasing interest to investors, mining companies and some coastal states. To date, no commercial-scale deep seabed mining has taken place but there is considerable pressure for minerals mining to become an economic reality, including to supply the projected demand for metals to support a global transition to renewable energy. At the same time, the full environmental impacts of deep seabed mining are difficult to predict but are expected to be highly damaging, both within, and perhaps well beyond, the areas mined. Here, we reflect on the considerable uncertainties that exist in relation to deep seabed mining. In particular, we provide a perspective on: (1) arguments that deep seabed mining is needed to supply minerals for the green energy revolution, using the electric vehicle battery industry as an illustration; (2) risks to biodiversity, ecosystem function and related ecosystem services; and (3) the lack of equitable benefit sharing to the global community now and for future generations. We explore the justification for a global moratorium on deep seabed mining to ensure protection of marine ecosystems, the need to focus on baseline research, and how improved governance of targeted marine regions could be key to the preservation and conservation of the ocean biome.

Broad-Scale Responses of Harbor Porpoises to Pile-Driving and Vessel Activities During Offshore Windfarm Construction - Aude Benhemma-Le Gall; Isla M. Graham; Nathan D. Merchant; Paul M. Thompson (Frontiers in Marine Science, 2021)
Offshore windfarm developments are expanding, requiring assessment and mitigation of impacts on protected species. Typically, assessments of impacts on marine mammals have focused on pile-driving, as intense impulsive noise elicits adverse behavioral responses. However, other construction activities such as jacket and turbine installation also change acoustic habitats through increased vessel activity. To date, the contribution of construction-related vessel activity in shaping marine mammal behavioral responses at windfarm construction sites has been overlooked and no guidelines or mitigation measures have been implemented. We compared broad-scale spatio-temporal variation in harbor porpoise occurrence and foraging activity between baseline periods and different construction phases at two Scottish offshore windfarms. Following a Before-After Control-Impact design, arrays of echolocation click detectors (CPODs) were deployed in 25 km by 25 km impact and reference blocks throughout the 2017–2019 construction. Echolocation clicks and buzzes were used to investigate porpoise occurrence and foraging activity, respectively. In parallel, we characterized broadband noise levels using calibrated noise recorders (SoundTraps and SM2Ms) and vessel activities using AIS data integrated with engineering records. Following an impact gradient design, we then quantified the magnitude of porpoise responses in relation to changes in the acoustic environment and vessel activity. Compared to baseline, an 8–17% decline in porpoise occurrence was observed in the impact block during pile-driving and other construction activities. The probability of detecting porpoises and buzzing activity was positively related to the distance from vessel and construction activities, and negatively related to levels of vessel intensity and background noise. Porpoise displacement was observed at up to 12 km from pile-driving activities and up to 4 km from construction vessels. This evidence of broad-scale behavioral responses of harbor porpoises to these different construction activities highlights the importance of assessing and managing all vessel activities at offshore windfarm sites to minimize potential impacts of anthropogenic noise.

Spatial Variation in Pelagic Wildlife Assemblages in the Ascension Island Marine Protected Area: Implications for Monitoring and Management - Christopher D. H. Thompson; Jessica J. Meeuwig; Judith Brown; Andrew J. Richardson; Alan M. Friedlander; Peter I. Miller; Sam B. Weber (Frontiers in Marine Science, 2021)
Bathymetric features such as islands and seamounts, as well as dynamic ocean features such as fronts often harbour rich marine communities. We deployed mid-water baited remote underwater video systems on three expeditions in Ascension Island’s Exclusive Economic Zone (EEZ), surveying the waters associated with six different bathymetric and dynamic ocean features: Ascension Island, two shallow seamounts (summits ≤ 101 m), one deeper seamount (summit > 250 m), apparent fronts, and haphazardly sampled open ocean areas. At Ascension Island, the pelagic assemblage consisted of a moderate proportion of predators and a diverse range of other taxa, including turtles, dolphins, and large non-piscivores. At the two shallow seamounts, sharks, tunas, billfish, and other large pelagic predators formed the vast majority of the assemblage, contributing > 99.9% of biomass and > 86% of abundance. At the deeper seamount, the pelagic community was comparatively depauperate, however the functional composition of its assemblage indicated some similarities to the shallow seamounts. Apparent fronts did not significantly differ from random offshore sites for metrics such as total abundance and taxonomic richness. However, they harboured assemblages with more abundant sharks, tunas, and large piscivores than random ocean open locations and these differences may be driven by certain front-associated species. Our results illustrate that pelagic assemblages vary markedly among different physical and oceanographic features and that seamounts appear particularly important for pelagic predators. The diversity and abundance of the assemblage, as well as the threatened status of many of the species observed, serve to highlight the conservation value of the Ascension Island EEZ. Our results also provide important baseline information of pelagic wildlife assemblages against which the performance of the recently implemented Ascension Island Marine Protected Area can be evaluated.

Pathogen infection influences a distinct microbial community composition in sorghum RILs - K. Masenya; G. D. Thompson; M. Tekere; T. P. Makhalanyane; R. E. Pierneef; D. J. G. Rees (Plant and Soil, 2021)
Aims The rhizosphere microbiome substantially affects plant health, yet comparatively little is known regarding the foliar community dynamics. Here, we examine the relationship between the microbiota and their response to natural infection by pathogens. Methods We established an experimental system using a set of sorghum recombinant inbred lines (RILS). These RILS included four models denoted as resistant, moderately resistant, susceptible and highly susceptible. A combination of 16S rRNA and ITS gene amplicon approaches was used to assess bacteria and fungi, respectively, in foliar samples. Results We show that the foliar microbiome differs substantially in asymptomatic and symptomatic RILs subsequent to natural infection by pathogens. A significant association was found between plant health and microbial community structure. Our analyses revealed several distinct fungal and bacterial pathogens. These pathogens included Gibberella and Pantoea genera, which were associated with the highly susceptible group. In addition to these pathogens, we also found signatures for Ascochyta , a known plant pathogenic genus. Members of the bacterial genus Methylorubrum and the fungal genus Hannaella, both known to exhibit plant growth-promoting (PGP) traits, were associated with the resistant and moderately resistant groups. These data also reveal numerous highly diverse fungal and bacterial taxa in RILs that did not show symptoms. We also found taxonomic differences between the microbiota hosted by the symptomatic and asymptomatic RILs. Conclusions Together, these data suggest that pathogen infection may result in distinct microbiota. These results suggest that highly diverse microbiome may promote the plants ability to resist the effects of pathogens potentially contributing to plant health.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Development and evaluation of colloidal gold immunochromatography test strip for rapid diagnosis of nervous necrosis virus in golden grey mullet ( Chelon aurata ) - Fatemeh Hassantabar; Mohammad J. Zorriehzahra; Farid Firouzbakhsh; Kim D. Thompson (Journal of Fish Diseases, 2021)
A lateral flow immunochromatography strip test, based on antibody–gold nanoparticles specific for nervous necrosis virus (NNV), was developed for rapid, on‐site detection of the virus in fish stocks. A monoclonal antibody against NNV was conjugated with colloidal gold as the detector antibody. A rabbit anti‐NNV polyclonal antibody and goat anti‐mouse IgG antibody were blotted onto the nitrocellulose membrane as the capture antibodies on the test line and control line, respectively. The reaction could be seen by the eye within 15 min and did not cross‐react with the other viruses tested. The detection limit of the strip was approximately 10 3 TCID 50 /ml and had good stability after storage at 4°C for 8 months. When brains of 70 naturally infected golden grey mullet, Chelon aurata , were tested with the strip test, the diagnostic specificity and sensitivity of the test compared to real‐time RT‐PCR were 100% and 74%, respectively. Therefore, the one‐step test strip developed here had high specificity, reproducibility, and stability. This, together with its simplicity to use and rapid detection, without the requirement of sophisticated equipment or specialized skills, makes the strip suitable for pond‐side detection of NNV in farmed fish.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

First report of Catharanthus mosaic virus infecting Gomphocarpus physocarpus in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (Journal of Plant Pathology, 2021)

Orchid fleck virus and a novel strain of sweet potato chlorotic stunt virus associated with an ornamental cultivar of Alcea rosea L. in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (European Journal of Plant Pathology, 2021)

Resource selection and movement by northern bobwhite broods varies with age and explains survival - Emily A. Sinnott; Mitch D. Weegman; Thomas R. Thompson; Frank R. Thompson (Oecologia, 2021)

Complex hydroperiod induced carryover responses for survival, growth, and endurance of a pond-breeding amphibian - Cassandra M. Thompson; Viorel D. Popescu (Oecologia, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

Toward a global and reproducible science for brain imaging in neurotrauma: the ENIGMA adult moderate/severe traumatic brain injury working group - Alexander Olsen; Talin Babikian; Erin D. Bigler; Karen Caeyenberghs; Virginia Conde; Kristen Dams-O’Connor; Ekaterina Dobryakova; Helen Genova; Jordan Grafman; Asta K. Håberg; Ingrid Heggland; Torgeir Hellstrøm; et al. (Brain Imaging and Behavior, 2021)
The global burden of mortality and morbidity caused by traumatic brain injury (TBI) is significant, and the heterogeneity of TBI patients and the relatively small sample sizes of most current neuroimaging studies is a major challenge for scientific advances and clinical translation. The ENIGMA (Enhancing NeuroImaging Genetics through Meta-Analysis) Adult moderate/severe TBI (AMS-TBI) working group aims to be a driving force for new discoveries in AMS-TBI by providing researchers world-wide with an effective framework and platform for large-scale cross-border collaboration and data sharing. Based on the principles of transparency, rigor, reproducibility and collaboration, we will facilitate the development and dissemination of multiscale and big data analysis pipelines for harmonized analyses in AMS-TBI using structural and functional neuroimaging in combination with non-imaging biomarkers, genetics, as well as clinical and behavioral measures. Ultimately, we will offer investigators an unprecedented opportunity to test important hypotheses about recovery and morbidity in AMS-TBI by taking advantage of our robust methods for large-scale neuroimaging data analysis. In this consensus statement we outline the working group’s short-term, intermediate, and long-term goals.

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Climate‐related geographical variation in performance traits across the invasion front of a widespread non‐native insect - Lily M. Thompson; Sean D. Powers; Ashley Appolon; Petra Hafker; Lelia Milner; Dylan Parry; Salvatore J. Agosta; Kristine L. Grayson (Journal of Biogeography, 2021)
Aim Invasive species are ideal systems for testing geographical differences in performance traits and measuring evolutionary responses as a species spreads across divergent climates and habitats. The European gypsy moth, Lymantria dispar dispar L. (Lepidoptera: Erebidae), is a generalist forest defoliator introduced to Medford, Massachusetts, USA in 1869. The invasion front extends from Minnesota to North Carolina and the ability of this species to adapt to local climate may contribute to its continuing spread. We evaluated the performance of populations along the climatic gradient of the invasion front to test for a relationship between climate and ecologically important performance traits. Location Eastern United States of America Taxon Lymantria dispar dispar L. (Lepidoptera: Erebidae) Methods Insects from 14 populations across the US invasion front and interior of the invasive range were reared from hatch to adult emergence in six constant temperature treatments. The responses of survival, pupal mass and larval development time were analysed as a function of source climate (annual mean normal temperature), rearing temperature and their interaction using multiple polynomial regression. Results With the exception of female development time, there were no significant interactions between source climate and rearing temperature, indicating little divergence in the shape of thermal reaction norms among populations. Source population and rearing temperature were significant predictors of survival and pupal mass. Independent of rearing temperature, populations from warmer climates had lower survival than those from colder climates, but attained larger body size despite similar development times. Larval development time was dependent on rearing temperature, but there were not consistent relationships with source climate. Main Conclusions Thermal adaptation can be an important factor shaping the spread of invasive species, particularly in the context of climate change. Our results suggest that L. d. dispar is highly plastic, but has undergone climate‐related adaptation in thermal performance and life‐history traits as it spread across North America.

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Cephalopods habitat and trophic ecology: historical data using snares penguin as biological sampler - H. R. Guímaro; D. R. Thompson; V. H. Paiva; F. R. Ceia; D. M. Cunningham; P. J. Moors; J. C. Xavier (Polar Biology, 2021)

Effects of environmental heterogeneity on phenotypic variation of the endemic plant Lilium pomponium in the Maritime and Ligurian Alps - Carmelo Macrì; Davide Dagnino; Maria Guerrina; Frédéric Médail; Luigi Minuto; John D. Thompson; Gabriele Casazza (Oecologia, 2021)
Geographical limits of species’ distributions are assumed to be coincident with ecological margins, although this assumption might not always be true. Indeed, harsh environments such as Alpine and Mediterranean ecosystems may favour high phenotypic variability among populations, especially those in peripheral sites. Floral traits are often found to be less variable and less affected by environmental heterogeneity than vegetative traits because variation in the former may have negative effects on fitness. For this reason, it is important to quantify variation in floral traits and plant fecundity in study range limits. The objective of the study is to examine phenotypic variation and differences in reproduction in endemic Lilium pomponium in the Maritime and Ligurian Alps in relation to environmental variation across its distribution range. In this species, marginal climatic populations occur both in the peripheral and central geographical locations of the distribution range; hence, geographical and ecological gradients are not concordant. Floral trait variation is related to local environmental conditions with an array of interactions among resource availability, potential pollen limitation and population size that are differentially related to floral traits. Contrary to the general expectation, all central and peripheral populations had similar, moderate seed production with each group limited by different factors acting on different stages of the life-history strategy. Our results are in line with the idea that general expectations are confirmed only when its assumptions are met and that the differences in pollination environment along an environmental gradient may not be the main determinant of the distribution limit.

Vibrio tetraodonis sp. nov.: genomic insights on the secondary metabolites repertoire - Gustavo P. R. Azevedo; Hannah K. Mattsson; Grasiele R. Lopes; Livia Vidal; Mariana Campeão; Luciane A. Chimetto Tonon; Gizele D. Garcia; Diogo A. Tschoeke; Bruno S. Silva; Koko Otsuki; Bruno Gomez-Gil; Jean Swings; et al. (Archives of Microbiology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Magnesium biofortification of Italian ryegrass (Lolium multiflorum L.) via agronomy and breeding as a potential way to reduce grass tetany in grazing ruminants - Diriba B. Kumssa; J. Alan Lovatt; Neil S. Graham; Sarah Palmer; Rory Hayden; Lolita Wilson; Scott D. Young; R. Murray Lark; Beth Penrose; E. Louise Ander; Russell Thompson; Lin-Xi Jiang; et al. (Plant and Soil, 2020)
Aim Magnesium (Mg) deficiency (known as grass tetany) is a serious metabolic disorder that affects grazing ruminants. We tested whether Mg-fertiliser can increase Mg concentration of Italian ryegrasses ( Lolium multiflorum L.) including a cultivar (cv. Bb2067; ‘Magnet’), bred to accumulate larger concentrations of Mg. Methods Under controlled environment (CE) conditions, three cultivars (cv. Bb2067, cv. Bb2068, cv. RvP) were grown in low-nutrient compost at six fertiliser rates (0–1500 μM MgCl 2 .6H 2 O). Under field conditions, the three cultivars in the CE condition and cv. Alamo were grown at two sites, and four rates of MgSO 4 fertiliser application rates (0–200 kg ha −1 MgO). Multiple grass cuts were taken over two-years. Results Grass Mg concentration increased with increasing Mg-fertiliser application rates in all cultivars and conditions. Under field conditions, cv. Bb2067 had 11–73% greater grass Mg concentration and smaller forage tetany index (FTI) than other cultivars across the Mg-fertiliser application rates, sites and cuts. Grass dry matter (DM) yield of cv. Bb2067 was significantly ( p < 0.05) smaller than cv. Alamo. The effect of Mg-fertiliser rate on DM yield was not significant ( p ≥ 0.05). Conclusions Biofortification of grass with Mg through breeding and agronomy can improve the forage Mg concentration for grazing ruminants, even in high-growth spring grass conditions when hypomagnesaemia is most prevalent. Response to agronomic biofortification varied with cultivar, Mg-fertiliser rate, site and weather. The cost:benefit of these approaches and farmer acceptability, and the impact on cattle and sheep grazing on grasses biofortified with Mg requires further investigation.

Assessment of Nitrogen Fixation by Mungbean Genotypes in Different Soil Textures Using 15N Natural Abundance Method - Andre A. Diatta; Wade E. Thomason; Ozzie Abaye; Thomas L. Thompson; Martin L. Battaglia; Larry J. Vaughan; Mamadou Lo; Jose F. D. C. L. Filho (Journal of Soil Science and Plant Nutrition, 2020)

Seasonal variation in the lipid profile of Acropora millepora at Halfway Island, Great Barrier Reef - J. A. Conlan; L. K. Bay; A. Jones; A. Thompson; D. S. Francis (Coral Reefs, 2020)

A Review of Overlapping Landscapes: Pseudoreplication or a Red Herring in Landscape Ecology? - Benjamin Zuckerberg; Jeremy M. Cohen; Laura A. Nunes; Jacy Bernath-Plaisted; John D. J. Clare; Neil A. Gilbert; Sofia S. Kozidis; Scott B. Maresh Nelson; Amy A. Shipley; Kimberly L. Thompson; André Desrochers (Current Landscape Ecology Reports, 2020)

A synoptic climatology of potential seiche‐inducing winds in a large intermontane lake: Quesnel Lake, British Columbia, Canada - Hadleigh D. Thompson; Stephen J. Déry; Peter L. Jackson; Bernard E. Laval (International Journal of Climatology, 2020)
Excitation of basin‐scale, internal waves (i.e., internal seiches) in lakes require spatially homogeneous wind fields that vary on time scales comparable to the seiche period, which can be on the order of several days in large lakes. We evaluate 2 years (October 1, 2016 to September 30, 2018) of 15‐min wind data from a shore‐based meteorological station to identify strong wind episodes likely to excite internal seiches in a large and geometrically complex lake surrounded by convoluted topography, Quesnel Lake, British Columbia, Canada. Our findings include the identification of strong wind event seasonality, with peak mean monthly wind speeds in April and November, and minimum mean monthly wind speeds in August. Using geopotential heights (GPHs) from 1.5° × 1.5° gridded reanalysis data to reconstruct the atmospheric state for each strong wind episode, two primary synoptic patterns are identified that, in conjunction with local topographic channelling, lead to either easterlies or westerlies occurring at our sampling station, with strong easterly episodes three times more frequent than westerly episodes. This highlights the important role that developing low‐pressure systems in the Northeastern Pacific Basin have in setting up the GPH gradient required for persistent strong winds at Quesnel Lake, in the hours and days before these storms make landfall. The projection of synoptic patterns of strong wind events onto a 4 × 3 self‐organizing map clustered strong wind events by mean wind direction, similar to the results of a manual classification. Methods to identify the strong wind episodes and the resulting self‐organizing map are both evaluated in‐part by two case studies where strong winds are known to have excited a basin‐scale baroclinic response in Quesnel Lake.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Mild acidity likely accelerates the physiological matriptase autoactivation process: a comparative study between spontaneous and acid-induced matriptase zymogen activation - Bailing Jia; Hamishi A. Thompson; Robert B. Barndt; Yi-Lin Chiu; Mon-Juan Lee; See-Chi Lee; Jehng-Kang Wang; Hung-Jen Tang; Chen-Yong Lin; Michael D. Johnson (Human Cell, 2020)

Rapid screening of marine bacterial symbionts using MALDI-TOF MS - Livia M. R. Vidal; Tainá M. Venas; Aline R. P. Gonçalves; Hannah K. Mattsson; Raphael V. P. Silva; Maria S. Nóbrega; Gustavo P. R. Azevedo; Gizele D. Garcia; Diogo A. Tschoeke; Verônica V. Vieira; Fabiano L. Thompson; Cristiane C. Thompson (Archives of Microbiology, 2020)

A Brief Observation of Endangered Coquerel’s Sifaka (Propithecus coquereli) Feeding on Red Mangrove (Rhizophora mucronata) Vegetation in a Mangrove Environment, Northwest Madagascar - C. Chell; M. E. Corral; I. Grant; C. J. Laskai; H. Gough; S. D. Rakotomalala; S. J. Ward; C. Thompson (International Journal of Primatology, 2020)

Localisation of antigens in the gut post-challenge with Streptococcus iniae in vaccinated and non-vaccinated red hybrid tilapia (Oreochromis sp.) - M. Hayat; M. Y. Sabri; A. R. Intan-Shameha; M. Y. Ina-Salwany; Kim D. Thompson (Aquaculture International, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Differential responses of heather and red grouse to long-term spatio-temporal variation in sheep grazing - Sonja C. Ludwig; Nicholas J. Aebischer; Michael Richardson; Staffan Roos; Des B. A. Thompson; Jeremy D. Wilson; David Baines (Biodiversity and Conservation, 2020)

Clinging on to alpine life: Investigating factors driving the uphill range contraction and population decline of a mountain breeding bird - Steven R. Ewing; Alistair Baxter; Jeremy D. Wilson; Daniel B. Hayhow; James Gordon; Des B. A. Thompson; D. Philip Whitfield; René van der Wal (Global Change Biology, 2020)
Climate change and anthropogenic nitrogen deposition are widely regarded as important drivers of environmental change in alpine habitats. However, due to the difficulties working in high‐elevation mountain systems, the impacts of these drivers on alpine breeding species have rarely been investigated. The Eurasian dotterel ( Charadrius morinellus ) is a migratory wader, which has been the subject of uniquely long‐term and spatially widespread monitoring effort in Scotland, where it breeds in alpine areas in dwindling numbers. Here we analyse data sets spanning three decades, to investigate whether key potential drivers of environmental change in Scottish mountains (snow lie, elevated summer temperatures and nitrogen deposition) have contributed to the population decline of dotterel. We also consider the role of rainfall on the species' wintering grounds in North Africa. We found that dotterel declines—in both density and site occupancy of breeding males—primarily occurred on low and intermediate elevation sites. High‐elevation sites mostly continued to be occupied, but males occurred at lower densities in years following snow‐rich winters, suggesting that high‐elevation snow cover displaced dotterel to lower sites. Wintering ground rainfall was positively associated with densities of breeding males two springs later. Dotterel densities were reduced at low and intermediate sites where nitrogen deposition was greatest, but not at high‐elevation sites. While climatic factors explained variation in breeding density between years, they did not seem to explain the species' uphill retreat and decline. We cannot rule out the possibility that dotterel have increasingly settled on higher sites previously unavailable due to extensive snow cover, while changes associated with nitrogen deposition may also have rendered lower lying sites less suitable for breeding. Causes of population and range changes in mountain‐breeding species are thus liable to be complex, involving multiple anthropogenic drivers of environmental change acting widely across annual and migratory life cycles.

A large population-based investigation into the genetics of susceptibility to gastrointestinal infections and the link between gastrointestinal infections and mental illness - Ron Nudel; Vivek Appadurai; Andrew J. Schork; Alfonso Buil; Jonas Bybjerg-Grauholm; Anders D. Børglum; Mark J. Daly; Ole Mors; David M. Hougaard; Preben Bo Mortensen; Thomas Werge; Merete Nordentoft; et al. (Human Genetics, 2020)
Gastrointestinal infections can be life threatening, but not much is known about the host’s genetic contribution to susceptibility to gastrointestinal infections or the latter’s association with psychiatric disorders. We utilized iPSYCH, a genotyped population-based sample of individuals born between 1981 and 2005 comprising 65,534 unrelated Danish individuals (45,889 diagnosed with mental disorders and 19,645 controls from a random population sample) in which all individuals were linked utilizing nationwide population-based registers to estimate the genetic contribution to susceptibility to gastrointestinal infections, identify genetic variants associated with gastrointestinal infections, and examine the link between gastrointestinal infections and psychiatric and neurodevelopmental disorders. The SNP heritability of susceptibility to gastrointestinal infections ranged from 3.7% to 6.4% on the liability scale. Significant correlations were found between gastrointestinal infections and the combined group of mental disorders (OR = 2.09; 95% CI: 1.82–2.4, P = 1.87 × 10 –25 ). Correlations with autism spectrum disorder, attention deficit hyperactivity disorder, and depression were also significant. We identified a genome-wide significant locus associated with susceptibility to gastrointestinal infections (OR = 1.13; 95% CI: 1.08–1.18, P = 2.9 × 10 –8 ), where the top SNP was an eQTL for the ABO gene. The risk allele was associated with reduced ABO expression, providing, for the first time, genetic evidence to support previous studies linking the O blood group to gastrointestinal infections. This study also highlights the importance of integrative work in genetics, psychiatry, infection, and epidemiology on the road to translational medicine.

Weather underground: Subsurface hydrologic processes mediate tree vulnerability to extreme climatic drought - Blair C. McLaughlin; Rachel Blakey; Andrew P. Weitz; Xue Feng; Brittni J. Brown; David D. Ackerly; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2020)
Drought extent and severity have increased and are predicted to continue to increase in many parts of the world. Understanding tree vulnerability to drought at both individual and species levels is key to ongoing forest management and preparation for future transitions in community composition. The influence of subsurface hydrologic processes is particularly important in water‐limited ecosystems, and is an under‐studied aspect of tree drought vulnerability. With California's 2013–2016 extraordinary drought as a natural experiment, we studied four co‐occurring woodland tree species, blue oak ( Quercus douglasii ), valley oak ( Quercus lobata ), gray pine ( Pinus sabiniana ), and California juniper ( Juniperus californica ), examining drought vulnerability as a function of climate, lithology and hydrology using regional aerial dieback surveys and site‐scale field surveys. We found that in addition to climatic drought severity (i.e., rainfall), subsurface processes explained variation in drought vulnerability within and across species at both scales. Regionally for blue oak, severity of dieback was related to the bedrock lithology, with higher mortality on igneous and metamorphic substrates, and to regional reductions in groundwater. At the site scale, access to deep subsurface water, evidenced by stem water stable isotope composition, was related to canopy condition across all species. Along hillslope gradients, channel locations supported similar environments in terms of water stress across a wide climatic gradient, indicating that subsurface hydrology mediates species’ experience of drought, and that areas associated with persistent access to subsurface hydrologic resources may provide important refugia at species’ xeric range edges. Despite this persistent overall influence of the subsurface environment, individual species showed markedly different response patterns. We argue that hydrologic niche segregation can be a useful lens through which to interpret these differences in vulnerability to climatic drought and climate change.

Rapid recovery of ecosystem function following extreme drought in a South African savanna grassland - Kevin R. Wilcox; Sally E. Koerner; David L. Hoover; Andrea K. Borkenhagen; Deron E. Burkepile; Scott L. Collins; Ava M. Hoffman; Kevin P. Kirkman; Alan K. Knapp; Tercia Strydom; Dave I. Thompson; Melinda D. Smith (Ecology, 2020)
Climatic extremes, such as severe drought, are expected to increase in frequency and magnitude with climate change. Thus, identifying mechanisms of resilience is critical to predicting the vulnerability of ecosystems. An exceptional drought (

The impact of acute remote ischaemic preconditioning on cerebrovascular function - Howard H. Carter; Joseph D. Maxwell; Ylva Hellsten; Andrew Thompson; Dick H. J. Thijssen; Helen Jones (European Journal of Applied Physiology, 2020)
Purpose Remote ischaemic preconditioning (RIPC) refers to the protection conferred to tissues and organs via brief periods of ischaemia in a remote vascular territory, including the brain. Recent studies in humans report that RIPC provides neuroprotection against recurrent (ischaemic) stroke. To better understand the ability of RIPC to improve brain health, the present study explored the potential for RIPC to acutely improve cerebrovascular function. Methods Eleven young healthy (females n = 6, age; 28.1 ± 3.7 years) and 9 older individuals (females n = 4, age 52.5 ± 6.7 years) at increased risk for stroke (cardiovascular disease risk factors) underwent assessments of cerebrovascular function, assessed by carbon dioxide (CO 2 ) reactivity and cerebral autoregulation during normo- and hypercapnia (5% CO 2 ) following 40 mins of bilateral arm RIPC or a sham condition. Squat-to-stand manoeuvres were performed to induce changes in blood pressure to assess cerebral autoregulation (0.10 Hz) and analysed via transfer function. Results We found no change in middle cerebral artery velocity or blood pressure across 40 mins of RIPC. Application of RIPC resulted in no change in CO 2 reactivity slopes (sham vs RIPC, 1.97 ± 0.88 vs 2.06 ± 0.69 cm/s/mmHg P = 0.61) or parameters of cerebral autoregulation during normocapnia (sham vs RIPC, normalised gain%, 1.27 ± 0.25 vs 1.22 ± 0.35, P = 0.46). Conclusion This study demonstrates that a single bout of RIPC does not influence cerebrovascular function acutely in healthy individuals, or those at increased cardiovascular risk. Given the previously reported protective role of RIPC on stroke recurrence in humans, it is possible that repeated bouts of RIPC may be necessary to impart beneficial effects on cerebrovascular function.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Risk Management and Analytics in Wildfire Response - Matthew P. Thompson; Yu Wei; David E. Calkin; Christopher D. O’Connor; Christopher J. Dunn; Nathaniel M. Anderson; John S. Hogland (Current Forestry Reports, 2019)
Purpose of Review The objectives of this paper are to briefly review basic risk management and analytics concepts, describe their nexus in relation to wildfire response, demonstrate real-world application of analytics to support response decisions and organizational learning, and outline an analytics strategy for the future. Recent Findings Analytics can improve decision-making and organizational performance across a variety of areas from sports to business to real-time emergency response. A lack of robust descriptive analytics on wildfire incident response effectiveness is a bottleneck for developing operationally relevant and empirically credible predictive and prescriptive analytics to inform and guide strategic response decisions. Capitalizing on technology such as automated resource tracking and machine learning algorithms can help bridge gaps between monitoring, learning, and data-driven decision-making. Summary By investing in better collection, documentation, archiving, and analysis of operational data on response effectiveness, fire management organizations can promote systematic learning and provide a better evidence base to support response decisions. We describe an analytics management framework that can provide structure to help deploy analytics within organizations, and provide real-world examples of advanced fire analytics applied in the USA. To fully capitalize on the potential of analytics, organizations may need to catalyze cultural shifts that cultivate stronger appreciation for data-driven decision processes, and develop informed skeptics that effectively balance both judgment and analysis in decision-making.

Characterising extinction debt following habitat fragmentation using neutral theory - Samuel E. D. Thompson; Ryan A. Chisholm; James Rosindell (Ecology Letters, 2019)
Habitat loss leads to species extinctions, both immediately and over the long term as ‘extinction debt’ is repaid. The same quantity of habitat can be lost in different spatial patterns with varying habitat fragmentation. How this translates to species loss remains an open problem requiring an understanding of the interplay between community dynamics and habitat structure across temporal and spatial scales. Here we develop formulas that characterise extinction debt in a spatial neutral model after habitat loss and fragmentation. Central to our formulas are two new metrics, which depend on properties of the taxa and landscape: ‘effective area’, measuring the remaining number of individuals and ‘effective connectivity’, measuring individuals’ ability to disperse through fragmented habitat. This formalises the conventional wisdom that habitat area and habitat connectivity are the two critical requirements for long‐term preservation of biodiversity. Our approach suggests that mechanistic fragmentation metrics help resolve debates about fragmentation and species loss.

Bridging From Monitoring to Solutions-Based Thinking: Lessons From CalCOFI for Understanding and Adapting to Marine Climate Change Impacts - Natalya D. Gallo; Elizabeth Drenkard; Andrew R. Thompson; Edward D. Weber; Deb Wilson-Vandenberg; Sam McClatchie; J. Anthony Koslow; Brice X. Semmens (Frontiers in Marine Science, 2019)

Interactions Between Mean Sea Level, Tide, Surge, Waves and Flooding: Mechanisms and Contributions to Sea Level Variations at the Coast - Déborah Idier; Xavier Bertin; Philip Thompson; Mark D. Pickering (Surveys in Geophysics, 2019)

A resting state fMRI analysis pipeline for pooling inference across diverse cohorts: an ENIGMA rs-fMRI protocol - Bhim M. Adhikari; Neda Jahanshad; Dinesh Shukla; Jessica Turner; Dominik Grotegerd; Udo Dannlowski; Harald Kugel; Jennifer Engelen; Bruno Dietsche; Axel Krug; Tilo Kircher; Els Fieremans; et al. (Brain Imaging and Behavior, 2019)

Reconciling the contribution of environmental and stochastic structuring of tropical forest diversity through the lens of imaging spectroscopy - Boris Bongalov; David F. R. P. Burslem; Tommaso Jucker; Samuel E. D. Thompson; James Rosindell; Tom Swinfield; Reuben Nilus; Daniel Clewley; Oliver L. Phillips; David A. Coomes (Ecology Letters, 2019)
Both niche and stochastic dispersal processes structure the extraordinary diversity of tropical plants, but determining their relative contributions has proven challenging. We address this question using airborne imaging spectroscopy to estimate canopy β‐diversity for an extensive region of a Bornean rainforest and challenge these data with models incorporating niches and dispersal. We show that remotely sensed and field‐derived estimates of pairwise dissimilarity in community composition are closely matched, proving the applicability of imaging spectroscopy to provide β‐diversity data for entire landscapes of over 1000 ha containing contrasting forest types. Our model reproduces the empirical data well and shows that the ecological processes maintaining tropical forest diversity are scale dependent. Patterns of β‐diversity are shaped by stochastic dispersal processes acting locally whilst environmental processes act over a wider range of scales.

Identification of a novel species of Eimeria Schneider, 1875 from the woylie, Bettongia penicillata Gray (Diprotodontia: Potoroidae) and the genetic characterisation of three Eimeria spp. from other potoroid marsupials - Amy S. Northover; Sarah Keatley; Aileen D. Elliot; Russell P. Hobbs; Rongchang Yang; Alan J. Lymbery; Stephanie S. Godfrey; Adrian F. Wayne; R. C. Andrew Thompson (Systematic Parasitology, 2019)

Spatial heterogeneity of gall formation in relation to chemotype distribution in Thymus vulgaris - John D. Thompson; Justin Amiot; Christophe Borron; Yan B. Linhart; Ken Keeefover-Ring; Perrine Gauthier (Plant Ecology, 2019)

Whole cell inactivated autogenous vaccine effectively protects red Nile tilapia ( Oreochromis niloticus ) against francisellosis via intraperitoneal injection - José Gustavo Ramírez‐Paredes; Miguel Angel Mendoza‐Roldan; Benjamin Lopez‐Jimena; Khalid Shahin; Matthijs Metselaar; Kim D. Thompson; David J. Penman; Randolph H. Richards; Alexandra Adams (Journal of Fish Diseases, 2019)
Francisella noatunensis subsp. orientalis is a pathogen of tilapia and other warm‐water fish for which no vaccines are commercially available. In this study, a whole cell formalin‐inactivated vaccine was developed for the first time using the highly virulent isolate STIR‐GUS‐F2f7 and the oil‐based adjuvant Montanide™ ISA 763A VG. The efficacy of the vaccine was assessed in red Nile tilapia via intraperitoneal (i.p.) injection using homologous experimental infection and correlates of protection such as seral antibody production and bacterial loads in the spleen. For immunization, fish were i.p. injected with 0.1 ml of the vaccine, the adjuvant alone or PBS. At 840 degree days post‐vaccination, all fish were i.p. injected with 4.0 × 10 3 CFU/fish of pathogenic bacteria. The RPS at the end of the trial was 100% in the vaccinated group with significantly higher survival than in the adjuvant and control groups. The RPS in the adjuvant group was 42%, and no significant difference was seen in survival between this and the PBS group. Moreover, significantly higher antibody titres in the serum and significantly lower bacterial loads in the spleen were detected in the vaccinated fish by ELISA and qPCR, respectively. These findings highlight the potential of autogenous vaccines for controlling francisellosis in tilapia.

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Exploration of Shared Genetic Architecture Between Subcortical Brain Volumes and Anorexia Nervosa - E. Walton; D. Hibar; Z. Yilmaz; N. Jahanshad; J. Cheung; V.-L. Batury; J. Seitz; C. M. Bulik; P. M. Thompson; Stefan Ehrlich (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Oocyte quality and viability in Nguni and Hereford cows exposed to different levels of dietary protein - R. Hamman; P. N. Thompson; M. P. Smuts; T. Tshuma; D. E. Holm (Tropical Animal Health and Production, 2019)

Frequency content of environmental variability and extinction risk of age-structured populations: Chinook salmon (Oncorhynchus tschawytscha) as an example - D. Patrick Kilduff; Louis W. Botsford; Lisa C. Thompson (Theoretical Ecology, 2019)

Cotton (Gossypium hirsutum L.) mutants with reduced levels of palmitic acid (C16:0) in seed lipids - Corey N. Thompson; Bralie R. Hendon; Deepika Mishra; Jacob M. Rieff; Cindy C. Lowery; Kimberly C. Lambert; Travis W. Witt; Steven J. Oswalt; Efrem Bechere; C. Wayne Smith; Roy G. Cantrell; Brendan R. Kelly; et al. (Euphytica, 2019)

Halomonas coralii sp. nov. Isolated from Mussismilia braziliensis - Livia M. R. Vidal; Aline Gonçalves; Tainá M. Venas; Mariana E. Campeão; Gabriela Calegario; Juline M. Walter; Bruno S. Silva; Gizele D. Garcia; Diogo A. Tschoeke; Jean Swings; Fabiano L. Thompson; Cristiane C. Thompson (Current Microbiology, 2019)

Imaging Spectroscopy for the Detection, Assessment and Monitoring of Natural and Anthropogenic Hazards - C. Ong; V. Carrère; S. Chabrillat; R. Clark; T. Hoefen; R. Kokaly; R. Marion; C. R. Souza Filho; G. Swayze; D. R. Thompson (Surveys in Geophysics, 2019)

Exposure to antibiotics in the first 24 months of life and neurocognitive outcomes at 11 years of age - R. F. Slykerman; C. Coomarasamy; K. Wickens; J. M. D. Thompson; T. V. Stanley; C. Barthow; J. Kang; J. Crane; E. A. Mitchell (Psychopharmacology, 2019)

Gut microbiome and brain functional connectivity in infants-a preliminary study focusing on the amygdala - Wei Gao; Andrew P. Salzwedel; Alexander L. Carlson; Kai Xia; M. Andrea Azcarate-Peril; Martin A. Styner; Amanda L. Thompson; Xiujuan Geng; Barbara D. Goldman; John H. Gilmore; Rebecca C. Knickmeyer (Psychopharmacology, 2019)

Relationships Between Estimated Hourly Energy Balance and Body Composition in Professional Cheerleaders - Moriah P. Bellissimo; Ashley D. Licata; Anita Nucci; Walter Thompson; Dan Benardot (Journal of Science in Sport and Exercise, 2019)

Subcortical shape and neuropsychological function among U.S. service members with mild traumatic brain injury - David F. Tate; Benjamin S. C. Wade; Carmen S. Velez; Ann Marie Drennon; Jacob D. Bolzenius; Douglas B. Cooper; Jan E. Kennedy; Matthew W. Reid; Amy O. Bowles; Paul M. Thompson; Boris A. Gutman; Jeffrey D. Lewis; et al. (Brain Imaging and Behavior, 2019)

Multi-gene panel testing confirms phenotypic variability in MUTYH-Associated Polyposis - Erin G. Sutcliffe; Amanda Bartenbaker Thompson; Amy R. Stettner; Megan L. Marshall; Maegan E. Roberts; Lisa R. Susswein; Ying Wang; Rachel T. Klein; Kathleen S. Hruska; Benjamin D. Solomon (Familial Cancer, 2019)

Redoximorphic Bt horizons of the Calhoun CZO soils exhibit depth-dependent iron-oxide crystallinity - Chunmei Chen; Diego Barcellos; Daniel D. Richter; Paul A. Schroeder; Aaron Thompson (Journal of Soils and Sediments, 2019)

Identification of newly settled Caribbean coral recruits by ITS-targeted single-step nested multiplex PCR - Elijah D. O’Cain; Marc E. Frischer; J. Scott Harrison; Tina L. Walters; Megan E. Thompson; Nicole D. Fogarty; Rob Ruzicka; Daniel F. Gleason (Coral Reefs, 2019)

Efficacy of a polyvalent injectable vaccine against Flavobacterium psychrophilum administered to rainbow trout ( Oncorhynchus mykiss L.) - Rowena Hoare; Sung‐Ju Jung; Thao P. H. Ngo; Kerry L. Bartie; Kim D. Thompson; Alexandra Adams (Journal of Fish Diseases, 2019)
Flavobacterium psychrophilum is one of the most important pathogens affecting cultured rainbow trout ( Oncorhynchus mykiss ). Recent information from UK salmonid farms showed country‐wide distribution of genetically and serologically divergent clones, which has hampered the development of a vaccine for rainbow trout fry syndrome. The current study assessed the efficacy of an injectable polyvalent vaccine containing formalin‐inactivated F. psychrophilum in rainbow trout. The vaccine was formulated with an oil adjuvant (Montanide ISA 760VG) or formalin‐killed cells alone. Duplicate groups of trout (60 ± 13 g) were given phosphate‐buffered saline or vaccine formulated with Montanide by intra‐peritoneal (i.p.) injection and challenged by intra‐muscular (i.m.) injection with a homologous and a heterologous isolate of F. psychrophilum at 525 degree days post‐vaccination (dd pv). Significant protection was achieved in vaccinated fish ( p = 0.0001, RPS 76% homologous, 88% heterologous). Efficacy of the adjuvanted vaccine was also demonstrated by heterologous challenge at 1155 dd pv resulting in 100% protection, whereas survival in the un‐adjuvanted group was not significantly different from control fish. Levels of specific antibody at 1155 dd pv, as measured by ELISA, were significantly higher in the fish vaccinated with adjuvant when compared with unvaccinated fish.

Population dynamics has greater effects than climate change on tree species distribution in a temperate forest region - Wen J. Wang; Frank R. Thompson; Hong S. He; Jacob S. Fraser; William D. Dijak; Martin A. Spetich (Journal of Biogeography, 2018)
Aim Population dynamics and disturbances have often been simplified or ignored when predicting regional‐scale tree species distributions in response to climate change in current climate‐distribution models (e.g., niche and biophysical process models). We determined the relative importance of population dynamics, tree harvest, climate change, and their interaction in affecting tree species distribution changes. Location Central Hardwood Forest Region of the United States. Major taxa studied Tree species. Methods We used a forest dynamic model, LANDIS PRO that accounted for population dynamics, tree harvest, and climate change to predict tree species’ distributions at 270 m resolution from 2000 to 2300. We quantified the relative importance of these factors using a repeated measures analysis of variance. We further investigated the effects of each factor on changes in species distributions by summarizing extinction and colonization rates. Results On average, population dynamics was the most important factor affecting tree species distribution changes. Tree harvest was more important than climate change by 2100 whereas climate change was more important than harvest by 2300. By end of the 21 st century, most tree species expanded their distributions irrespective of any climate or harvest scenario. By 2300, most northern, some southern, and most widely distributed species contracted their distributions while most southern species, some widely distributed species, and few northern species expanded their distributions under warmer climates with tree harvest. Harvest accelerated or ameliorated the contractions and expansions for species that were negatively or positively affected by climate change. Main conclusions Our results suggest that population dynamics and tree harvest can be more important than climate change and thus should be explicitly included when predicting future tree species’ distributions. Understanding the underlying mechanisms that drive tree species distributions will enable better predictions of tree species distributions under climate change.

The ecohydrological context of drought and classification of plant responses - Xue Feng; David D. Ackerly; Todd E. Dawson; Stefano Manzoni; Rob P. Skelton; Giulia Vico; Sally E. Thompson (Ecology Letters, 2018)
Many recent studies on drought‐induced vegetation mortality have explored how plant functional traits, and classifications of such traits along axes of, for example, isohydry–anisohydry, might contribute to predicting drought survival and recovery. As these studies proliferate, the consistency and predictive value of such classifications need to be carefully examined. Here, we outline the basis for a systematic classification of plant drought responses that accounts for both environmental conditions and functional traits. We use non‐dimensional analysis to integrate plant traits and metrics of environmental variation into groups that can be associated with alternative drought stress pathways (hydraulic failure and carbon limitation), and demonstrate that these groupings predict physiological drought outcomes using both synthetic and measured data. In doing so, we aim to untangle some confounding effects of environment and trait variations that undermine current classification schemes, advocate for more careful treatment of the environmental context within which plants experience and respond to drought, and outline a pathway towards a general classification of drought vulnerability.

Longitudinal Preterm Cerebellar Volume: Perinatal and Neurodevelopmental Outcome Associations - Lillian G. Matthews; T. E. Inder; L. Pascoe; K. Kapur; K. J. Lee; B. B. Monson; L. W. Doyle; D. K. Thompson; P. J. Anderson (The Cerebellum, 2018)

Eastern rockhopper penguins Eudyptes filholi as biological samplers of juvenile and sub-adult cephalopods around Campbell Island, New Zealand - J. C. Xavier; Y. Cherel; F. R. Ceia; J. P. Queirós; B. Guimarães; R. Rosa; D. M. Cunningham; P. J. Moors; D. R. Thompson (Polar Biology, 2018)

The metabolic fate of fenclozic acid in chimeric mice with a humanized liver - Anja Ekdahl; Lars Weidolf; Matthew Baginski; Yoshio Morikawa; Richard A. Thompson; Ian D. Wilson (Archives of Toxicology, 2018)

Different types of drifts in two seasonal forecast systems and their dependence on ENSO - L Hermanson; H.-L. Ren; M. Vellinga; N. D. Dunstone; P. Hyder; S. Ineson; A. A. Scaife; D. M. Smith; V. Thompson; B. Tian; K. D. Williams (Climate Dynamics, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Description of Alteromonas abrolhosensis sp. nov., isolated from sea water of Abrolhos Bank, Brazil - Maria S. Nóbrega; Bruno S. Silva; Luciana Leomil; Diogo Antonio Tschoeke; Mariana E. Campeão; Gizele D. Garcia; Graciela A. Dias; Verônica V. Vieira; Cristiane C. Thompson; Fabiano L. Thompson (Antonie van Leeuwenhoek, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Rapid isolation of culturable microalgae from a tropical shallow lake system - Giovana O. Fistarol; Paulo I. Hargreaves; Juline M. Walter; Tatiana V. Viana; Piter D. F. Gomes; Caio Brito Lourenço; Carlos E. Rezende; Gustavo Gregoracci; Cintia Rua; Cristiane C. Thompson; Fabiano L. Thompson; Paulo S. Salomon (Journal of Applied Phycology, 2018)

Perspectives on the Great Amazon Reef: Extension, Biodiversity, and Threats - Ronaldo B. Francini-Filho; Nils E. Asp; Eduardo Siegle; John Hocevar; Kenneth Lowyck; Nilo D'Avila; Agnaldo A. Vasconcelos; Ricardo Baitelo; Carlos E. Rezende; Claudia Y. Omachi; Cristiane C. Thompson; Fabiano L. Thompson (Frontiers in Marine Science, 2018)

Blue-Green Water Nexus in Aquaculture for Resilience to Climate Change - Nesar Ahmed; James D. Ward; Shirley Thompson; Christopher P. Saint; James S. Diana (Reviews in Fisheries Science & Aquaculture, 2018)

The Kraken Wakes: induced EMT as a driver of tumour aggression and poor outcome - Andrew D. Redfern; Lisa J. Spalding; Erik W. Thompson (Clinical & Experimental Metastasis, 2018)

Non-communicable chronic diseases and timely breast cancer screening among women of the Eastern Caribbean Health Outcomes Research Network (ECHORN) Cohort Study - K. H. Wang; T. A. Thompson; D. Galusha; H. Friedman; C. M. Nazario; M. Nunez; R. G. Maharaj; O. P. Adams; M. Nunez-Smith (Cancer Causes & Control, 2018)

Thermal biology mediates responses of amphibians and reptiles to habitat modification - A. Justin Nowakowski; James I. Watling; Michelle E. Thompson; George A. Brusch; Alessandro Catenazzi; Steven M. Whitfield; David J. Kurz; Ángela Suárez‐Mayorga; Andrés Aponte‐Gutiérrez; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2018)
Human activities often replace native forests with warmer, modified habitats that represent novel thermal environments for biodiversity. Reducing biodiversity loss hinges upon identifying which species are most sensitive to the environmental conditions that result from habitat modification. Drawing on case studies and a meta‐analysis, we examined whether observed and modelled thermal traits, including heat tolerances, variation in body temperatures, and evaporative water loss, explained variation in sensitivity of ectotherms to habitat modification. Low heat tolerances of lizards and amphibians and high evaporative water loss of amphibians were associated with increased sensitivity to habitat modification, often explaining more variation than non‐thermal traits. Heat tolerances alone explained 24–66% (mean = 38%) of the variation in species responses, and these trends were largely consistent across geographic locations and spatial scales. As habitat modification alters local microclimates, the thermal biology of species will likely play a key role in the reassembly of terrestrial communities.

Secondary resistance to tolvaptan in two patients with SIAD due to small cell lung cancer - A. Garrahy; A. M. Hannon; H. M. Zia-Ul-Hussnain; D. J. Williams; C. J. Thompson (European Journal of Clinical Pharmacology, 2018)

Antimicrobial susceptibility of Flavobacterium psychrophilum isolates from the United Kingdom - T P H Ngo; P Smith; K L Bartie; K D Thompson; D W Verner‐Jeffreys; R Hoare; A Adams (Journal of Fish Diseases, 2018)
Routine application of antimicrobials is the current treatment of choice for rainbow trout fry syndrome ( RTFS ) or bacterial coldwater disease ( BCWD ) caused by Flavobacterium psychrophilum . In this study, the antimicrobial susceptibilities of 133 F. psychrophilum isolates, 118 of which were from the UK , were evaluated by broth microdilution and disc diffusion methods following VET 04‐A2 and VET 03‐A guidelines of Clinical and Laboratory Standards Institute ( CLSI ), respectively. Isolates were categorized as wild type (fully susceptible, WT ) or non‐wild type ( NWT ) using normalized resistance interpretation ( NRI )‐determined cut‐off values ( CO WT ). Broth microdilution testing showed that only 12% of UK isolates were WT to oxolinic acid ( MIC CO WT ≤ 0.25 mg/L) and 42% were WT for oxytetracycline ( MIC CO WT ≤ 0.25 mg/L). In contrast, all the isolates tested were WT ( MIC CO WT ≤ 2 mg/L) for florfenicol, the main antimicrobial for RTFS control in the UK . Disc diffusion‐based CO WT values were ≥51 mm for 10 μg amoxicillin, ≥44 mm for 30 μg florfenicol, ≥30 mm for 2 μg oxolinic acid and ≥51 mm for 30 μg oxytetracycline. There was a high categorical agreement between the classifications of the isolates by two testing methods for florfenicol (100%), oxytetracycline (93%) and oxolinic acid (99%).

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

An improved null model for assessing the net effects of multiple stressors on communities - Patrick L. Thompson; Megan M. MacLennan; Rolf D. Vinebrooke (Global Change Biology, 2018)
Ecological stressors (i.e., environmental factors outside their normal range of variation) can mediate each other through their interactions, leading to unexpected combined effects on communities. Determining whether the net effect of stressors is ecologically surprising requires comparing their cumulative impact to a null model that represents the linear combination of their individual effects (i.e., an additive expectation). However, we show that standard additive and multiplicative null models that base their predictions on the effects of single stressors on community properties (e.g., species richness or biomass) do not provide this linear expectation, leading to incorrect interpretations of antagonistic and synergistic responses by communities. We present an alternative, the compositional null model, which instead bases its predictions on the effects of stressors on individual species, and then aggregates them to the community level. Simulations demonstrate the improved ability of the compositional null model to accurately provide a linear expectation of the net effect of stressors. We simulate the response of communities to paired stressors that affect species in a purely additive fashion and compare the relative abilities of the compositional null model and two standard community property null models (additive and multiplicative) to predict these linear changes in species richness and community biomass across different combinations (both positive, negative, or opposite) and intensities of stressors. The compositional model predicts the linear effects of multiple stressors under almost all scenarios, allowing for proper classification of net effects, whereas the standard null models do not. Our findings suggest that current estimates of the prevalence of ecological surprises on communities based on community property null models are unreliable, and should be improved by integrating the responses of individual species to the community level as does our compositional null model.

Forest biodiversity, ecosystem functioning and the provision of ecosystem services - Eckehard G. Brockerhoff; Luc Barbaro; Bastien Castagneyrol; David I. Forrester; Barry Gardiner; José Ramón González-Olabarria; Phil O’B. Lyver; Nicolas Meurisse; Anne Oxbrough; Hisatomo Taki; Ian D. Thompson; Fons van der Plas; et al. (Biodiversity and Conservation, 2017)

Simulation of the hydrological impacts of climate change on a restored floodplain - Julian R. Thompson; Honeyeh Iravani; Hannah M. Clilverd; Carl D. Sayer; Catherine M. Heppell; Jan C. Axmacher (Hydrological Sciences Journal, 2017)

Evaluation of training dose in male Sprague-Dawley rats trained to discriminate 4-methylmethcathinone - Michael D. Berquist; Nathyn A. Thompson; Lisa E. Baker (Psychopharmacology, 2017)

Application of low‐frequency sonophoresis and reduction of antibiotics in the aquatic systems - C Cobo Labarca; J Radinger; V Schöning; R Ariav; R Jung; K D Thompson; W Kloas; K Knopf (Journal of Fish Diseases, 2017)
A major concern in aquaculture is the use of chemical therapeutics, such as antibiotics, because of their impact on the environment as well as on the fish product. As a potential tool for reducing antibiotic use, we tested the application of low‐frequency ultrasound as a method for enhancing antibiotic uptake. Rainbow trout juveniles ( Oncorhynchus mykiss) were exposed to two different concentrations of oxytetracycline ( OTC ), flumequine ( FLU ) and florfenicol ( FLO ), administered by bath after the application of ultrasound. After exposure, concentrations of these substances were measured in the liver and blood of treated fish. Results showed that the ultrasound treatment can significantly increase the uptake for all three antibiotics. The uptake of OTC for example, in fish exposed to an OTC concentration of 20 mg L −1 after prior treatment with ultrasound, was similar to the OTC concentrations in their liver and blood to fish exposed to 100 mg L −1 without sonication. For FLU and FLO , the use of ultrasound caused significant differences of uptake in the liver at high antibiotic concentrations. This suggests that the use of ultrasound as a technique to deliver antibiotics to fish can ultimately reduce the amount of antibiotics discharged into the aquatic environment.

Outbreak of Cleidodiscus in juvenile black crappies ( Pomoxis nigromaculatus ) and bath treatment with praziquantel - C Bader; J Jesudoss Chelladurai; K Thompson; D Starling; M T Brewer (Journal of Fish Diseases, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Facing a wicked problem with optimism: issues and priorities for coral conservation in Hong Kong - N. N. Duprey; S. E. McIlroy; T. P. T. Ng; P. D. Thompson; T. Kim; J. C. Y. Wong; C. W. M. Wong; S. M. Husa; S. M. H. Li; G. A. Williams; D. M. Baker (Biodiversity and Conservation, 2017)

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

The impacts of rising temperatures on aircraft takeoff performance - Ethan D. Coffel; Terence R. Thompson; Radley M. Horton (Climatic Change, 2017)

Reconciling seasonal hydraulic risk and plant water use through probabilistic soil–plant dynamics - Xue Feng; Todd E. Dawson; David D. Ackerly; Louis S. Santiago; Sally E. Thompson (Global Change Biology, 2017)
Current models used for predicting vegetation responses to climate change are often guided by the dichotomous needs to resolve either (i) internal plant water status as a proxy for physiological vulnerability or (ii) external water and carbon fluxes and atmospheric feedbacks. Yet, accurate representation of fluxes does not always equate to accurate predictions of vulnerability. We resolve this discrepancy using a hydrodynamic framework that simultaneously tracks plant water status and water uptake. We couple a minimalist plant hydraulics model with a soil moisture model and, for the first time, translate rainfall variability at multiple timescales – with explicit descriptions at daily, seasonal, and interannual timescales – into a physiologically meaningful metric for the risk of hydraulic failure. The model, parameterized with measured traits from chaparral species native to Southern California, shows that apparently similar transpiration patterns throughout the dry season can emerge from disparate plant water potential trajectories, and vice versa. The parsimonious set of parameters that captures the role of many traits across the soil–plant–atmosphere continuum is then used to establish differences in species sensitivities to shifts in seasonal rainfall statistics, showing that co‐occurring species may diverge in their risk of hydraulic failure despite minimal changes to their seasonal water use. The results suggest potential shifts in species composition in this region due to species‐specific changes in hydraulic risk. Our process‐based approach offers a quantitative framework for understanding species sensitivity across multiple timescales of rainfall variability and provides a promising avenue toward incorporating interactions of temporal variability and physiological mechanisms into drought response models.

Distribution and abundance of cetaceans in a wind energy development area offshore of Massachusetts and Rhode Island - Kelsey M. Stone; Sarah M. Leiter; Robert D. Kenney; Brooke C. Wikgren; Jessica L. Thompson; Jessica K. D. Taylor; Scott D. Kraus (Journal of Coastal Conservation, 2017)

Ultrastructural analysis of sequential cyprinid herpesvirus 3 morphogenesis in vitro - S J Monaghan; S M Bergmann; K D Thompson; L Brown; T Herath; J del‐Pozo; A Adams (Journal of Fish Diseases, 2017)
Cyprinid herpesvirus 3 (Cy HV ‐3) is an alloherpesvirus, and it is the aetiological agent of koi herpesvirus disease. Although the complex morphogenic stages of the replication cycle of Cy HV ‐3 were shown to resemble that of other members of the Herpesvirales , detailed analysis of the sequence and timing of these events was not definitively determined. This study describes these features through a time course using cyprinid cell cultures ( KF ‐1 and CCB ) infected with Cy HV ‐3 ( KHV isolate, H361) and analysed by transmission electron microscopy. Rapid viral entry was noted, with high levels of intracellular virus within 1–4 h post‐infection (hpi). Intranuclear capsid assembly, paracrystalline array formation and primary envelopment of capsids occurred within 4 hpi. Between 1 and 3 days post‐infection (dpi), intracytoplasmic secondary envelopment occurred, as well as budding of infectious virions at the plasma membrane. At 5–7 dpi, the cytoplasm contained cytopathic vacuoles, enveloped virions within vesicles, and abundant non‐enveloped capsids; also there was frequent nuclear deformation. Several morphological features are suggestive of inefficient viral assembly, with production of non‐infectious particles, particularly in KF ‐1 cells. The timing of this alloherpesvirus morphogenesis is similar to other members of the Herpesvirales, but there may be possible implications of using different cell lines for Cy HV ‐3 propagation.

Hydrologic refugia, plants, and climate change - Blair C. McLaughlin; David D. Ackerly; P. Zion Klos; Jennifer Natali; Todd E. Dawson; Sally E. Thompson (Global Change Biology, 2017)
Climate, physical landscapes, and biota interact to generate heterogeneous hydrologic conditions in space and over time, which are reflected in spatial patterns of species distributions. As these species distributions respond to rapid climate change, microrefugia may support local species persistence in the face of deteriorating climatic suitability. Recent focus on temperature as a determinant of microrefugia insufficiently accounts for the importance of hydrologic processes and changing water availability with changing climate. Where water scarcity is a major limitation now or under future climates, hydrologic microrefugia are likely to prove essential for species persistence, particularly for sessile species and plants. Zones of high relative water availability – mesic microenvironments – are generated by a wide array of hydrologic processes, and may be loosely coupled to climatic processes and therefore buffered from climate change. Here, we review the mechanisms that generate mesic microenvironments and their likely robustness in the face of climate change. We argue that mesic microenvironments will act as species‐specific refugia only if the nature and space/time variability in water availability are compatible with the ecological requirements of a target species. We illustrate this argument with case studies drawn from California oak woodland ecosystems. We posit that identification of hydrologic refugia could form a cornerstone of climate‐cognizant conservation strategies, but that this would require improved understanding of climate change effects on key hydrologic processes, including frequently cryptic processes such as groundwater flow.

Egg shape in the Common Guillemot Uria aalge and Brunnich’s Guillemot U. lomvia: not a rolling matter? - Tim R. Birkhead; Jamie E. Thompson; John D. Biggins (Journal of Ornithology, 2017)

MRI Characterization in the Acute Phase of Experimental Subarachnoid Hemorrhage - Dewei Guo; D. Andrew Wilkinson; B. Gregory Thompson; Aditya S. Pandey; Richard F Keep; Guohua Xi; Ya Hua (Translational Stroke Research, 2017)

Amphibian sensitivity to habitat modification is associated with population trends and species traits - A. Justin Nowakowski; Michelle E. Thompson; Maureen A. Donnelly; Brian D. Todd (Global Ecology and Biogeography, 2017)
Aim Habitat modification is causing widespread declines in biodiversity and the homogenization of biotas. Amphibians are especially threatened by habitat modification, yet we know little about why some species persist or thrive in the face of this threat whereas others decline. Our aim was to identify intrinsic factors that explain variation among amphibians in their sensitivity to habitat modification (SHM), factors that could help target groups of species for conservation. Location Global. Time period 1986–2015 Major taxon studied Amphibians. Methods We quantified SHM using species abundances in natural and altered habitats as reported in published field surveys. We first examined associations between local SHM and range‐wide threatened status, population trends and invasiveness. We then evaluated the importance of intrinsic and extrinsic variables in explaining species SHM using multiple comparative methods. Our analyses included over 200 species that could be ranked with confidence from 47 studies across five continents. Results Amphibians species varied considerably in local SHM. High SHM was associated with elevated range‐wide extinction risk and declining population trends. Species that were tolerant of habitat modification were most likely to be invasive outside their native range. Geographical range size was the most important intrinsic predictor and was negatively associated with SHM. Larval habitat was also an important predictor, but was tightly coupled with phylogenetic position. Main conclusions Narrowly distributed species whose larvae develop on land or in lotic habitats are most sensitive to habitat modification. However, other unmeasured, phylogenetically constrained traits could underlie the effect of larval habitat. Species range size is frequently correlated with global extinction risk in vertebrates, and our analysis extends this macroecological pattern to the sensitivity of amphibians to local habitat loss, a proximate driver of extinction. These general patterns of SHM should help identify those groups of amphibians most at risk in an era of rapid habitat loss and scarce conservation resources.

DNA Sequencing as a Tool to Monitor Marine Ecological Status - Kelly D. Goodwin; Luke R. Thompson; Bernardo Duarte; Tim Kahlke; Andrew R. Thompson; João C. Marques; Isabel Caçador (Frontiers in Marine Science, 2017)

Acrolein Inhalation Alters Myocardial Synchrony and Performance at and Below Exposure Concentrations that Cause Ventilatory Responses - Leslie C. Thompson; Allen D. Ledbetter; Najwa Haykal-Coates; Wayne E. Cascio; Mehdi S. Hazari; Aimen K. Farraj (Cardiovascular Toxicology, 2017)

Long-term trends in cetacean occurrence during the annual sardine run off the Wild Coast, South Africa - M Caputo; PW Froneman; D du Preez; G Thompson; S Plön (African Journal of Marine Science, 2017)

Dynamic habitat corridors for marine predators; intensive use of a coastal channel by harbour seals is modulated by tidal currents - Gordon D. Hastie; Deborah J.F. Russell; Steven Benjamins; Simon Moss; Ben Wilson; Dave Thompson (Behavioral Ecology and Sociobiology, 2016)

Optimization of Spray Drying Conditions for Yield, Particle Size and Biological Activity of Thermally Stable Viral Vectors - Daniel A. LeClair; Emily D. Cranston; Zhou Xing; Michael R. Thompson (Pharmaceutical Research, 2016)

Conservation genetics of the endangered San Francisco Bay endemic salt marsh harvest mouse (Reithrodontomys raviventris) - M. J. Statham; S. Aamoth; L. Barthman-Thompson; S. Estrella; S. Fresquez; L. D. Hernandez; R. Tertes; B. N. Sacks (Conservation Genetics, 2016)

Policy challenges and approaches for the conservation of mangrove forests in Southeast Asia - Daniel A. Friess; Benjamin S. Thompson; Ben Brown; A. Aldrie Amir; Clint Cameron; Heather J. Koldewey; Sigit D. Sasmito; Frida Sidik (Conservation Biology, 2016)
Many drivers of mangrove forest loss operate over large scales and are most effectively addressed by policy interventions. However, conflicting or unclear policy objectives exist at multiple tiers of government, resulting in contradictory management decisions. To address this, we considered four approaches that are being used increasingly or could be deployed in Southeast Asia to ensure sustainable livelihoods and biodiversity conservation. First, a stronger incorporation of mangroves into marine protected areas (that currently focus largely on reefs and fisheries) could resolve some policy conflicts and ensure that mangroves do not fall through a policy gap. Second, examples of community and government comanagement exist, but achieving comanagement at scale will be important in reconciling stakeholders and addressing conflicting policy objectives. Third, private‐sector initiatives could protect mangroves through existing and novel mechanisms in degraded areas and areas under future threat. Finally, payments for ecosystem services (PES) hold great promise for mangrove conservation, with carbon PES schemes (known as blue carbon) attracting attention. Although barriers remain to the implementation of PES, the potential to implement them at multiple scales exists. Closing the gap between mangrove conservation policies and action is crucial to the improved protection and management of this imperiled coastal ecosystem and to the livelihoods that depend on them.

Sheep grazing in the North Atlantic region: A long-term perspective on environmental sustainability - Louise C. Ross; Gunnar Austrheim; Leif-Jarle Asheim; Gunnar Bjarnason; Jon Feilberg; Anna Maria Fosaa; Alison J. Hester; Øystein Holand; Ingibjörg S. Jónsdóttir; Lis E. Mortensen; Atle Mysterud; Erla Olsen; et al. (Ambio, 2016)

Metaproteomics reveals metabolic transitions between healthy and diseased stony coral Mussismilia braziliensis - Gizele D. Garcia; Eidy de O. Santos; Gabriele V. Sousa; Russolina B. Zingali; Cristiane C. Thompson; Fabiano L. Thompson (Molecular Ecology, 2016)
Infectious diseases such as white plague syndrome ( WPS ) and black band disease ( BBD ) have caused massive coral loss worldwide. We performed a metaproteomic study on the Abrolhos coral Mussismilia braziliensis to define the types of proteins expressed in healthy corals compared to WPS ‐ and BBD ‐affected corals. A total of 6363 MS / MS spectra were identified as 361 different proteins. Healthy corals had a set of proteins that may be considered markers of holobiont homoeostasis, including tubulin, histone, Rab family, ribosomal, peridinin–chlorophyll a‐binding protein, F0F1‐type ATP synthase, alpha‐ iG protein, calmodulin and ADP ‐ribosylation factor. Cnidaria proteins found in healthy M. braziliensis were associated with Cnidaria – Symbiodinium endosymbiosis and included chaperones (hsp70, hsp90 and calreticulin), structural and membrane modelling proteins (actin) and proteins with functions related to intracellular vesicular traffic (Rab7 and ADP ‐ribosylation factor 1) and signal transduction (14‐3‐3 protein and calmodulin). WPS resulted in a clear shift in the predominance of proteins, from those related to aerobic nitrogen‐fixing bacteria (i.e. Rhizobiales, Sphingomonadales and Actinomycetales ) in healthy corals to those produced by facultative/anaerobic sulphate‐reducing bacteria (i.e. Enterobacteriales , Alteromonadales , Clostridiales and Bacteroidetes ) in WPS corals. BBD corals developed a diverse community dominated by cyanobacteria and sulphur cycle bacteria. Hsp60, hsp90 and adenosylhomocysteinase proteins were produced mainly by cyanobacteria in BBD corals, which is consistent with elevated oxidative stress in hydrogen sulphide‐ and cyanotoxin‐rich environments. This study demonstrates the usefulness of metaproteomics for gaining better comprehension of coral metabolic status in health and disease, especially in reef systems such as the Abrolhos that are suffering from the increase in global and local threatening events.

Growth of juvenile steelhead Oncorhynchus mykiss under size‐selective pressure limited by seasonal bioenergetic and environmental constraints - J. N. Thompson; D. A. Beauchamp (Journal of Fish Biology, 2016)
Increased freshwater growth of juvenile steelhead Oncorhynchus mykiss improved survival to smolt and adult stages, thus prompting an examination of factors affecting growth during critical periods that influenced survival through subsequent life stages. For three tributaries with contrasting thermal regimes, a bioenergetics model was used to evaluate how feeding rate and energy density of prey influenced seasonal growth and stage‐specific survival of juvenile O. mykiss . Sensitivity analysis examined target levels for feeding rate and energy density of prey during the growing season that improved survival to the smolt and adult stages in each tributary. Simulated daily growth was greatest during warmer months (1 July to 30 September), whereas substantial body mass was lost during cooler months (1 December to 31 March). Incremental increases in annual feeding rate or energy density of prey during summer broadened the temperature range at which faster growth occurred and increased the growth of the average juvenile to match those that survived to smolt and adult stages. Survival to later life stages could be improved by increasing feeding rate or energy density of the diet during summer months, when warmer water temperatures accommodated increased growth potential. Higher growth during the summer period in each tributary could improve resiliency during subsequent colder periods that lead to metabolic stress and weight loss. As growth and corresponding survival rates in fresh water are altered by shifting abiotic regimes, it will be increasingly important for fisheries managers to better understand the mechanisms affecting growth limitations in rearing habitats and what measures might maintain or improve growth conditions and survival.

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

Detecting grizzly bear use of ungulate carcasses using global positioning system telemetry and activity data - Michael R. Ebinger; Mark A. Haroldson; Frank T. van Manen; Cecily M. Costello; Daniel D. Bjornlie; Daniel J. Thompson; Kerry A. Gunther; Jennifer K. Fortin; Justin E. Teisberg; Shannon R. Pils; P. J. White; Steven L. Cain; et al. (Oecologia, 2016)

A road map for designing and implementing a biological monitoring program - Joel H. Reynolds; Melinda G. Knutson; Ken B. Newman; Emily D. Silverman; William L. Thompson (Environmental Monitoring and Assessment, 2016)

Spawn date explains variation in growth rate among families of hatchery reared Hood River steelhead (Oncorhynchus mykiss) - Neil F. Thompson; Mark R. Christie; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2016)

Quantitative immunoenzymatic detection of viral encephalopathy and retinopathy virus (betanodavirus) in sea bass Dicentrarchus labrax - N Nuñez‐Ortiz; V Stocchi; A Toffan; F Pascoli; N Sood; F Buonocore; S Picchietti; C Papeschi; A R Taddei; K D Thompson; G Scapigliati (Journal of Fish Diseases, 2016)
Viral encephalopathy and retinopathy disease caused by betanodavirus, genus of the family Nodaviridae, affects marine, wild and farmed species including sea bass, one of the most important farmed species in Europe. This work describes a reliable and sensitive indirect ELISA assay to detect betanodavirus in biological samples using a polyclonal antiserum (pAb 283) against the 283/I09 virus strain, the most common red‐spotted grouper nervous necrosis virus ( RGNNV ) genotype in the Mediterranean area, and a capture‐based ELISA using a monoclonal antibody (mAb 4C3) specific to a common epitope present on the capsid protein. Using adsorbed, purified VER v preparation, the detection limit of indirect ELISA was 2 μg mL −1 (3 × 10 5 TCID 50 per mL), whereas for capture‐based ELISA, the sensitivity for the antigen in solution was 17 μg mL −1 (35 × 10 5 TCID 50 per mL). The capture‐based ELISA was employed to detect VER v in brain homogenates of in vivo infected sea bass and resulted positive in 22 of 32 samples, some of these with a high viral load estimates (about 1.1 × 10 8 TCID 50 per mL). The ELISA system we propose may be helpful in investigations where coupling of viral content in fish tissues with the presence of circulating VER v‐specific IgM is required, or for use in samples where PCR is difficult to perform.

The effects of increasing dietary levels of amino acid-supplemented soy protein concentrate and constant dietary supplementation of phosphorus on growth, composition and immune responses of juvenile Atlantic salmon (Salmo salar L.) - C. Metochis; V. O. Crampton; K. Ruohonen; J. G. Bell; A. Adams; K. D. Thompson (Fish Physiology and Biochemistry, 2016)

Highly heritable resistance to root-lesion nematode (Pratylenchus thornei) in Australian chickpea germplasm observed using an optimised glasshouse method and multi-environment trial analysis - M. S. Rodda; K. B. Hobson; C. R. Forknall; R. P. Daniel; J. P. Fanning; D. D. Pounsett; S. Simpfendorfer; K. J. Moore; K. J. Owen; J. G. Sheedy; J. P. Thompson; G. J. Hollaway; et al. (Australasian Plant Pathology, 2016)

Genetic diversity and structure of the globally invasive tree, Paraserianthes lophantha subspecies lophantha, suggest an introduction history characterised by varying propagule pressure - G. D. Thompson; D. M. Richardson; J. R. U. Wilson; D. U. Bellstedt; J. J. Le Roux (Tree Genetics & Genomes, 2016)

Rapid treatment of vessels fouled with an invasive polychaete, Sabella spallanzanii , using a floating dock and chlorine as a biocide - Donald J. Morrisey; Craig V. Depree; Christopher W. Hickey; Don S. McKenzie; Irene Middleton; Matt D. Smith; Michael Stewart; Karen J. Thompson (Biofouling, 2016)

Serum androgens and prostate cancer risk: results from the placebo arm of the Prostate Cancer Prevention Trial - Jeannette M. Schenk; Cathee Till; Ann W. Hsing; Frank Z. Stanczyk; Zhihong Gong; Marian L. Neuhouser; Juergen K. Reichardt; Ashraful M. Hoque; William D. Figg; Phyllis J. Goodman; Catherine M. Tangen; Ian M. Thompson (Cancer Causes & Control, 2016)

Piscine reovirus, but not Jaundice Syndrome, was transmissible to Chinook Salmon, Oncorhynchus tshawytscha (Walbaum), Sockeye Salmon, Oncorhynchus nerka (Walbaum), and Atlantic Salmon, Salmo salar L. - K A Garver; G D Marty; S N Cockburn; J Richard; L M Hawley; A Müller; R L Thompson; M K Purcell; S Saksida (Journal of Fish Diseases, 2016)
A Jaundice Syndrome occurs sporadically among sea‐pen‐farmed Chinook Salmon in British Columbia, the westernmost province of Canada. Affected salmon are easily identified by a distinctive yellow discolouration of the abdominal and periorbital regions. Through traditional diagnostics, no bacterial or viral agents were cultured from tissues of jaundiced Chinook Salmon; however, piscine reovirus (PRV) was identified via RT‐ rPCR in all 10 affected fish sampled. By histopathology, Jaundice Syndrome is an acute to peracute systemic disease, and the time from first clinical signs to death is likely

Physiological and molecular responses to an acute bout of reduced-exertion high-intensity interval training (REHIT) - R. S. Metcalfe; F. Koumanov; J. S. Ruffino; K. A. Stokes; G. D. Holman; D. Thompson; N. B. J. Vollaard (European Journal of Applied Physiology, 2015)

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Medical Advocacy and Supportive Environments for African-Americans Following Abnormal Mammograms - Yamile Molina; Bridgette H. Hempstead; Jacci Thompson-Dodd; Shauna Rae Weatherby; Claire Dunbar; Sarah D. Hohl; Rachel C. Malen; Rachel M. Ceballos (Journal of Cancer Education, 2015)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Stormwater runoff to an impaired lake: impacts and solutions - Alan D. Steinman; Elaine Sterrett Isely; Kurt Thompson (Environmental Monitoring and Assessment, 2015)

Estimating surface NO2 and SO2 mixing ratios from fast-response total column observations and potential application to geostationary missions - T. Knepp; M. Pippin; J. Crawford; G. Chen; J. Szykman; R. Long; L. Cowen; A. Cede; N. Abuhassan; J. Herman; R. Delgado; J. Compton; et al. (Journal of Atmospheric Chemistry, 2015)

Bay breeze influence on surface ozone at Edgewood, MD during July 2011 - Ryan M. Stauffer; Anne M. Thompson; Douglas K. Martins; Richard D. Clark; Daniel L. Goldberg; Christopher P. Loughner; Ruben Delgado; Russell R. Dickerson; Jeffrey W. Stehr; Maria A. Tzortziou (Journal of Atmospheric Chemistry, 2015)

Fermentation of Dilute Acid Pretreated Populus by Clostridium thermocellum, Caldicellulosiruptor bescii, and Caldicellulosiruptor obsidiansis - Kelsey L. Yee; Miguel Rodriguez; Choo Y. Hamilton; Scott D. Hamilton-Brehm; Olivia A. Thompson; James G. Elkins; Brian H. Davison; Jonathan R. Mielenz (BioEnergy Research, 2015)

Isolating weather effects from seasonal activity patterns of a temperate North American Colubrid - Andrew D. George; Frank R. Thompson; John Faaborg (Oecologia, 2015)

Genetic variation and structure in the neotropical tree, Manilkara zapota (L) P. Royen (Sapotaceae) used by the ancient Maya - K. M. Thompson; T. M. Culley; A. M. Zumberger; D. L. Lentz (Tree Genetics & Genomes, 2015)

Increasing frequency of extreme fire weather in Canada with climate change - Xianli Wang; Dan K. Thompson; Ginny A. Marshall; Cordy Tymstra; Richard Carr; Mike D. Flannigan (Climatic Change, 2015)

Examination of the early infection stages of koi herpesvirus ( KHV ) in experimentally infected carp, C yprinus carpio L . using in situ hybridization - S J Monaghan; K D Thompson; A Adams; J Kempter; S M Bergmann (Journal of Fish Diseases, 2015)
Koi herpesvirus ( KHV ) causes a highly infectious disease afflicting common carp and koi, C yprinus carpio L. Various molecular and antibody‐based detection methods have been used to elucidate the rapid attachment and dissemination of the virus throughout carp tissues, facilitating ongoing development of effective diagnostic approaches. In situ hybridization ( ISH ) was used here to determine the target tissues of KHV during very early infection, after infecting carp with a highly virulent KHV isolate. Analysis of paraffin‐embedded tissues (i.e. gills, skin, spleen, kidney, gut, liver and brain) during the first 8 h and following 10 days post‐infection (hpi; dpi) revealed positive signals in skin mucus, gills and gut sections after only 1 hpi. Respiratory epithelial cells were positive as early as 2 hpi. Viral DNA was also detected within blood vessels of various tissues early in the infection. Notable increases in signal abundance were observed in the gills and kidney between 5 and 10 dpi, and viral DNA was detected in all tissues except brain. This study suggests that the gills and gut play an important role in the early pathogenesis of this Alloherpesvirus, in addition to skin, and demonstrates ISH as a useful diagnostic tool for confirmation of acutely infected carp.

How robust is the pre-1931 National Climatic Data Center—climate divisional dataset? Examples from Georgia and Louisiana - Jason Allard; Clint Thompson; Barry D. Keim (Theoretical and Applied Climatology, 2015)

The VMAT-2 inhibitor tetrabenazine alters effort-related decision making as measured by the T-maze barrier choice task: reversal with the adenosine A2A antagonist MSX-3 and the catecholamine uptake blocker bupropion - Samantha E. Yohn; Christian Thompson; Patrick A. Randall; Christie A. Lee; Christa E. Müller; Younis Baqi; Mercè Correa; John D. Salamone (Psychopharmacology, 2015)

Acceleration of cyanobacterial dominance in north temperate‐subarctic lakes during the Anthropocene - Zofia E. Taranu; Irene Gregory‐Eaves; Peter R. Leavitt; Lynda Bunting; Teresa Buchaca; Jordi Catalan; Isabelle Domaizon; Piero Guilizzoni; Andrea Lami; Suzanne McGowan; Heather Moorhouse; Giuseppe Morabito; et al. (Ecology Letters, 2015)
Increases in atmospheric temperature and nutrients from land are thought to be promoting the expansion of harmful cyanobacteria in lakes worldwide, yet to date there has been no quantitative synthesis of long‐term trends. To test whether cyanobacteria have increased in abundance over the past ~ 200 years and evaluate the relative influence of potential causal mechanisms, we synthesised 108 highly resolved sedimentary time series and 18 decadal‐scale monitoring records from north temperate‐subarctic lakes. We demonstrate that: (1) cyanobacteria have increased significantly since c . 1800 ce , (2) they have increased disproportionately relative to other phytoplankton, and (3) cyanobacteria increased more rapidly post c . 1945 ce . Variation among lakes in the rates of increase was explained best by nutrient concentration (phosphorus and nitrogen), and temperature was of secondary importance. Although cyanobacterial biomass has declined in some managed lakes with reduced nutrient influx, the larger spatio‐temporal scale of sedimentary records show continued increases in cyanobacteria throughout the north temperate‐subarctic regions.

Transcriptional Regulatory Events Initiated by Ascl1 and Neurog2 During Neuronal Differentiation of P19 Embryonic Carcinoma Cells - Holly S. Huang; Tanya M. Redmond; Ginger M. Kubish; Shweta Gupta; Robert C. Thompson; David L. Turner; Michael D. Uhler (Journal of Molecular Neuroscience, 2015)

Rare germline copy number deletions of likely functional importance are implicated in endometrial cancer predisposition - Gemma L. Moir-Meyer; John F. Pearson; Felicity Lose; Rodney J. Scott; Mark McEvoy; John Attia; Elizabeth G. Holliday; Paul D. Pharoah; Alison M. Dunning; Deborah J. Thompson; Douglas F. Easton; Amanda B. Spurdle; et al. (Human Genetics, 2015)

Differential proteomic responses of selectively bred and wild‐type Sydney rock oyster populations exposed to elevated CO 2 - E. L. Thompson; W. O'Connor; L. Parker; P. Ross; D. A Raftos (Molecular Ecology, 2015)
Previous work suggests that larvae from Sydney rock oysters that have been selectively bred for fast growth and disease resistance are more resilient to the impacts of ocean acidification than nonselected, wild‐type oysters. In this study, we used proteomics to investigate the molecular differences between oyster populations in adult Sydney rock oysters and to identify whether these form the basis for observations seen in larvae. Adult oysters from a selective breeding line (B2) and nonselected wild types ( WT ) were exposed for 4 weeks to elevated p CO 2 (856 μatm) before their proteomes were compared to those of oysters held under ambient conditions (375 μatm p CO 2 ). Exposure to elevated p CO 2 resulted in substantial changes in the proteomes of oysters from both the selectively bred and wild‐type populations. When biological functions were assigned, these differential proteins fell into five broad, potentially interrelated categories of subcellular functions, in both oyster populations. These functional categories were energy production, cellular stress responses, the cytoskeleton, protein synthesis and cell signalling. In the wild‐type population, proteins were predominantly upregulated. However, unexpectedly, these cellular systems were downregulated in the selectively bred oyster population, indicating cellular dysfunction. We argue that this reflects a trade‐off, whereby an adaptive capacity for enhanced mitochondrial energy production in the selectively bred population may help to protect larvae from the effects of elevated CO 2 , whilst being deleterious to adult oysters.

Sensitivity of seven PCR s for early detection of koi herpesvirus in experimentally infected carp, C yprinus carpio L ., by lethal and non‐lethal sampling methods - S J Monaghan; K D Thompson; A Adams; S M Bergmann (Journal of Fish Diseases, 2015)
Koi herpesvirus ( KHV ) causes an economically important, highly infectious disease in common carp and koi, Cyprinus carpio L. Since the occurrence of mass mortalities worldwide, highly specific and sensitive molecular diagnostic methods have been developed for KHV detection. The sensitivity and reliability of these assays have essentially focused at the detection of low viral DNA copy numbers during latent or persistent infections. However, the efficacy of these assays has not been investigated with regard to low‐level viraemia during acute infection stages. This study was conducted to compare the sensitivity of seven different polymerase chain reaction ( PCR ) assays to detect KHV during the first hours and days post‐infection (hpi; dpi), using lethal and non‐lethal sampling methods. The results highlight the limitations of the assays for detecting virus during the first 4 dpi despite rapid mortality in experimentally infected carp. False‐negative results were associated with time post‐infection and the tissue sampled. Non‐lethal sampling appears effective for KHV screening, with efficient detection in mucus samples obtained from external swabs during this early infection period ( PCR assays. Non‐lethal sampling may improve the reliability of KHV detection in subclinical, acutely infected carp.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Using extended pedigrees to identify novel autism spectrum disorder (ASD) candidate genes - Marc Woodbury-Smith; Andrew D. Paterson; Bhooma Thiruvahindrapduram; Anath C. Lionel; Christian R. Marshall; Daniele Merico; Bridget A. Fernandez; Eric Duku; James S. Sutcliffe; Irene O’Conner; Christina Chrysler; Ann Thompson; et al. (Human Genetics, 2015)

A tree well travelled: global genetic structure of the invasive tree Acacia saligna - Genevieve D. Thompson; Dirk U. Bellstedt; David M. Richardson; John R. U. Wilson; Johannes J. Le Roux (Journal of Biogeography, 2015)
Aim Invasiveness of an introduced species in one region is often used to predict risk and inform management of the same species elsewhere. This assumes that entities in both regions are equivalent in their ecology and response to management. However, intraspecific genetic variation can result in differences in performance between regions. We conducted population genetic and phylogeographic analyses of the widely introduced and intraspecifically diverse Australian tree species Acacia saligna, in order to improve our understanding of its worldwide invasion history. Location The native range of A. saligna in Western Australia and introduced ranges in eastern Australia, Israel, Italy, New Zealand, Portugal, South Africa, Spain and the USA . Methods We analysed microsatellite genotype data obtained from 447 individuals of A. saligna (including reference populations of known subspecies lineages) using Bayesian assignment analysis. We also reconstructed parsimony networks and a phylogeny using data from the nuclear external transcribed spacer (ETS) gene region for a subset of 120 individuals. Results There was no consistent genetic pattern in introduced populations in different parts of the world. All three subspecies lineages of A. saligna have been moved around the world, showing high levels of admixture in some introduced populations. A previously identified novel and cultivated South African lineage was also identified in Portugal and Italy. Main conclusions With different subspecies lineages present in different regions globally, it is unclear exactly how effective management approaches of invasions in one region will be in other regions. For example, the successful biological control agents against cultivated lineages of A. saligna in South Africa will probably be effective against similar genotypes in Portugal but not against dissimilar lineages present elsewhere. Further work is needed to conclusively link the relative extent of invasions to genetic differences, and to determine whether genetic novelty can explain the widespread invasions of A. saligna observed in South Africa and Portugal.

Emergent stability in a large, free‐flowing watershed - Jonathan W. Moore; Michael P. Beakes; Holly K. Nesbitt; Justin D. Yeakel; David A. Patterson; Lisa A. Thompson; Corey C. Phillis; Douglas C. Braun; Corinna Favaro; David Scott; Charmaine Carr-Harris; William I. Atlas (Ecology, 2015)
While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.

Sex reversal, selection against hatchery females or wild males does not explain differences in sex ratio between first generation hatchery and wild steelhead, Oncorhynchus mykiss - Neil F. Thompson; Kathleen S. Cole; Laura A. McMahon; Melanie L. Marine; Lyle D. Curtis; Michael S. Blouin (Environmental Biology of Fishes, 2015)

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Understanding the Patient-Provider Communication Needs and Experiences of Latina and Non-Latina White Women Following an Abnormal Mammogram - Yamile Molina; Sarah D. Hohl; Linda K. Ko; Edgar A. Rodriguez; Beti Thompson; Shirley A. A. Beresford (Journal of Cancer Education, 2014)

Developmental anatomy of blueberry (Vaccinium corymbosum L. ‘Aurora’) shoot regeneration - Thompson D. Pizzolato; James J. Polashock; Kate L. Thomas; Sherry L. Kitto (In Vitro Cellular & Developmental Biology - Plant, 2014)

Assessing Potato Psyllid Haplotypes in Potato Crops in the Pacific Northwestern United States - Kylie D. Swisher; Venkatesan G. Sengoda; Jacob Dixon; Joseph E. Munyaneza; Alexzandra F. Murphy; Silvia I. Rondon; Brandon Thompson; Alexander V. Karasev; Erik J. Wenninger; Nora Olsen; James M. Crosslin (American Journal of Potato Research, 2014)

Biodiversity and ecosystem services: lessons from nature to improve management of planted forests for REDD-plus - Ian D. Thompson; Kimiko Okabe; John A. Parrotta; Eckehard Brockerhoff; Hervé Jactel; David I. Forrester; Hisatomo Taki (Biodiversity and Conservation, 2014)

Stakeholders’ Responses to the Use of Innovative Water Trading Systems in East Anglia, England - D. M. Lumbroso; C. Twigger-Ross; J. Raffensperger; J. J. Harou; M. Silcock; A. J. K. Thompson (Water Resources Management, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Neuroimaging and genetic risk for Alzheimer’s disease and addiction-related degenerative brain disorders - Florence F. Roussotte; Madelaine Daianu; Neda Jahanshad; Cassandra D. Leonardo; Paul M. Thompson (Brain Imaging and Behavior, 2014)

Loss of a large grazer impacts savanna grassland plant communities similarly in North America and South Africa - Stephanie Eby; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Navashni Govender; Nicole Hagenah; Sally E. Koerner; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Oecologia, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Human and Non-Human Primate Intestinal FcRn Expression and Immunoglobulin G Transcytosis - Pamela J. Hornby; Philip R. Cooper; Connie Kliwinski; Edwin Ragwan; John R. Mabus; Benjamin Harman; Suzanne Thompson; Amanda L. Kauffman; Zhengyin Yan; Susan H. Tam; Haimanti Dorai; Gordon D. Powers; et al. (Pharmaceutical Research, 2014)

Kinetics of short-term carbon mineralization in roots of biofuel crops in soils - F. A. Rivas; M. A. Tabatabai; D. C. Olk; M. L. Thompson (Biology and Fertility of Soils, 2014)

Plant community response to loss of large herbivores differs between North American and South African savanna grasslands - Sally E. Koerner; Deron E. Burkepile; Richard W. S. Fynn; Catherine E. Burns; Stephanie Eby; Navashni Govender; Nicole Hagenah; Katherine J. Matchett; Dave I. Thompson; Kevin R. Wilcox; Scott L. Collins; Kevin P. Kirkman; et al. (Ecology, 2014)
Herbivory and fire shape plant community structure in grass‐dominated ecosystems, but these disturbance regimes are being altered around the world. To assess the consequences of such alterations, we excluded large herbivores for seven years from mesic savanna grasslands sites burned at different frequencies in North America (Konza Prairie Biological Station, Kansas, USA) and South Africa (Kruger National Park). We hypothesized that the removal of a single grass‐feeding herbivore from Konza would decrease plant community richness and shift community composition due to increased dominance by grasses. Similarly, we expected grass dominance to increase at Kruger when removing large herbivores, but because large herbivores are more diverse, targeting both grasses and forbs, at this study site, the changes due to herbivore removal would be muted. After seven years of large‐herbivore exclusion, richness strongly decreased and community composition changed at Konza, whereas little change was evident at Kruger. We found that this divergence in response was largely due to differences in the traits and numbers of dominant grasses between the study sites rather than the predicted differences in herbivore assemblages. Thus, the diversity of large herbivores lost may be less important in determining plant community dynamics than the functional traits of the grasses that dominate mesic, disturbance‐maintained savanna grasslands.

Multiple-Point Simulation with an Existing Reservoir Model as Training Image - L. Y. Hu; Y. Liu; C. Scheepens; A. W. Shultz; R. D. Thompson (Mathematical Geosciences, 2014)

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

Riding the storm: the response of Plantago lanceolata to simulated tidal flooding - Mick E. Hanley; P. Y. S. Yip; S. Hoggart; D. T. Bilton; S. D. Rundle; R. C. Thompson (Journal of Coastal Conservation, 2013)

Toenail iron, genetic determinants of iron status, and the risk of glioma - Gabriella M. Anic; Melissa H. Madden; Reid C. Thompson; L. Burton Nabors; Jeffrey J. Olson; Renato V. LaRocca; James E. Browning; John D. Brockman; Peter A. Forsyth; Kathleen M. Egan (Cancer Causes & Control, 2013)

Relationship Between Woody Plant Colonization and Typha L. Encroachment in Stormwater Detention Basins - Priscilla Bocskor Plumb; Susan D. Day; Theresa M. Wynn-Thompson; John R. Seiler (Environmental Management, 2013)

Lichen Conservation in Heavily Managed Boreal Forests - RICHARD TROY MCMULLIN; IAN D. THOMPSON; STEVEN G. NEWMASTER (Conservation Biology, 2013)
Lichens are an important component of the boreal forest, where they are long lived, tend to accumulate in older stands, and are a major food source for the threatened woodland caribou (Rangifer tarandus caribou) . To be fully sustainable, silvicultural practices in the boreal forest must include the conservation of ecological integrity. Dominant forest management practices, however, have short‐term negative effects on lichen diversity, particularly the application of herbicides. To better understand the long‐term effects of forest management, we examined lichen regeneration in 35 mixed black spruce (Picea mariana) and jack pine (Pinus banksiana) forest stands across northern Ontario to determine recovery following logging and postharvest silvicultural practices. Our forest stands were 25–40 years old and had undergone 3 common sivilcultural treatments that included harvested and planted; harvested, planted, and treated with N‐[phosphonomethyl] glycine (glyphosate); and harvested, planted, and treated with 2,4‐dichlorophenoxyacetic acid (2,4‐D). Forest stands with herbicide treatments had lower lichen biomass and higher beta and gamma diversity than planted stands that were not treated chemically or control stands. In northwestern Ontario, planted stands that were not treated chemically had significantly greater (p Conservación de Líquenes en Bosques Boreales Manejados Intensivamente

Effects of neuromuscular fatigue on the electromechanical delay of the leg extensors and flexors in young and old men - E. C. Conchola; B. J. Thompson; D. B. Smith (European Journal of Applied Physiology, 2013)

Metagenomic identification, seasonal dynamics, and potential transmission mechanisms of a Daphnia ‐associated single‐stranded DNA virus in two temperate lakes - Ian Hewson; Gabriel Ng; WenFang Li; Brenna A. LaBarre; Isabel Aguirre; Jorge G. Barbosa; Mya Breitbart; Anthony W. Greco; Colleen M. Kearns; Alexander Looi; Lindsay R. Schaffner; Philip D. Thompson; et al. (Limnology and Oceanography, 2013)
We used a metagenomic approach to identify viruses that may be involved in the ecology of Daphnia spp. in Oneida and Cayuga lakes (upstate New York). We identified several highly represented, putative eukaryotic, circular, single‐stranded deoxyribonucleic acid (DNA) viral genomes. Among these, we discovered a genotype similar in both sequence and genomic architecture to a virus previously reported from a hyperthermal lake that shares characteristics of both single‐stranded ribonucleic acid (RNA) and single‐stranded DNA viruses. We used quantitative polymerase chain reactions to study the prevalence and viral load of both positive‐sense and negative‐sense strands of the Daphnia mendotae ‐associated (Cladocera) hybrid virus (DMClaHV) over a summer season in Oneida and Cayuga lakes. DMClaHV had high prevalence within Daphnia populations, where viral load and the proportion of virus‐positive individuals were higher preceding host population decline. DMClaHV viral load was different between two species of Daphnia ( D. mendotae and D. retrocurva ), and the dynamics between viruses and their hosts varied between the two lakes. We detected DMClaHV in eggs (ephippia) retrieved from Oneida Lake sediments with an estimated age of 30 yr. Using transmission electron microscopy, we observed small (20 nm diameter) virus‐like particles in Daphnia that were well away from gut tissues and not associated with intracellular parasites. Because Daphnia plays a critical role in many lake ecosystems, DMClaHV may have important effects on herbivory and thus carbon flow through the lake ecosystem.

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

A polygon-based modeling approach to assess exposure of resources and assets to wildfire - Matthew P. Thompson; Joe Scott; Jeffrey D. Kaiden; Julie W. Gilbertson-Day (Natural Hazards, 2013)

The effect of multiple primary rules on population-based cancer survival - Hannah K. Weir; Christopher J. Johnson; Trevor D. Thompson (Cancer Causes & Control, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Influence of heat stress and exercise intensity on vastus lateralis muscle and prefrontal cortex oxygenation - Julien D. Périard; Martin W. Thompson; Corinne Caillaud; Valentina Quaresima (European Journal of Applied Physiology, 2013)

Carbon Accumulation Patterns During Post-Fire Succession in Cajander Larch (Larix cajanderi) Forests of Siberia - Heather D. Alexander; Michelle C. Mack; Scott Goetz; Michael M. Loranty; Pieter S. A. Beck; Kamala Earl; Sergey Zimov; Sergey Davydov; Catharine C. Thompson (Ecosystems, 2012)

Ultrastructural morphogenesis of salmonid alphavirus 1 - T K Herath; H W Ferguson; K D Thompson; A Adams; R H Richards (Journal of Fish Diseases, 2012)
Studies on the ultrastructural morphogenesis of viruses give an insight into how the host cell mechanisms are utilized for new virion synthesis. A time course examining salmonid alphavirus 1 ( SAV 1) assembly was performed by culturing the virus on Chinook salmon embryo cells ( CHSE ‐214). Different stages of viral replication were observed under electron microscopy. Virus‐like particles were observed inside membrane‐bound vesicles as early as 1 h following contact of the virus with the cells. Membrane‐dependent replication complexes were observed in the cytoplasm of the cells, with spherules found at the periphery of late endosome‐like vacuoles. The use of intracellular membranes for RNA replication is similar to other positive‐sense single‐stranded RNA (+ss RNA ) viruses. The number of Golgi apparatus and associated vacuoles characterized by ‘fuzzy’‐coated membranes was greater in virus‐infected cells. The mature enveloped virions started to bud out from the cells at approximately 24 h post‐infection. These observations suggest that the pathway used by SAV 1 for the generation of new virus particles in vitro is comparable to viral replication observed with mammalian alphaviruses but with some interesting differences.

Geographic divergence in a species‐rich symbiosis: interactions between Monterey pines and ectomycorrhizal fungi - Jason D. Hoeksema; Jesus Vargas Hernandez; Deborah L. Rogers; Luciana Luna Mendoza; John N. Thompson (Ecology, 2012)
A key problem in evolutionary biology is to understand how multispecific networks are reshaped by evolutionary and coevolutionary processes as they spread across contrasting environments. To address this problem, we need studies that explicitly evaluate the multispecific guild structure of coevolutionary processes and some of their key outcomes such as local adaptation. We evaluated geographic variation in interactions between most extant native populations of Monterey pine ( Pinus radiata ) and the associated resistant‐propagule community (RPC) of ectomycorrhizal (EM) fungi, using a reciprocal cross‐inoculation experiment with all factorial combinations of plant genotypes and soils with fungal guilds from each population. Our results suggest that the pine populations have diverged in community composition of their RPC fungi, and have also diverged genetically in several traits related to interactions of seedlings with particular EM fungi, growth, and biomass allocation. Patterns of genetic variation among pine populations for compatibility with EM fungi differed for the three dominant species of EM fungi, suggesting that Monterey pines can evolve differently in their compatibility with different symbiont species.

Use of partition coefficients in flow-limited physiologically-based pharmacokinetic modeling - Matthew D. Thompson; Daniel A. Beard; Fan Wu (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Cultivation shapes genetic novelty in a globally important invader - GENEVIEVE D. THOMPSON; DIRK U. BELLSTEDT; MARGARET BYRNE; MELISSA A. MILLAR; DAVID M. RICHARDSON; JOHN R.U. WILSON; JOHANNES J. LE ROUX (Molecular Ecology, 2012)
Acacia saligna is a species complex that has become invasive in a number of countries worldwide where it has caused substantial environmental and economic impacts. Understanding genetic and other factors contributing to its success may allow managers to limit future invasions of closely related species. We used three molecular markers to compare the introduced range (South Africa) to the native range (Western Australia). Nuclear markers showed that invasive populations are divergent from native populations and most closely related to a cultivated population in Western Australia. We also found incongruence between nuclear and chloroplast data that, together with the long history of cultivation of the species, suggest that introgressive hybridization (coupled with chloroplast capture) may have occurred within A. saligna. While we could not definitively prove introgression, the genetic distance between cultivated and native A. saligna populations was comparable to known interspecific divergences among other Acacia species. Therefore, cultivation, multiple large‐scale introductions and possibly introgressive hybridization have rapidly given rise to the divergent genetic entity present in South Africa. This may explain the known global variation in invasiveness and inaccuracy of native bioclimatic models in predicting potential distributions.

The role of aerobic fitness and exercise intensity on endurance performance in uncompensable heat stress conditions - Julien D. Périard; Corinne Caillaud; Martin W. Thompson (European Journal of Applied Physiology, 2012)

Effect of prolonged exercise and pre-exercise dietary manipulation on hepatic triglycerides in trained men - N. A. Johnson; D. van Overbeek; P. G. Chapman; M. W. Thompson; T. Sachinwalla; J. George (European Journal of Applied Physiology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Higher incidence of clear cell adenocarcinoma of the cervix and vagina among women born between 1947 and 1971 in the United States - Emily K. Smith; Mary C. White; Hannah K. Weir; Lucy A. Peipins; Trevor D. Thompson (Cancer Causes & Control, 2012)

Studies on the effect of temperature and pH on the inactivation of fish viral and bacterial pathogens - P F Dixon; D A Smail; M Algoët; T S Hastings; A Bayley; H Byrne; M Dodge; A Garden; C Joiner; E Roberts; D Verner‐Jeffreys; F Thompson (Journal of Fish Diseases, 2012)
Disposal of fish by‐products in the European Community must comply with Regulation (EC) No 1069/2009 which categorizes animal by‐products according to risk, and specifies methods of disposal of by‐products according to that risk. There is provision under the regulation for composting or ensiling to be used for by‐products from aquatic animals. Biosecurity considerations require knowledge of the parameters of time and temperature, or time and pH, required to inactivate any fish pathogens that may be present. To provide those data, we undertook laboratory studies on the inactivation of a number of fish pathogenic viruses and bacteria at 60 °C, pH 4.0 and pH 12.0 as a preliminary to conducting subsequent trials with the most resistant viruses and bacteria in fish tissues. The most resistant bacterium to 60 °C, pH 4.0 as well as pH 12.0 was Lactococcus garvieae . Its concentration was reduced to the level of sensitivity of the test after 24–48 h exposure to 60 °C, but it survived for at least 7 days at pH 4.0 and 14 days at pH 12.0. The most resistant virus to 60 °C was infectious pancreatic necrosis virus, and to pH 12.0 was infectious salmon anaemia virus. The majority of the viruses tested survived exposure to pH 4.0 for up to 28 days. The results suggest that the process of acid ensiling alone is not an effective method for the inactivation of many viral and bacterial pathogens, and fish by‐products would need further treatment by a method approved under the regulation following ensiling, whereas alkaline or heat treatment are likely to provide an increased degree of biosecurity for on‐farm processing of mortalities.

Modelling water-level options for ecosystem services and assessment of climate change: Loktak Lake, northeast India - C. R. Singh; J. R. Thompson; D. G. Kingston; J. R. French (Hydrological Sciences Journal, 2011)

Evolution of anthropogenic and biomass burning emissions of air pollutants at global and regional scales during the 1980–2010 period - Claire Granier; Bertrand Bessagnet; Tami Bond; Ariela D’Angiola; Hugo Denier van der Gon; Gregory J. Frost; Angelika Heil; Johannes W. Kaiser; Stefan Kinne; Zbigniew Klimont; Silvia Kloster; Jean-François Lamarque; et al. (Climatic Change, 2011)

Primary care physician compliance with colorectal cancer screening guidelines - Jesse N. Nodora; William D. Martz; Erin L. Ashbeck; Elizabeth T. Jacobs; Patricia A. Thompson; María Elena Martínez (Cancer Causes & Control, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Field estimates of reproductive success in a model insect: behavioural surrogates are poor predictors of fitness - David J. Thompson; Christopher Hassall; Chris D. Lowe; Phillip C. Watts (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 905–913 Abstract Understanding, and therefore measuring, factors that determine fitness is a central problem in evolutionary biology. We studied a natural population of Coenagrion puella (Odonata: Zygoptera) over two entire breeding seasons, with over a thousand individuals uniquely marked and genotyped, and all mating events at the rendezvous site recorded. Using a parentage analysis, fitness of individuals in the first generation was quantified as the numbers of offspring that survived to maturity. Although mating behaviour can be predicted by environmental and demographical variables, the numbers of mature offspring produced (fitness) cannot, and crucially, are poorly correlated with behavioural observations of mating. While fitness of both sexes was positively related to mating behaviour and to female’s ectoparasite burden, these behavioural observations explained little more variance in offspring production than environmental and demographical variables. Thus, we demonstrate that behavioural measures of reproductive success are not necessarily reliable estimates of fitness in natural populations.

Neuromuscular function following prolonged intense self-paced exercise in hot climatic conditions - Julien D. Périard; Matthew N. Cramer; Phillip G. Chapman; Corinne Caillaud; Martin W. Thompson (European Journal of Applied Physiology, 2011)

Serum estrogen levels and prostate cancer risk in the prostate cancer prevention trial: a nested case–control study - Song Yao; Cathee Till; Alan R. Kristal; Phyllis J. Goodman; Ann W. Hsing; Catherine M. Tangen; Elizabeth A. Platz; Frank Z. Stanczyk; Juergen K. V. Reichardt; Li Tang; Marian L. Neuhouser; Regina M. Santella; et al. (Cancer Causes & Control, 2011)

Development of appropriate equations for physiologically based pharmacokinetic modeling of permeability-limited and flow-limited transport - Matthew D. Thompson; Daniel A. Beard (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Development of an aquatic pathogen database (AquaPathogen X) and its utilization in tracking emerging fish virus pathogens in North America - E J Emmenegger; E Kentop; T M Thompson; S Pittam; A Ryan; D Keon; J A Carlino; J Ranson; R B Life; R M Troyer; K A Garver; G Kurath (Journal of Fish Diseases, 2011)
The AquaPathogen X database is a template for recording information on individual isolates of aquatic pathogens and is freely available for download ( http://wfrc.usgs.gov ). This database can accommodate the nucleotide sequence data generated in molecular epidemiological studies along with the myriad of abiotic and biotic traits associated with isolates of various pathogens (e.g. viruses, parasites and bacteria) from multiple aquatic animal host species (e.g. fish, shellfish and shrimp). The cataloguing of isolates from different aquatic pathogens simultaneously is a unique feature to the AquaPathogen X database, which can be used in surveillance of emerging aquatic animal diseases and elucidation of key risk factors associated with pathogen incursions into new water systems. An application of the template database that stores the epidemiological profiles of fish virus isolates, called Fish ViroTrak, was also developed. Exported records for two aquatic rhabdovirus species emerging in North America were used in the implementation of two separate web‐accessible databases: the Molecular Epidemiology of Aquatic Pathogens infectious haematopoietic necrosis virus (MEAP‐IHNV) database ( http://gis.nacse.org/ihnv/ ) released in 2006 and the MEAP‐ viral haemorrhagic septicaemia virus ( http://gis.nacse.org/vhsv/ ) database released in 2010.

A Real-Time Risk Assessment Tool Supporting Wildland Fire Decisionmaking - David E. Calkin; Matthew P. Thompson; Mark A. Finney; Kevin D. Hyde (Journal of Forestry, 2011)
Development of appropriate management strategies for escaped wildland fires is complex. Fire managers need the ability to identify, in real time, the likelihood that wildfire will affect valuable developed and natural resources (e.g., private structures, public infrastructure, and natural and cultural resources). These determinations help guide where and when aggressive suppression is required to protect values and when fire may be allowed to burn to enhance ecosystem conditions. This article describes the primary components of the Wildland Fire Decision Support System (WFDSS), a geospatial decision support system developed by the US Forest Service. WFDSS provides state-of-the-art wildfire risk analysis, decision documentation, and long-term implementation planning. In particular, we describe how the two primary decision support analysis components of WFDSS, Fire Spread Probability (fire behavior) and Rapid Assessment of Values at Risk (resource assessment), fit into the current state of risk assessment tools for wildfire suppression decisionmaking.

Mutation deep within an intron of MSH2 causes Lynch syndrome - Mark Clendenning; Daniel D. Buchanan; Michael D. Walsh; Belinda Nagler; Christophe Rosty; Bryony Thompson; Amanda B. Spurdle; John L. Hopper; Mark A. Jenkins; Joanne P. Young (Familial Cancer, 2011)

Assessment of flipper tag site healing in gray seal pups using thermography - W. Paterson; P. P. Pomeroy; C. E. Sparling; S. Moss; D. Thompson; J. I. Currie; D. J. McCafferty (Marine Mammal Science, 2011)
Infrared thermography was used to monitor the healing process at flipper tag sites in gray seal ( Halichoerus grypus ) pups. We tested the hypothesis that tagging would result in a rise in surface temperature associated with tag site healing processes compared with adjacent untagged areas of the flipper. Prior to tagging thermal images were recorded of the dorsal side of hind flippers of pups tagged in early lactation ( n = 20) and at weaning ( n = 19) on the Isle of May, Scotland (56°11′N, 02°33′W) from October to December 2008. Pups tagged in early lactation were sampled again at late lactation, at weaning and then every 3 d for an average of 29 d post‐tagging while pups tagged at weaning were sampled every 3 d for an average of 17 d post‐tagging. Tag sites were also scored for signs of infection or swelling at each sampling. Results showed that (1) small temperature increases associated with wound healing processes around the tag site returned to pre‐tagging levels before animals leave the island and (2) there was little evidence of tagging‐related infections or tag loss irrespective of age at tagging.

The sensitivity of gap analysis to conservation targets - Ruppert Vimal; Ana S. L. Rodrigues; Raphaël Mathevet; John D. Thompson (Biodiversity and Conservation, 2011)

AKT1 polymorphisms are associated with risk for metabolic syndrome - Joseph M. Devaney; Heather Gordish-Dressman; Brennan T. Harmon; Margaret K. Bradbury; Stephanie A. Devaney; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Thomas B. Price; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; et al. (Human Genetics, 2011)

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2011)

Detection of Polymyxa graminis in a barley crop in Australia - J. P. Thompson; T. G. Clewett; R. E. Jennings; J. G. Sheedy; K. J. Owen; D. M. Persley (Australasian Plant Pathology, 2011)

Evaluation of data-driven network analysis approaches for functional connectivity MRI - Shella D. Keilholz; Matthew Magnuson; Garth Thompson (Brain Structure and Function, 2010)

Use of Acoustic Tools to Reveal Otherwise Cryptic Responses of Forest Elephants to Oil Exploration - PETER H. WREGE; ELIZABETH D. ROWLAND; BRUCE G. THOMPSON; NIKOLAS BATRUCH (Conservation Biology, 2010)
Most evaluations of the effects of human activities on wild animals have focused on estimating changes in abundance and distribution of threatened species; however, ecosystem disturbances also affect aspects of animal behavior such as short‐term movement, activity budgets, and reproduction. It may take a long time for changes in behavior to manifest as changes in abundance or distribution. Therefore, it is important to have methods with which to detect short‐term behavioral responses to human activity. We used continuous acoustic and seismic monitoring to evaluate the short‐term effects of seismic prospecting for oil on forest elephants (Loxodonta cyclotis) in Gabon, Central Africa. We monitored changes in elephant abundance and activity as a function of the frequency and intensity of acoustic and seismic signals from dynamite detonation and human activity. Elephants did not flee the area being explored; the relative number of elephants increased in a seasonal pattern typical of elsewhere in the ecosystem. In the exploration area, however, they became more nocturnal. Neither the intensity nor the frequency of dynamite blasts affected the frequency of calling or the daily pattern of elephant activity. Nevertheless, the shift of activity to nocturnal hours became more pronounced as human activity neared each monitored area of forest. This change in activity pattern and its likely causes would not have been detected through standard monitoring methods, which are not sensitive to behavioral changes over short time scales (e.g., dung transects, point counts) or cover a limited area (e.g., camera traps). Simultaneous acoustic monitoring of animal communication, human, and environmental sounds allows the documentation of short‐term behavioral changes in response to human disturbance.

Association of red‐mark syndrome with a Rickettsia ‐like organism and its connection with strawberry disease in the USA - M Metselaar; K D Thompson; R M L Gratacap; M J L Kik; S E LaPatra; S J Lloyd; D R Call; P D Smith; A Adams (Journal of Fish Diseases, 2010)
Red‐mark syndrome (RMS), a disease seen mostly in rainbow trout, Oncorhynchus mykiss , is of unknown aetiology. The research presented here indicates the presence of an intracellular bacterium in RMS‐affected fish. A positive reaction was observed using immunohistochemistry (IHC) with skin lesions, liver, kidney and spleen of affected fish sampled from several locations within the United Kingdom using two different polyclonal antisera raised against Piscirickettsia salmonis . The same reaction was also seen with a number of different anti‐ P. salmonis monoclonal antibodies (MAbs). A disease with similar clinical signs to RMS, referred to as strawberry disease (SD), has been reported in the USA. A Rickettsia ‐like organism (RLO) has recently been associated with SD based on analysis of 16S rDNA sequences. Using the same panel of anti‐ P. salmonis antibodies used to screen the RMS samples, similar staining was obtained in tissue of SD‐affected fish by IHC. A polymerase chain reaction (PCR) using RLO‐specific primers was also performed on RMS‐affected fish from the United Kingdom, and the samples were positive for the RLO 16S rRNA sequence. These findings suggest that the same aetiological agent may be responsible for RMS in the United Kingdom and SD in the USA.

African American's Self-Report Patterns Using the National Cancer Institute Colorectal Cancer Screening Questionnaire - Sula Hood; Vetta L. Sanders Thompson; Salimah Cogbill; Lauren D. Arnold; Michael Talley; Nicole M. Caito (Journal of Cancer Education, 2010)

Erratum to: Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. B. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

Measurement and estimation of plastic greenhouse reference evapotranspiration in a Mediterranean climate - M. D. Fernández; S. Bonachela; F. Orgaz; R. Thompson; J. C. López; M. R. Granados; M. Gallardo; E. Fereres (Irrigation Science, 2010)

Synthesis of “Difficult” Fluorescence Quenched Substrates of Granzyme C - Susan E. Northfield; Kade D. Roberts; Simon J. Mountford; Richard A. Hughes; Dion Kaiserman; Matthew Mangan; Robert N. Pike; Phillip I. Bird; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2010)

A polymorphism near IGF1 is associated with body composition and muscle function in women from the Health, Aging, and Body Composition Study - Matthew C. Kostek; Joseph M. Devaney; Heather Gordish-Dressman; Tamara B. Harris; Paul D. Thompson; Priscilla M. Clarkson; Theodore J. Angelopoulos; Paul M. Gordon; Niall M. Moyna; Linda S. Pescatello; Paul S. Visich; Robert F. Zoeller; et al. (European Journal of Applied Physiology, 2010)

Influence of Electromechanical Activity on Cardiac Differentiation of Mouse Embryonic Stem Cells - Worawan Limpitikul; Nicolas Christoforou; Susan A. Thompson; John D. Gearhart; Leslie Tung; Elizabeth A. Lipke (Cardiovascular Engineering and Technology, 2010)

Erratum to: Integrating advanced technologies for optimization of aerial herbicide applications - D. Thompson; D. Chartrand; B. Staznik; J. Leach; P. Hodgins (New Forests, 2010)

Integrating advanced technologies for optimization of aerial herbicide applications - D. Thompson; D. Chartrand; B. Staznik; J. Leach; P. Hodgins (New Forests, 2010)

Assessing the sensitivity of alpine lakes and ponds to nitrogen deposition in the Canadian Rocky Mountains - Conrad A. Murphy; Patrick L. Thompson; Rolf D. Vinebrooke (Hydrobiologia, 2010)

Undergraduate Cancer Training Program for Underrepresented Students: Findings from a Minority Institution/Cancer Center Partnership - Gloria D. Coronado; Mary A. O’Connell; Jennifer Anderson; Helena Löest; Dana Ogaz; Beti Thompson (Journal of Cancer Education, 2010)

Conservation Value of Sites of Hybridization in Peripheral Populations of Rare Plant Species - JOHN D. THOMPSON; MYRIAM GAUDEUL; MAX DEBUSSCHE (Conservation Biology, 2010)
Populations at the periphery of a species’ range are of interest to conservation biologists because they can show marked genetic differentiation from populations at the center of a range and because of potential hybridization among rare and common species. We examined two closely related Cyclamen species. One is a narrow endemic, and the other is more geographically widespread (both protected by law in continental southern France). We used floral traits and genetic variability to test for hybridization among the species in peripheral populations of the rare species. The species co‐occurred on Corsica in a disjunct, peripheral part of the distribution of the endemic species and in an ecologically marginal area for the widespread species. The two species have hybridized and the endemic species showed high levels of introgression with its widespread congener. Genetic and floral variability in sites with both species was markedly higher than in sites with a single species. Our results highlight the need for a conservation strategy that integrates hybrid populations because they represent a source of novel diversity that may have adaptive potential.

The rise of research on futures in ecology: rebalancing scenarios and predictions - Audrey Coreau; Gilles Pinay; John D. Thompson; Pierre‐Olivier Cheptou; Laurent Mermet (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1277–1286 Abstract Concern about the ecological consequences of global change has increasingly stimulated ecologists to examine the futures of ecological systems. Studying futures is not only a crucial element of the interaction between science, management and decision making , but also a critical research challenge per se , especially because futures cannot be observed or experimented on. In addition, researchers can encounter methodological and theoretical difficulties, which make interpretations and predictions problematic. In the literature which deals with futures of ecological systems two main lines of research can be distinguished: a predictive approach, which dominates the literature, can be contrasted with a rarer number of studies that elaborate potential scenarios for ecological systems. Scenario approaches currently concern mainly contacts with stakeholders or decision makers, or the use of climate scenarios to derive projections about ecological futures. We argue that a new direction for ecological futures research could be explored by using ecological scenarios in combination with predictive models to further fundamental ecological research, in addition to enhancing its applied value.

Differences in the antibody response and survival of genetically different varieties of common carp (Cyprinus carpio L.) vaccinated with a commercial Aeromonas salmonicida/A. hydrophila vaccine and challenged with A. hydrophila - Zsigmond Jeney; Tímea Rácz; Kim D. Thompson; Saravanane Poobalane; László Ardó; Alexandra Adams; Galina Jeney (Fish Physiology and Biochemistry, 2009)

Modelling the hydrological impacts of climate change on UK lowland wet grassland - J. R. Thompson; H. Gavin; A. Refsgaard; H. Refstrup Sørenson; D. J. Gowing (Wetlands Ecology and Management, 2009)

Lipopolysaccharide extraction: a phenol alternative - R M L Gratacap; K D Thompson; I R Bricknell; A Adams (Journal of Fish Diseases, 2009)

Synergistic effects of climate change and local stressors: CO 2 and nutrient‐driven change in subtidal rocky habitats - BAYDEN D. RUSSELL; JO‐ANNE I. THOMPSON; LAURA J. FALKENBERG; SEAN D. CONNELL (Global Change Biology, 2009)
Climate‐driven change represents the cumulative effect of global through local‐scale conditions, and understanding their manifestation at local scales can empower local management. Change in the dominance of habitats is often the product of local nutrient pollution that occurs at relatively local scales (i.e. catchment scale), a critical scale of management at which global impacts will manifest. We tested whether forecasted global‐scale change [elevated carbon dioxide (CO 2 ) and subsequent ocean acidification] and local stressors (elevated nutrients) can combine to accelerate the expansion of filamentous turfs at the expense of calcifying algae (kelp understorey). Our results not only support this model of future change, but also highlight the synergistic effects of future CO 2 and nutrient concentrations on the abundance of turfs. These results suggest that global and local stressors need to be assessed in meaningful combinations so that the anticipated effects of climate change do not create the false impression that, however complex, climate change will produce smaller effects than reality. These findings empower local managers because they show that policies of reducing local stressors (e.g. nutrient pollution) can reduce the effects of global stressors not under their governance (e.g. ocean acidification). The connection between research and government policy provides an example whereby knowledge (and decision making) across local through global scales provides solutions to some of the most vexing challenges for attaining social goals of sustainability, biological conservation and economic development.

Reproductive timing and patterns of development for the damselfly Coenagrion puella in the field - Chris D. Lowe; Ian F. Harvey; Phillip C. Watts; David J. Thompson (Ecology, 2009)
By a combination of detailed behavioral observations and molecular genetic approaches we have assessed development time, timing of first maturity, and the extent of genetic structure through the flying season in a wild population of the damselfly Coenagrion puella in England. This work provides the first estimate of development time (egg to mature adult) in the field based on individual damselflies. Development time was significantly longer for females than males. In contrast to reported laboratory studies, there was no difference in development times between different female color morphs. Development time ranged between 347 and 396 days and was negatively correlated with egg‐laying date. As a result eggs laid early in one season reach adult maturity relatively late in the next; concurrently individuals developing from eggs laid late mature relatively early. We speculate that this pattern of development is a direct physiological response to seasonal environmental variation and results in reproductive synchrony within a population. Size, specifically hind wing length, declined with development time in males, but not in females. In one of the two years of the study there was evidence for weak clustering of related individuals during the reproductive season. This appeared to be the result of developmental synchronization within families: variance in timing of maturation was smaller in full‐sib families than in half‐sib families or randomly assigned unrelated groups.

The tomato brassinosteroid receptor BRI1 increases binding of systemin to tobacco plasma membranes, but is not involved in systemin signaling - Robert Malinowski; Rebecca Higgins; Yuan Luo; Laverne Piper; Azka Nazir; Vikramjit S. Bajwa; Steven D. Clouse; Paul R. Thompson; Johannes W. Stratmann (Plant Molecular Biology, 2009)

Guidelines for the treatment of marine mammals in field research - N. J. Gales; W. D. Bowen; D. W. Johnston; K. M. Kovacs; C. L. Littnan; W. F. Perrin; J. E. Reynolds; P. M. Thompson (Marine Mammal Science, 2009)

On the variation of the tropospheric ozone over Indian region in relation to the meteorological parameters - S. D. Patil; B. Thompson; J. V. Revadekar (International Journal of Remote Sensing, 2009)

Survival costs associated with wood frog breeding migrations: effects of timber harvest and drought - Tracy A. G. Rittenhouse; Raymond D. Semlitsch; Frank R. Thompson (Ecology, 2009)
Migration presents a trade‐off for individuals between the potential fitness benefits of reaching high‐quality habitat vs. the potential costs of migration. Within an information‐theoretic framework, we examined the costs of migration for adult wood frogs ( Rana sylvatica ) in response to timber harvest and annual weather conditions using Cox proportional‐hazard estimates of survival. In 2004 prior to timber harvest, survival did not differ between the inside (0.75, SE = 0.078) and outside (0.73, SE = 0.235) of the circular timber harvest arrays (each 164 m radius). Following timber harvest, survival inside arrays in both 2005 and 2006 (0.22, SE = 0.065; 0.42, SE = 0.139) was lower than survival outside of the arrays and prior to harvest. Sources of mortality included predation in all years and desiccation in the drought year of 2005. The most‐supported models for explaining both predation and desiccation risks reflected behaviors as opposed to timber harvest or weather conditions. Both predation and desiccation risks increased when frogs made frequent movements or were located near breeding ponds. Optimal behaviors for reducing predation and desiccation risks were the same before and after timber harvest; however, the survival consequences for not adopting these behaviors were more severe following harvest. Our results provide empirical evidence for (1) the ecological pressures that influence migratory behavior and (2) differential survival in relation to migratory behavior which reveals why frogs move relatively long distances away from breeding sites.

Detection and identification of aquatic mycobacteria in formalin‐fixed, paraffin‐embedded fish tissues - F Pourahmad; K D Thompson; A Adams; R H Richards (Journal of Fish Diseases, 2009)
The isolation of mycobacteria from field samples is problematic, and isolation of the bacterium is sometimes not even attempted. The detection of mycobacteria through traditional histology using formalin‐fixed, paraffin‐embedded (FFPE) tissues is neither sensitive nor specific. However, detection of mycobacterial DNA from FFPE specimens, suspected of being infected with mammalian mycobacteriosis, is a routine clinical procedure. In the present study, a polymerase chain reaction (PCR)‐based method was used to detect and identify mycobacteria in FFPE specimens sampled from fish suspected of being infected with fish mycobacteriosis. A total of 45 fish tissue samples, comprising of 12 tissue samples obtained from experimentally infected fish and the remainder from fish naturally infected with mycobacteria, were analysed using a PCR protocol which amplifies a fragment of the mycobacterial 65 kDa heat‐shock protein ( hsp65 ) gene. PCR‐restriction enzyme analysis and/or sequencing were employed to further analyse the PCR amplicons. The PCR results were compared with those obtained by histology and culture. Mycobacterial DNA was detected in 34 of the 45 samples examined, of which 16 samples (47%) showed granulomatous reactions on histological examination. Using histology as the gold standard, no false‐negative PCR results were obtained. Also, considering the presence or absence of granulomas as a diagnostic criterion, the sensitivity and specificity of PCR in 42 of the FFPE tissues were 16/16 (100%) and 8/26 (∼30.8%), respectively. Corresponding microbiological cultures were available for 15 cases, of which 13 were pure Mycobacterium cultures. Of these, 13 were PCR positive (100% sensitivity and 50% specificity). The PCR‐based methods used here proved sensitive, specific and rapid for the detection of mycobacteria in routinely processed paraffin wax‐embedded and formalin‐fixed histological samples, and the results of the study suggest that this method has potential use in retrospective epidemiological studies.

The effect of angiotensin-converting enzyme genotype on acute mountain sickness and summit success in trekkers attempting the summit of Mt. Kilimanjaro (5,895 m) - Nicholas S. Kalson; Julian Thompson; Andrew J. Davies; Suzy Stokes; Mark D. Earl; Adam Whitehead; Ian Tyrrell-Marsh; Hannah Frost; Hugh Montgomery (European Journal of Applied Physiology, 2009)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Evaluation of the INNO‐LiPA mycobacteria v2 assay for identification of aquatic mycobacteria - F Pourahmad; K D Thompson; J B Taggart; A Adams; R H Richards (Journal of Fish Diseases, 2008)
Fifty‐seven isolates of mycobacteria comprising 10 reference strains, 47 field isolates and one non‐ Mycobacterium isolate were screened using commercial INNO‐LiPA v2 assay kits. All mycobacteria isolates tested hybridized with the Mycobacterium genus probe on the LiPA strip. All M. marinum , M. fortuitum and M. chelonae reference and field strains and three out of the four M. gordonae isolates hybridized to their corresponding species‐ or complex‐specific probes. Two cultures (a type strain and a field isolate) yielded mixed growth of two mycobacterial species, i.e. M. chelonae and M. fortuitum. A Mycobacterium isolate from one of these cultures was subsequently purified and correctly identified with the kit. However, sequence analysis of the 16S–23S rRNA internal transcribed spacer (ITS) region of various mycobacteria isolates revealed a misidentification of M. shottsii and M. pseudoshottsii with the kit because these isolates reacted with the M. marinum / M. ulcerans probe. Moreover, nine of the 13 field isolates presumed to be M. fortuitum from the results of the kit had closer ITS sequence homology with M. conceptionense , a species which, to our knowledge, has never been reported in fish. These findings highlight the need to redesign the M. fortuitum – M. peregrinum probe included in the INNO‐LiPA assay and to introduce additional complex‐specific probes into the kit. Nevertheless, the kit proved to be a rapid and reliable method for identifying mycobacteria in the aquatic environment and would be particularly useful in laboratories without sequencing facilities.

Allometric scaling of isometric biceps strength in adult females and the effect of body mass index - Robert F. Zoeller; Eric D. Ryan; Heather Gordish-Dressman; Thomas B. Price; Richard L. Seip; Theodore J. Angelopoulos; Niall M. Moyna; Paul M. Gordon; Paul D. Thompson; Eric P. Hoffman (European Journal of Applied Physiology, 2008)

Comparison of marker-based pairwise relatedness estimators on a pedigreed plant population - Marco C. A. M. Bink; Amy D. Anderson; W. Eric van de Weg; Elizabeth A. Thompson (Theoretical and Applied Genetics, 2008)

EMT and MET in carcinoma—clinical observations, regulatory pathways and new models - Erik W. Thompson; Elizabeth D. Williams (Clinical & Experimental Metastasis, 2008)

Gene expression profiling of M. truncatula transcription factors identifies putative regulators of grain legume seed filling - Jérôme Verdier; Klementina Kakar; Karine Gallardo; Christine Le Signor; Grégoire Aubert; Armin Schlereth; Christopher D. Town; Michael K. Udvardi; Richard D. Thompson (Plant Molecular Biology, 2008)

A Comparison of Female Mating Strategies in Pan troglodytes and Pongo spp. - R. M. Stumpf; M. Emery Thompson; C. D. Knott (International Journal of Primatology, 2008)

Effects of recovery time on phosphocreatine kinetics during repeated bouts of heavy-intensity exercise - S. C. Forbes; G. H. Raymer; J. M. Kowalchuk; R. T. Thompson; G. D. Marsh (European Journal of Applied Physiology, 2008)

Antioxidant Properties of Cultivars and Selections from the Colorado Potato Breeding Program - C. Stushnoff; D. Holm; M. D. Thompson; W. Jiang; H. J. Thompson; N. I. Joyce; P. Wilson (American Journal of Potato Research, 2008)

Strong genetic divergence indicates that congeneric damselflies Coenagrion puella and C. pulchellum (Odonata: Zygoptera: Coenagrionidae) do not hybridise - Chris D. Lowe; Ian F. Harvey; David J. Thompson; Phillip C. Watts (Hydrobiologia, 2008)

Dakota Diamond: An Exceptionally High Yielding, Cold Chipping Potato Cultivar with Long-Term Storage Potential - A. L. Thompson; B. L. Farnsworth; N. C. Gudmestad; G. A. Secor; D. A. Preston; J. R. Sowokinos; M. Glynn; H. Hatterman-Valenti (American Journal of Potato Research, 2008)

The sensitivity of annual grassland carbon cycling to the quantity and timing of rainfall - WENDY W. CHOU; WHENDEE L. SILVER; RANDALL D. JACKSON; ANDREW W. THOMPSON; BARBARA ALLEN‐DIAZ (Global Change Biology, 2008)
Global climate models predict significant changes to the rainfall regimes of the grassland biome, where C cycling is particularly sensitive to the amount and timing of precipitation. We explored the effects of both natural interannual rainfall variability and experimental rainfall additions on net C storage and loss in annual grasslands. Soil respiration and net primary productivity (NPP) were measured in treatment and control plots over four growing seasons (water years, or WYs) that varied in wet‐season length and the quantity of rainfall. In treatment plots, we increased total rainfall by 50% above ambient levels and simulated one early‐ and one late‐season storm. The early‐ and late‐season rain events significantly increased soil respiration for 2–4 weeks after wetting, while augmentation of wet‐season rainfall had no significant effect. Interannual variability in precipitation had large and significant effects on C cycling. We observed a significant positive relationship between annual rainfall and aboveground NPP across the study ( P =0.01, r 2 =0.69). Changes in the seasonal timing of rainfall significantly affected soil respiration. Abundant rainfall late in the wet season in WY 2004, a year with average total rainfall, led to greater net ecosystem C losses due to a ∼50% increase in soil respiration relative to other years. Our results suggest that C cycling in annual grasslands will be less sensitive to changes in rainfall quantity and more affected by altered seasonal timing of rainfall, with a longer or later wet season resulting in significant C losses from annual grasslands.

Impairment of movement-associated brain deactivation in multiple sclerosis: further evidence for a functional pathology of interhemispheric neuronal inhibition - S. C. Manson; C. Wegner; M. Filippi; F. Barkhof; C. Beckmann; O. Ciccarelli; N. De Stefano; Christian Enzinger; F. Fazekas; F. Agosta; A. Gass; J. Hirsch; et al. (Experimental Brain Research, 2008)

Influence of Nitrogen Addition and Plant Root Parameters on Phytoremediation of Pyrene-contaminated Soil - Oriana A. Thompson; Duane C. Wolf; John D. Mattice; Gregory J. Thoma (Water, Air, & Soil Pollution, 2008)

Toxicity of the Systemic Insecticide, Imidacloprid, to Forest Stream Insects and Microbial Communities - D. P. Kreutzweiser; K. P. Good; D. T. Chartrand; T. A. Scarr; D. G. Thompson (Bulletin of Environmental Contamination and Toxicology, 2008)

An inhibitor of methionine aminopeptidase type-2, PPI-2458, ameliorates the pathophysiological disease processes of rheumatoid arthritis - D. D. Lazarus; E. G. Doyle; S. G. Bernier; A. B. Rogers; M. T. Labenski; J. D. Wakefield; R. M. Karp; E. J. Clark; J. Lorusso; J. G. Hoyt; C. D. Thompson; G. Hannig; et al. (Inflammation Research, 2008)

Environmental analysis of groundwater in Mecosta County, Michigan - Alan D. Steinman; Bopi Biddanda; Xuefeng Chu; Kurt Thompson; Rick Rediske (Environmental Monitoring and Assessment, 2007)

Do age and baseline LDL cholesterol levels determine the effect of regular exercise on plasma lipoprotein cholesterol and apolipoprotein B levels? - Theodore J. Angelopoulos; Stephen A. Sivo; George A. Kyriazis; Jonathan D. Caplan; Robert F. Zoeller; Joshua Lowndes; Richard L. Seip; Paul D. Thompson (European Journal of Applied Physiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Identification of B‐cell epitopes on the betanodavirus capsid protein - J Z Costa; A Adams; J E Bron; K D Thompson; W G Starkey; R H Richards (Journal of Fish Diseases, 2007)
The pepscan procedure was used to identify betanodavirus B‐cell epitopes recognized by neutralizing mouse monoclonal antibodies (MAbs) and serum samples obtained from sea bass, Dicentrarchus labrax , naturally infected with betanodavirus. Pepscan was performed with a panel of thirty‐four 12‐mer synthetic peptides that mimicked the entire betanodavirus capsid protein. Sea bass serum samples reacted strongly with three regions of the capsid protein comprising amino acid residues 1–32, 91–162 and 181–212. The latter region was also recognized by neutralizing MAbs and coincided with a region of high antigenic propensity identified by an antigen prediction algorithm. These data suggest that a region of the betanodavirus capsid protein spanning amino acid residues 181–212 may represent a neutralization domain that could potentially be used to inform the development of nodavirus vaccines and immunodiagnostic reagents.

The interplay of pollination, costs of reproduction and plant size in maternal fertility limitation in perennial Paeonia officinalis - Emilie Andrieu; Max Debussche; Marta Galloni; John D. Thompson (Oecologia, 2007)

The impact of forest spread on a marginal population of a protected peony (Paeonia officinalis L.): the importance of conserving the habitat mosaic - E. Andrieu; J. D. Thompson; M. Debussche (Biodiversity and Conservation, 2007)

Hydrologic and edaphic characteristics of three mountain wetlands in southeastern Kentucky, USA - Yvonne Thompson; Brian C. Sandefur; Jarrod O. Miller; A. D. Karathanasis (Wetlands, 2007)

Dihydroxyoctadecamonoenoate esters inhibit the neutrophil respiratory burst - David Alan Thompson; Bruce D Hammock (Journal of Biosciences, 2007)

Does cigarette smoking increase plasma urotensin II concentrations? - S. J. Gold; J. P. Thompson; J. P. Williams; E. E. F. Helm; J. Sadler; W. Song; L. L. Ng; D. G. Lambert (European Journal of Clinical Pharmacology, 2007)

Monitoring of Biodiversity Indicators in Boreal Forests: a Need for Improved Focus - Ian D. Thompson (Environmental Monitoring and Assessment, 2006)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Dakota Jewel: An attractive, new, bright red-skinned, fresh market potato cultivar with improved storage characteristics - A. L. Thompson; B. L. Farnsworth; G. A. Secor; N. C. Gudmestad; D. A. Preston; H. Hatterman-Valenti (American Journal of Potato Research, 2006)

Plasma Hsp72 is higher in runners with more serious symptoms of exertional heat illness - P. A. Ruell; M. W. Thompson; K. M. Hoffman; J. R. Brotherhood; D. A. B. Richards (European Journal of Applied Physiology, 2006)

Isolation and identification of Shewanella alga and its pathogenic effects on post‐larvae of abalone Haliotis diversicolor supertexta - J Cai; H Chen; K D Thompson; C Li (Journal of Fish Diseases, 2006)

Net Carbon Exchange Across the Arctic Tundra-Boreal Forest Transition in Alaska 1981–2000 - C. C. Thompson; A. D. McGuire; J. S. Clein; F. S. Chapin; J. Beringer (Mitigation and Adaptation Strategies for Global Change, 2006)

Dakota rose: A bright red tablestock potato cultivar that retains its skin color in storage - A. L. Thompson; G. A. Secor; J. H. Lorenzen; B. L. Farnsworth; R. G. Novy; N. C. Gudmestad; E. T. Holm; D. A. Preston (American Journal of Potato Research, 2006)

Colonization of rainbow trout, Oncorhynchus mykiss (Walbaum), eggs by Flavobacterium psychrophilum , the causative agent of rainbow trout fry syndrome - I N Vatsos; K D Thompson; A Adams (Journal of Fish Diseases, 2006)

Quantifying Damage, Saturation and Anisotropy in Cracked Rocks by Inverting Elastic Wave Velocities - Alexandre Schubnel; Philip M. Benson; Ben D. Thompson; Jim F. Hazzard; R. Paul Young (Pure and Applied Geophysics, 2006)

Fracture in Westerly Granite under AE Feedback and Constant Strain Rate Loading: Nucleation, Quasi-static Propagation, and the Transition to Unstable Fracture Propagation - Ben D. Thompson; R. Paul Young; David A. Lockner (Pure and Applied Geophysics, 2006)

Understanding Managers’ Views of Global Environmental Risk - Stephen D. Hill; Dixon Thompson (Environmental Management, 2006)

Use of stem diameter variations to detect plant water stress in tomato - M. Gallardo; R. B. Thompson; L. C. Valdez; M. D. Fernández (Irrigation Science, 2006)

RAAS polymorphisms alter the acute blood pressure response to aerobic exercise among men with hypertension - Bruce E. Blanchard; Gregory J. Tsongalis; Margaux A. Guidry; Lisa A. LaBelle; Michelle Poulin; Amy L. Taylor; Carl M. Maresh; Joseph Devaney; Paul D. Thompson; Linda S. Pescatello (European Journal of Applied Physiology, 2006)

Infectious pancreatic necrosis virus in Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland: virus identification, histopathology, immunohistochemistry and genetic comparison with Scottish mainland isolates - D A Smail; N Bain; D W Bruno; J A King; F Thompson; D J Pendrey; S Morrice; C O Cunningham (Journal of Fish Diseases, 2006)
During mid‐June 1999 peak mortalities of 11% of the total stock per week were seen at a sea cage site of Atlantic salmon, Salmo salar L., post‐smolts in the Shetland Isles, Scotland. Virus was isolated on chinook salmon embryo (CHSE) cells in a standard diagnostic test and infectious pancreatic necrosis virus (IPNV) identified by enzyme‐linked immunosorbent assay. IPNV was confirmed as serogroup A by a cell immunofluorescent antibody test using the cross‐reactive monoclonal antibody AS‐1. Four weeks after the main outbreak, virus titres in surviving moribund fish were assayed at >10 10 TCID 50 g −1 kidney. Histopathology of moribund fish was characterized by pancreatic acinar cell necrosis and a marked catarrhal enteritis of the intestinal mucosa. In the liver, necrosis, leucocytic infiltration and a generalized cell vacuolation were noted. IPNV‐specific immunostaining was demonstrated in pancreas, liver, heart, gill and kidney tissue. The nucleotide sequence of the coding region of segment A was determined from the Shetland isolate. A 1180 bp fragment of the VP2 gene of this isolate was compared with a 1979 reference isolate from mainland Scottish Atlantic salmon, La/79 and another more recent mainland isolate, 432/00. Both A2 isolates were derived from carrier fish without signs of IPN and serotyped by a plaque neutralization test. The Shetland isolate shows a different nucleotide and amino acid sequence compared with the two isolates from carrier fish. These latter isolates showed identical amino acid sequences in the fragment examined, despite the 21 years separating the isolations. Sequence comparisons with other A2 (Sp) isolates on the database confirm all three Scottish isolates are A2 (Sp).

Regulation and Manipulation of the Biosynthesis of Abscisic Acid, Including the Supply of Xanthophyll Precursors - Ian B. Taylor; Tineke Sonneveld; Timothy D. H. Bugg; Andrew J. Thompson (Journal of Plant Growth Regulation, 2005)

Case Study Part 2: Probabilistic Modelling of Long-term Effects of Pesticides on Individual Breeding Success in Birds and Mammals - W. ROELOFS; D.R. CROCKER; R.F. SHORE; D.R.J. MOORE; G.C. SMITH; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; et al. (Ecotoxicology, 2005)

Case Study Part 1: How to Calculate Appropriate Deterministic Long-Term Toxicity to Exposure Ratios (TERs) for Birds and Mammals - R.F. SHORE; D.R. CROCKER; H.R. AKCAKAYA; R.S. BENNETT; P.F. CHAPMAN; M. CLOOK; M. CRANE; I.C. DEWHURST; P.J. EDWARDS; A. FAIRBROTHER; S. FERSON; D. FISCHER; et al. (Ecotoxicology, 2005)

Dakota Pearl: An attractive, bright white-skinned, cold-chipping cultivar with tablestock potential - A. L. Thompson; R. G. Novy; B. L. Farnsworth; G. A. Secor; N. C. Gudmestad; J. R. Sowokinos; E. T. Holm; J. H. Lorenzen; D. Preston (American Journal of Potato Research, 2005)

Identifying brain regions for integrative sensorimotor processing with ankle movements - O. Ciccarelli; A. T. Toosy; J. F. Marsden; C. M. Wheeler-Kingshott; C. Sahyoun; P. M. Matthews; D. H. Miller; A. J. Thompson (Experimental Brain Research, 2005)

Upregulated MT1-MMP/TIMP-2 axis in the TSU-Pr1-B1/B2 model of metastatic progression in transitional cell carcinoma of the bladder - Christine L. Chaffer; Bonnie Dopheide; Daniel R. McCulloch; Allan B. Lee; Jane M. Moseley; Erik W. Thompson; Elizabeth D. Williams (Clinical & Experimental Metastasis, 2005)

Spatial structure of genetic variation and primary succession in the pioneer tree species Antirhea borbonica on La Réunion - I. LITRICO; J. RONFORT; R. VERLAQUE; J. D. THOMPSON (Molecular Ecology, 2005)
In habitats where colonization and extinction are recurrent, the distribution of gene frequencies among patches of suitable habitat may reflect the age structure of different populations. In this study, we quantify population genetic structure for a pioneer tree species, Antirhea borbonica , in a chrono‐sequence of primary succession on the lava flows of the Piton de La Fournaise volcano (La Réunion). Using microsatellite loci and amplified fragment length polymorphism (AFLP) markers, we quantified genetic variation within and among populations for early‐ and late‐succession populations in a landscape where extinction and recolonization are recurrent (the ‘Grand Brûlé’) and for late‐succession populations in a more stable landscape. This study produced three main results. First, we detected no evidence that founder events increase genetic differentiation among colonizing populations; F ST values among early‐ and among late‐succession populations were similar. Second, we found no evidence for isolation by distance; genetic distance was not correlated with spatial distance within and among populations. Third, F IS values are consistently high in all populations, despite the fact that A. borbonica populations are functionally close to dioecy and thus expected to have an outcrossing mating system. Multiple colonization events from different sources may limit differentiation among young populations and spatial isolation may enhance differentiation among late‐succession populations. Ecological processes acting during colonization may create the conditions for spatial aggregation within pioneer populations, and thus contribute to the high F IS values.

Differential resistance to freezing and spatial distribution in a chemically polymorphic plant Thymus vulgaris - Justin Amiot; Yann Salmon; Christian Collin; John D. Thompson (Ecology Letters, 2005)
Secondary compounds play multiple ecological roles. In this study, we present novel experimental evidence of differential tolerance to freezing temperatures among chemotypes of a chemically polymorphic plant, Thymus vulgaris . Non‐phenolic chemotypes showed a significantly better survival and re‐growth after early‐winter freezing (−10° in early December) than phenolic chemotypes. Comparison of temperature data (1971–2002) at a phenolic and non‐phenolic site showed that whereas early‐winter freezing occurred in 6 years in the non‐phenolic site they never occurred at the phenolic site. Observations of trichome morphology (where the essential oil is stocked) with and without intense freezing indicate that non‐phenolic chemotypes may escape any negative effects of freezing by releasing their essential oil into the atmosphere during severe freezing. The correlation between tolerance of freezing and local temperature regimes strongly suggests that differential freezing resistance is a key ingredient of the distribution of thyme chemotypes in space.

Land Disposal of Centrate from Biosolids Production - D. J. Baumgartner; E. P. Glenn; T. L. Thompson; B. A. Skeen (Water, Air, & Soil Pollution, 2005)

Oligogenic combinations associated with breast cancer risk in women under 53years of age - Christopher E. Aston; David A. Ralph; Dominique P. Lalo; Sharmila Manjeshwar; Bobby A. Gramling; Daniele C. DeFreese; Amy D. West; Dannielle E. Branam; Linda F. Thompson; Melissa A. Craft; Debra S. Mitchell; Craig D. Shimasaki; et al. (Human Genetics, 2005)

Evidence for an extreme climatic event on Achill Island, Co. Mayo, Ireland around 5200–5100 cal. yr BP - C. Caseldine; G. Thompson; C. Langdon; D. Hendon (Journal of Quaternary Science, 2005)
A range of detailed palaeoenvironmental analyses carried out on a series of three peat profiles from Achill Island, Co. Mayo, western Ireland, reveal evidence for an extreme climatic event, probably a storm or series of storms, around 5200–5100 cal. yr BP that caused the deposition of an extensive layer of silt across blanket peat. This event followed a period of relatively dry climate during which Neolithic communities expanded in the region. There was a subsequent period of continuing dry conditions allowing extensive colonisation of the peat by Pinus before a shift to wetter conditions characteristic of the later Holocene. The extreme climatic event is possibly linked to human abandonment of the area comparable to that observed from the work on the internationally significant Céide Fields in the same region. Copyright © 2005 John Wiley & Sons, Ltd.

Fine root dynamics and trace gas fluxes in two lowland tropical forest soils - Whendee L. Silver; Andrew W. Thompson; Megan E. McGroddy; Ruth K. Varner; Jadson D. Dias; Hudson Silva; Patrick M. Crill; Michael Keller (Global Change Biology, 2005)
Fine root dynamics have the potential to contribute significantly to ecosystem‐scale biogeochemical cycling, including the production and emission of greenhouse gases. This is particularly true in tropical forests which are often characterized as having large fine root biomass and rapid rates of root production and decomposition. We examined patterns in fine root dynamics on two soil types in a lowland moist Amazonian forest, and determined the effect of root decay on rates of C and N trace gas fluxes. Root production averaged 229 (±35) and 153 (±27) g m −2 yr −1 for years 1 and 2 of the study, respectively, and did not vary significantly with soil texture. Root decay was sensitive to soil texture with faster rates in the clay soil ( k =−0.96 year −1 ) than in the sandy loam soil ( k =−0.61 year −1 ), leading to greater standing stocks of dead roots in the sandy loam. Rates of nitrous oxide (N 2 O) emissions were significantly greater in the clay soil (13±1 ng N cm −2 h −1 ) than in the sandy loam (1.4±0.2 ng N cm −2 h −1 ). Root mortality and decay following trenching doubled rates of N 2 O emissions in the clay and tripled them in sandy loam over a 1‐year period. Trenching also increased nitric oxide fluxes, which were greater in the sandy loam than in the clay. We used trenching (clay only) and a mass balance approach to estimate the root contribution to soil respiration. In clay soil root respiration was 264–380 g C m −2 yr −1 , accounting for 24% to 35% of the total soil CO 2 efflux. Estimates were similar using both approaches. In sandy loam, root respiration rates were slightly higher and more variable (521±206 g C m 2 yr −1 ) and contributed 35% of the total soil respiration. Our results show that soil heterotrophs strongly dominate soil respiration in this forest, regardless of soil texture. Our results also suggest that fine root mortality and decomposition associated with disturbance and land‐use change can contribute significantly to increased rates of nitrogen trace gas emissions.

Limitations on reproductive success in endemic Aquilegia viscosa (Ranunculaceae) relative to its widespread congener Aquilegia vulgaris: the interplay of herbivory and pollination - Sbastien Lavergne; Max Debussche; John D. Thompson (Oecologia, 2005)

MULTISITE MARK-RECAPTURE FOR CETACEANS: POPULATION ESTIMATES WITH BAYESIAN MODEL AVERAGING - J. W. Durban; D. A. Elston; D. K. Ellifrit; E. Dickson; P. S. Hammond; P. M. Thompson (Marine Mammal Science, 2005)

Pharmacokinetics and Biodistribution of Novel Aptamer Compositions - Judith M. Healy; Scott D. Lewis; Markus Kurz; Ryan M. Boomer; Kristin M. Thompson; Charles Wilson; Thomas G. McCauley (Pharmaceutical Research, 2004)

Foreign Particles Testing in Orally Inhaled and Nasal Drug Products - James Blanchard; James Coleman; Claire D?Abreu Hayling; Raouf Ghaderi; Barbara Haeberlin; John Hart; Steen Jensen; Richard Malcolmson; Stanley Mittelman; Lee M. Nagao; Sonja Sekulic; Caesar Snodgrass-Pilla; et al. (Pharmaceutical Research, 2004)

LCC15-MB Cells are MDA-MB-435: A Review of Misidentified Breast and prostate cell lines - Erik W. Thompson; Mark Waltham; Susan J. Ramus; Anne-Marie Hutchins; Jane E. Armes; Ian G. Campbell; Elizabeth D. Williams; Phillip R. Thompson; James M. Rae; Michael D. Johnson; Robert Clarke (Clinical & Experimental Metastasis, 2004)

Common origins of MDA-MB-435 cells from various sources with those shown to have melonoma properties - James M. Rae; Susan J. Ramus; Mark Waltham; Jane E. Armes; Ian G. Campbell; Robert Clarke; Robert J. Barndt; Michael D. Johnson; Erik W. Thompson (Clinical & Experimental Metastasis, 2004)

The nature of spatial transitions in the Arctic - H. E. Epstein; J. Beringer; W. A. Gould; A. H. Lloyd; C. D. Thompson; F. S. Chapin; G. J. Michaelson; C. L. Ping; T. S. Rupp; D. A. Walker (Journal of Biogeography, 2004)
Aim Describe the spatial and temporal properties of transitions in the Arctic and develop a conceptual understanding of the nature of these spatial transitions in the face of directional environmental change. Location Arctic tundra ecosystems of the North Slope of Alaska and the tundra‐forest region of the Seward Peninsula, Alaska Methods We synthesize information from numerous studies on tundra and treeline ecosystems in an effort to document the spatial changes that occur across four arctic transitions. These transitions are: (i) the transition between High‐Arctic and Low‐Arctic systems, (ii) the transition between moist non‐acidic tundra (MNT) and moist acidic tundra (MAT, also referred to as tussock tundra), (iii) the transition between tussock tundra and shrub tundra, (iv) the transition between tundra and forested systems. By documenting the nature of these spatial transitions, in terms of their environmental controls and vegetation patterns, we develop a conceptual model of temporal dynamics of arctic ecotones in response to environmental change. Results Our observations suggest that each transition is sensitive to a unique combination of controlling factors. The transition between High and Low Arctic is sensitive primarily to climate, whereas the MNT/MAT transition is also controlled by soil parent material, permafrost and hydrology. The tussock/shrub tundra transition appears to be responsive to several factors, including climate, topography and hydrology. Finally, the tundra/forest boundary responds primarily to climate and to climatically associated changes in permafrost. There were also important differences in the demography and distribution of the dominant plant species across the four vegetation transitions. The shrubs that characterize the tussock/shrub transition can achieve dominance potentially within a decade, whereas spruce trees often require several decades to centuries to achieve dominance within tundra, and Sphagnum moss colonization of non‐acidic sites at the MNT/MAT boundary may require centuries to millennia of soil development. Main conclusions We suggest that vegetation will respond most rapidly to climatic change when (i) the vegetation transition correlates more strongly with climate than with other environmental variables, (ii) dominant species exhibit gradual changes in abundance across spatial transitions, and/or (iii) the dominant species have demographic properties that allow rapid increases in abundance following climatic shifts. All three of these properties characterize the transition between tussock tundra and low shrub tundra. It is therefore not surprising that of the four transitions studied this is the one that appears to be responding most rapidly to climatic warming.

Darwin's cross‐promotion hypothesis and the evolution of stylar polymorphism - Adeline C. Cesaro; John D. Thompson (Ecology Letters, 2004)
There is growing appreciation that the ecological factors which impact on rates of pollen transfer can contribute significantly to reproductive trait evolution in plants. In heterostylous species, several studies support Darwin's claim that the reciprocal positions of stigmas and anthers enhance inter‐morph mating in comparison to intra‐morph mating and thus the maintenance of the polymorphism. In this study, we evaluate the relative importance of intra‐morph and inter‐morph pollen transfers in Narcissus assoanus , a species with dimorphic variation in style length but non‐reciprocity of anther positions. This stigma‐height dimorphism represents a transitional stage in theoretical models of the evolution of distyly. Seed set variation on recipient plants with donor plants of a single morph in experimental arrays in a natural population illustrate that inter‐morph cross‐pollination is more efficient that intra‐morph cross‐pollination as a result of high rates of pollen transfer from long‐styled to short‐styled plants. The observed rates of pollen transfer satisfy the theoretical conditions for the establishment of a stigma‐height dimorphism in an ancestral monomorphic long‐styled population in pollen‐limited situations. These results provide experimental evidence for the Darwinian hypothesis that enhanced inter‐morph cross‐pollination facilitates not only the maintenance of heterostyly but also the establishment of transitional forms implicated in the evolution of this polymorphism.

Ecosystem Management across Ownerships: the Potential for Collision with Antitrust Laws - JONATHAN R. THOMPSON; MARK D. ANDERSON; K. NORMAN JOHNSON (Conservation Biology, 2004)
Cross‐boundary ecosystem management is increasingly being advocated to address large‐scale ecological issues on forested landscapes. Such management requires information about the age, composition, and distribution of trees and other vegetation in addition to the ability to coordinate management over large areas. In the United States, the forest industry owns and manages a large quantity of biologically productive forest land, and these forests are crucial to the success of regional ecosystem planning. Antitrust laws, such as the Sherman Antitrust Act of 1890, limit the industry's ability to participate in regional ecosystem planning because they restrict the ability of competing firms to coordinate activities and share information. Because antitrust courts do not consider the intentions of violators, achieving conservation or other public policy goals, even when working with government agencies, is not a sufficient defense. Therefore, the real and perceived threat of antitrust litigation is a disincentive to the forest industry's participation in large‐scale ecosystem management. Potential solutions to this problem include state immunity statutes and third‐party data aggregation.

Molecular and ecological evidence for small‐scale isolation by distance in an endangered damselfly, Coenagrion mercuriale - P. C. WATTS; J. R. ROUQUETTE; I. J. SACCHERI; S. J. KEMP; D. J. THOMPSON (Molecular Ecology, 2004)
Coenagrion mercuriale (Charpentier) (Odonata: Zygoptera) is one of Europe's most threatened damselflies and is listed in the European Habitats directive. We combined an intensive mark‐release‐recapture (MRR) study with a microsatellite‐based genetic analysis for C. mercuriale from the Itchen Valley, UK, as part of an effort to understand the dispersal characteristics of this protected species. MRR data indicate that adult damselflies are highly sedentary, with only a low frequency of interpatch movement that is predominantly to neighbouring sites. This restricted dispersal leads to significant genetic differentiation throughout most of the Itchen Valley, except between areas of continuous habitat, and isolation by distance (IBD), even though the core populations are separated by less than 10 km. An urban area separating some sites had a strong effect on the spatial genetic structure. Average pairwise relatedness between individual damselflies is positive at short distances, reflecting fine‐scale genetic clustering and IBD both within‐ and between‐habitat patches. Damselflies from a fragmented habitat have higher average kinship than those from a large continuous population, probably because of poorer dispersal and localized breeding in the former. Although indirect estimates of gene flow must be interpreted with caution, it is encouraging that our results indicate that the spatial pattern of genetic variation matches closely with that expected from direct observations of movement. These data are further discussed with respect to possible barriers to dispersal within the study site and the ecology and conservation of C. mercuriale . To our knowledge, this is the first report of fine‐scale genetic structuring in any zygopteran species.

Effects of model resolution and subgrid-scale physics on the simulation of precipitation in the continental United States - J. P. Iorio; P. B. Duffy; B. Govindasamy; S. L. Thompson; M. Khairoutdinov; D. Randall (Climate Dynamics, 2004)

Present And Past Ice-Sheet Mass Balance Simulations For Greenland And The Tibetan Plateau - T. G. D. Casal; J. E. Kutzbach; L. G. Thompson (Climate Dynamics, 2004)

Soil Sampling Techniques for Alabama, USA Grain Fields - A. N. Thompson; J. N. Shaw; P. L. Mask; J. T. Touchton; D. Rickman (Precision Agriculture, 2004)

Landscape Influences on Potential Soil Respiration Rates in a Forested Watershed of Southeastern Kentucky - Amanda C. Abnee; James A. Thompson; Randall K. Kolka; Elisa M. D’Angelo; Mark S. Coyne (Environmental Management, 2004)

Physical disturbance of an upland grassland influences the impact of elevated UV‐B radiation on metabolic profiles of below‐ground micro‐organisms - L. M. Avery; P. C. Thorpe; K. Thompson; N. D. Paul; J. P. Grime; H. M. West (Global Change Biology, 2004)
This investigation determined the response of soil microbial communities to enhanced UV‐B radiation and disturbance in upland grassland. A factorial field experiment encompassing two levels of UV‐B supplementation (simulating ambient and a 30% increase in stratospheric ozone) and two levels of disturbance (disturbed and undisturbed) was established at Buxton Climate Change Impacts Laboratory, Derbyshire, UK, and maintained for 7 years prior to sampling. Enhanced UV‐B increased microbial utilization of carbohydrates, carboxylic acids, polymers and aromatic compounds present in Biolog® GN plates when inoculated with soils taken from disturbed plots, but did not affect carbon utilization of soil microbial communities associated with undisturbed plots (UV‐B×Disturbance interaction, P UV‐B treatment did not affect numbers of bacteria or fungi. Direct microscopic counts showed fewer bacteria in soil originating from disturbed plots than from undisturbed plots (Disturbance, P P UV‐B treatment did not affect total plant biomass within undisturbed plots or the biomass of individual groupings of grasses, forbs and mosses. Per cent root length colonized by arbuscular mycorrhizal fungi (AMF) was not affected by enhanced UV‐B radiation in the undisturbed plots. Neither AMF nor plant biomass was measured in disturbed plots. The key findings of this study show that UV‐B‐mediated alterations in carbon utilization occurred in soil microbial communities subjected to disturbance, but such changes were not observed in communities sampled from undisturbed grassland. Differences in the catabolic potential of microbial communities from disturbed grassland subjected to enhanced UV‐B are probably related to plant‐mediated changes in resource availability or quality.

Prolonged vitamin C supplementation and recovery from eccentric exercise - D. Thompson; J. Hill; T. Hurst; J. R. Powell; C. Williams; D. M. Bailey (European Journal of Applied Physiology, 2004)

Urinary Excretion: Does It Accurately Reflect Relative Differences in Bioavailability/Systemic Exposure When Renal Clearance Is Nonlinear? - Gary A. Thompson; Roger D. Toothaker (Pharmaceutical Research, 2004)

Population biology of hyperbenthic crustaceans in a cold water environment (Conception Bay, Newfoundland). II. Acanthostepheia malmgreni (Amphipoda) - N. B. Richoux; R. J. Thompson; D. Deibel (Marine Biology, 2004)

Population biology of hyperbenthic crustaceans in a cold water environment (Conception Bay, Newfoundland). I. Mysis mixta (Mysidacea) - N. B. Richoux; D. Deibel; R. J. Thompson (Marine Biology, 2004)

Identification and characterization of a novel mouse prion gene allele - Sarah E. Lloyd; Simon R. Thompson; Jonathan A. Beck; Jacqueline M. Linehan; Jonathan D. F. Wadsworth; Sebastian Brandner; John Collinge; Elizabeth M. C. Fisher (Mammalian Genome, 2004)

The effect of nicotine on basophil histamine release - M. E. M. Thompson-Cree; M. D. Shields; M. R. Stevenson; M. Ennis (Inflammation Research, 2004)

Functional mechanisms underlying cetacean distribution patterns: hotspots for bottlenose dolphins are linked to foraging - G. D. Hastie; B. Wilson; L. J. Wilson; K. M. Parsons; P. M. Thompson (Marine Biology, 2004)

Real-time NASBA for Detection of Strawberry Vein Banding Virus - D. Vašková; J. Špak; M.M. Klerks; C.D. Schoen; J.R. Thompson; W. Jelkmann (European Journal of Plant Pathology, 2004)

A Comparison of Two Factorial Designs, a Complete 3×3 Factorial and a Central Composite Rotatable Design, for Use in Binomial Response Experiments in Aquatic Toxicology - Andrea N. Edginton; Patrick M. Sheridan; Herman J. Boermans; Dean G. Thompson; John D. Holt; Gerald R. Stephenson (Archives of Environmental Contamination and Toxicology, 2004)

Detection and Tentative Grouping of Strawberry crinkle virus Isolates - M.M. Klerks; J.L. Lindner; D. Vaškova; J. Špak; J.R. Thompson; W. Jelkmann; C.D. Schoen (European Journal of Plant Pathology, 2004)

Transfection of MDA-MB-231 human breast carcinoma cells with bone sialoprotein (BSP) stimulates migration and invasion in vitro and growth of primary and secondary tumors in nude mice - Julie A. Sharp; Mark Waltham; Elizabeth D. Williams; Michael A. Henderson; Erik W. Thompson (Clinical & Experimental Metastasis, 2004)

Forest Certification of State and University Lands in North Carolina: A Comparison - F. Cubbage; S. Moore; J. Cox; L. Jervis; J. Edeburn; D. Richter; W. Boyette; M. Thompson; M. Chesnutt (Journal of Forestry, 2003)
North Carolina State University, Duke University, and the North Carolina Division of Forest Resources (DFR) recently received both Forest Stewardship Council (FSC) and Sustainable Forestry Initiative (SFI) certification for their forests. Meeting SFI standards required better environmental management systems, improved use of best management practices, and better recordkeeping but few subsequent forest management changes. FSC required about the same environmental system changes but more forest management changes to favor future natural stand management and biodiversity protection. Costs included changes in forest management and recordkeeping to achieve forest certification, inspection expenses, prescribed changes in forest management, forgone timber revenues, and more stakeholder consultation. Benefits can include an improved professional reputation, better worker safety and training, better records and processes, more active public involvement, enhanced knowledge for outreach, better environmental management systems, more holistic management, and perhaps higher timber prices or greater market access.

Flower size dimorphism in diclinous plants native to La Runion Island - L. Humeau; T. Pailler; J. D. Thompson (Plant Systematics and Evolution, 2003)

Effect of target-distractor similarity on FEF visual selection in the absence of the target - Jeffrey D. Schall; Takashi R. Sato; Katsumi Watanabe; Kirk G. Thompson (Experimental Brain Research, 2003)

Genetic variation among life-history stages of mussels in a Mytilus edulis?M . trossulus hybrid zone - J. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 2003)

Is the long-latency stretch reflex in human masseter transcortical? - Sophie L. Pearce; Timothy S. Miles; Philip D. Thompson; Michael A. Nordstrom (Experimental Brain Research, 2003)

Mid-Holocene climates of the Americas: a dynamical response to changed seasonality - S. P. Harrison; J. E. Kutzbach; Z. Liu; P. J. Bartlein; B. Otto-Bliesner; D. Muhs; I. C. Prentice; R. S. Thompson (Climate Dynamics, 2003)

Qualitative and Quantitative Variation in Monoterpene Co-Occurrence and Composition in the Essential Oil of Thymus vulgaris Chemotypes - John D. Thompson; Jean-Claude Chalchat; André Michet; Yan B. Linhart; Bodil Ehlers (Journal of Chemical Ecology, 2003)

Characterization of Crystalline Drug Nanoparticles Using Atomic Force Microscopy and Complementary Techniques - Huaiqiu Galen Shi; Leon Farber; James N. Michaels; Allison Dickey; Karen C. Thompson; Suhas D. Shelukar; Patricia N. Hurter; Scott D. Reynolds; Michael J. Kaufman (Pharmaceutical Research, 2003)

Dietary nutrient levels regulate protein and carbohydrate intake, gluconeogenic/glycolytic flux and blood trehalose level in the insect Manduca sexta L. - S. N. Thompson; D. B. Borchardt; L.-W. Wang (Journal of Comparative Physiology B, 2003)

Characterisation of the expression of a novel constitutive maize promoter in transgenic wheat and maize - S. Rasco-Gaunt; D. Liu; C. Li; A. Doherty; K. Hagemann; A. Riley; T. Thompson; C. Brunkan; M. Mitchell; K. Lowe; E. Krebbers; P. Lazzeri; et al. (Plant Cell Reports, 2003)

Preparation and characterization of vanadyl complexes with bidentate maltol-type ligands; in vivo comparisons of anti-diabetic therapeutic potential - Katherine H. Thompson; Barry D. Liboiron; Yan Sun; Karycia D. Bellman; Ika A. Setyawati; Brian O. Patrick; Veranja Karunaratne; Gulnar Rawji; Jeffrey Wheeler; Kymberley Sutton; Sanjay Bhanot; Carrie Cassidy; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

The Stable Carbon Isotope Ratio of Biogenic Emissions of Isoprene and the Potential Use of Stable Isotope Ratio Measurements to Study Photochemical Processing of Isoprene in the Atmosphere - J. Rudolph; R. S. Anderson; K. V. Czapiewski; E. Czuba; D. Ernst; T. Gillespie; L. Huang; C. Rigby; A. E. Thompson (Journal of Atmospheric Chemistry, 2003)

BOTTLENOSE DOLPHINS INCREASE BREATHING SYNCHRONY IN RESPONSE TO BOAT TRAFFIC - Gordon D. Hastie; Ben Wilson; Lindsay H. Tufft; Paul M. Thompson (Marine Mammal Science, 2003)
A bstract To minimize potential impacts of boat traffic on the behavior of cetaceans it is important to assess short‐term behavioral responses to boats and interpret the long‐term consequences of these. Anecdotal descriptions of synchronous behavior in cetaceans are particularly frequent with reports of individuals within schools surfacing to breathe in a coordinated fashion being common. However, quantitative descriptions are rare. This study begins by quantifying synchronous breathing patterns of bottlenose dolphins off northern Scotland. We investigate possible functions of synchrony such as feeding patterns and presence of calves. We then test whether the presence of boat traffic in an area used intensively by dolphins affects their breathing synchrony. Although the majority of dolphin schools observed showed random breathing patterns, 30.5 % of schools showed synchronous breathing. There was no variation in this behavior with respect to identifiable feeding activities. However, synchrony was significantly negatively telated to the presence of calves in the school (χ 2 = 7.17, df = 1, P = 0.007) and significantly positively related to the presence of boat traffic in the study area ( χ = 13.85, df = 1, P = 0.0002). Such consistent short‐term behavioral responses by dolphins may potentially accumulate to produce longer‐term consequences both for individuals and the whole population.

Statistical hypothesis testing formulations for U.S. environmental regulatory standards for ozone - Mary Lou Thompson; Lawrence H. Cox; Paul D. Sampson; David C. Caccia (Environmental and Ecological Statistics, 2002)

Post-phloem protein trafficking in the maize caryopsis: ZmTRXh1, a thioredoxin specifically expressed in the pedicel parenchyma of Zea mays L., is found predominantly in the placentochalaza - Geraldina Santandrea; Yan Guo; Timothy O'Connell; Richard D. Thompson (Plant Molecular Biology, 2002)

Reproductive isolation and reproductive output in two sympatric mussel species (Mytilus edulis, M. trossulus) and their hybrids from Newfoundland - J. E. Toro; R. J. Thompson; D. J. Innes (Marine Biology, 2002)

Cancer prevention behaviors and socioeconomic status among Hispanics and non-Hispanic Whites in a rural population in the United States - Beti Thompson; Gloria D. Coronado; Cam C. Solomon; Dale F. McClerran; Marian L. Neuhouser; Ziding Feng (Cancer Causes & Control, 2002)

Fate and Persistence of Azadirachtin A Following Applications to Mesocosms in a Small Forest Lake - D. G. Thompson; D. P. Kreutzweiser; B. Staznik; D. Chartrand; S. Capell (Bulletin of Environmental Contamination and Toxicology, 2002)

Serum selenium and the risk of cervical cancer among women in the United States - Frances E. Thompson; Blossom H. Patterson; Stephanie J. Weinstein; Mary McAdams; Vickie L. Spate; Richard F. Hamman; Robert S. Levine; Katherine Mallin; Paul D. Stolley; Louise A. Brinton; J. Steven Morris; Regina G. Ziegler (Cancer Causes & Control, 2002)

Ankerite carbonatite from Swartbooisdrif, Namibia: the first evidence for magmatic ferrocarbonatite - R. Thompson; P. Smith; S. Gibson; D. Mattey; A. Dickin (Contributions to Mineralogy and Petrology, 2002)

Induction of persistent changes in the organisation of the human motor cortex - Darrin R. McKay; Michael C. Ridding; Philip D. Thompson; Timothy S. Miles (Experimental Brain Research, 2002)

Identification of Mycobacterium spp. isolated from snakehead, Channa striata (Fowler), and Siamese fighting fish, Betta splendens (Regan), using polymerase chain reaction–reverse cross blot hybridization (PCR–RCBH) - S Puttinaowarat; K D Thompson; A Kolk; A Adams (Journal of Fish Diseases, 2002)
A variety of methods have been used to identify Mycobacterium spp. isolated from snakehead and Siamese fighting fish, including biochemistry, mycolic acid profiles and antibody‐based methods. However, these methods are unable to differentiate between different species of Mycobacterium . Polymerase chain reaction (PCR) followed by reverse cross blot hybridization (RCBH) was adapted in this study to speciate aquatic mycobacteria. The method was highly specific for Mycobacterium spp. and identified the bacteria to species level with a detection limit of 100 fg DNA, equivalent to 20 mycobacteria. Twenty‐nine isolates previously collected and cultured from Siamese fighting fish (10 isolates) and snakehead (19 isolates) during outbreaks of mycobacteriosis were analysed using PCR–RCBH. Six of the Siamese fighting fish isolates and nine of the snakehead isolates were identified as Mycobacterium fortuitum , while the remainder were classified as M. marinum . Notably, two isolates recovered from snakehead and Siamese fighting fish, previously identified as M. poriferae and M. piscicida , respectively, were confirmed to be M. fortuitum .

Nest Predators and Fragmentation: a Review and Meta‐Analysis - Anna D. Chalfoun; Frank R. Thompson; Mary J. Ratnaswamy (Conservation Biology, 2002)
Population declines of many avian species are often attributed to increased rates of nest predation in fragmented landscapes, yet mechanisms underlying these effects have rarely been examined. We reviewed the literature to determine the extent to which hypotheses about nest predators and fragmentation have been invoked and compared this to the number of direct tests of predators with respect to habitat edge, patch size, or landscape type. We also conducted a meta‐analysis of tested predator effects to evaluate whether predator responses—numerical, functional, or species richness—to fragmentation depend on spatial scale (edge, patch, or landscape), landscape type, geographic region, or predator taxa. We found 120 papers containing hypotheses about nest predators and fragmentation, but only 31 with hypothesis tests. Most tests were of a single predator species or guild, whereas most cited hypotheses generalized across broader taxonomic groups. Results of predator tests were variable, but some general patterns were evident. Predator effects, including increased abundance, activity, or species richness in edges, small patches, or certain landscapes, were more prevalent (1) in tests conducted at the landscape scale than at the local scale, ( 2) in agricultural landscapes than in predominantly forested landscapes, (3) in certain biogeographic regions, and (4) for avian predators than for mammalian predators. Local‐scale (edge and patch) effects were most common when the land surrounding patches was agricultural and when tests were conducted within agricultural landscapes. The response of nest predators to fragmentation is complex, taxon‐specific, and context‐dependent. Conservation efforts for declining avian species may therefore need to be customized according to the nest‐predator species primarily responsible for local nest mortality and the nature of the landscape mosaic.

Interdisciplinary Irrigated Precision Farming Research - D. F. Heermann; J. Hoeting; S. E. Thompson; H. R. Duke; D. G. Westfall; G. W. Buchleiter; P. Westra; F. B. Peairs; K. Fleming (Precision Agriculture, 2002)

Development and mapping of SSR markers for maize - Natalya Sharopova; Michael D. McMullen; Linda Schultz; Steve Schroeder; Hector Sanchez-Villeda; Jack Gardiner; Dean Bergstrom; Katherine Houchins; Susan Melia-Hancock; Theresa Musket; Ngozi Duru; Mary Polacco; et al. (Plant Molecular Biology, 2002)

Geographic isolation and evolution of Mediterranean endemic Cyclamen : insights from chloroplast trn L (UAA) intron sequence variation - L. Gielly; M. Debussche; J. D. Thompson (Plant Systematics and Evolution, 2001)

Copper, Cadmium, and Zinc Concentrations in Juvenile Chinook Salmon and Selected Fish-Forage Organisms (Aquatic Insects) in the Upper Sacramento River, California - Michael K. Saiki; Barbara A. Martin; Larry D. Thompson; Daniel Welsh (Water, Air, & Soil Pollution, 2001)

Quantifying the 5-HT 1A agonist action of buspirone in man - Bridge M.; Marvin G.; Thompson C.; Sharma A.; Jones D.; Kendall M. (Psychopharmacology, 2001)

Testing a simple stochastic model for the dynamics of waterfowl aggregations - Emily D. Silverman; Mark Kot; Elizabeth Thompson (Oecologia, 2001)

Mercury in Bar-Tailed Godwit ( Limosa lapponica ) and Lesser Knot ( Calidris canutus ): Spatially Explicit Information from Non-Breeding Birds in New Zealand - D. R. Thompson (Bulletin of Environmental Contamination and Toxicology, 2001)

The allometry of flower size dimorphism in dioecious Dombeya species on La Réunion - Laurence Humeau; John D. Thompson (Ecology Letters, 2001)
In this paper we examine whether variation in male and female flower size follows an allometric relation for 10 dioecious species in the genus Dombeya endemic to La Réunion. Male flowers are significantly larger than female flowers and the degree of dimorphism varies significantly across species. There is a significant allometric relationship between male and female flower size: as mean flower size decreases the degree of flower size dimorphism increases. This is the first study to document an allometric relationship between male and female flower size in unisexual plants. We discuss this allometric relationship in relation to two characteristics frequently observed in dioecious flowers: flower size dimorphism is common in unisexual plants and dioecious species often have smaller flowers than hermaphrodites.

The production of a lymphokine (macrophage activating factor) by rainbow trout, Oncorhynchus mykiss (Walbaum), leucocytes stimulated with the extracellular products of Mycobacterium sp. - S‐C Chen; K D Thompson; A Adams; R H Richards (Journal of Fish Diseases, 2001)
The production of macrophage activation factor (MAF) by rainbow trout, Oncorhynchus mykiss (Walbaum) , head kidney leucocytes was examined after culturing in vitro with extracellular products (ECP) collected from Mycobacterium sp. Cultures of leucocytes were prepared from naive fish, or fish previously vaccinated with either the ECP or with formalin killed whole cell preparations (WC) of the bacterium. The cells were then incubated with the ECP in vitro and the ability of their supernatants to activate macrophages assessed. Macrophages from control fish were incubated with the supernatants, and their ability to reduce nitroblue tetrazolium (NBT) measured as an indicator of macrophage activation. Incubation of head kidney macrophages from naive fish directly with 1, 10 or 100 μg mL –1 of ECP for 48 h significantly enhanced macrophage activation compared with control macrophages. Vaccination of fish with either ECP or WC had no significant effect on the respiratory burst of control macrophages 4 weeks post‐vaccination. By the eighth week, however, absorbance levels of respiratory burst reflecting both the primary (cells from vaccinated fish cultured in vitro with PBS) and the secondary (cells cultured in vitro with ECP) MAF responses of fish vaccinated with ECP and WC, had peaked and these were significantly different from the non‐vaccinated controls. This activity had fallen to levels similar to control fish by week 12 for fish vaccinated with WC.

Breeding biology, resource partitioning and reproductive effort of a dioecious shrub, Clutia pulchella L. (Euphorbiaceae) - D. I. Thompson; T. J. Edwards (Plant Systematics and Evolution, 2001)

Task-dependent control of human masseter muscles from ipsilateral and contralateral motor cortex - Sophie L. Butler; Timothy S. Miles; Philip D. Thompson; Michael A. Nordstrom (Experimental Brain Research, 2001)

Risedronate Pharmacokinetics and Intra- and Inter-Subject Variability Upon Single-Dose Intravenous and Oral Administration - David Y. Mitchell; William H. Barr; Rachelle A. Eusebio; Karen A. Pallone Stevens; Frank P. Duke; Darrell A. Russell; John D. Nesbitt; James H. Powell; Gary A. Thompson (Pharmaceutical Research, 2001)

How do visitation patterns vary among pollinators in relation to floral display and floral design in a generalist pollination system? - J. D. Thompson (Oecologia, 2001)

High pressure fluids in the system MgO–SiO2–H2O under upper mantle conditions - R. Stalder; P. Ulmer; A. Thompson; D. Günther (Contributions to Mineralogy and Petrology, 2001)

The production and characterization of monoclonal antibodies against Photobacterium damselae ssp. piscicida and initial observations using immunohistochemistry - T S Jung; K D Thompson; D J Morris; A Adams; K Sneddon (Journal of Fish Diseases, 2001)
Five monoclonal antibodies (MAbs: F2B1, 1E4, 13B10, 4D4 and F3G12) were produced against lysed Photobacterium damselae ssp. piscicida ( Ph. d . ssp. piscicida ). The MAbs recognized three antigens of differing molecular weight on the Western blot of Ph. d . ssp. piscicida . They also cross‐reacted with five different species of Vibrio . An enzyme linked immunosorbent assay (ELISA) with MAbs, F3G12 and 4D4 demonstrated differences between Ph. d . ssp. piscicida and three Ph. d . ssp. damselae type strains, indicating differences in the surface antigenicity between these two groups of bacteria. Antigen retrieval in conjunction with immunohistochemistry (IHC) using MAb 13B10, revealed colonies of bacteria in the kidney, spleen and liver of sea bass, Dicentrarchus labrax , infected with pasteurellosis. A number of positive colonies were observed around the mucosal layers of the intestinal tissue, especially within the lamina propria. In addition, a number of bacterial colonies were associated with red blood cells and blood vessels of the organs examined.

A Piscirickettsia salmonis ‐like organism in grouper, Epinephelus melanostigma , in Taiwan - S‐C Chen; P‐C Wang; M‐C Tung; K D Thompson; A Adams (Journal of Fish Diseases, 2000)

Acclimation response of spring wheat in a free-air CO2 enrichment (FACE) atmosphere with variable soil nitrogen regimes. 1. Leaf position and phenology determine acclimation response - Neal R. Adam; Gerard W. Wall; Bruce A. Kimball; Paul J. Pinter; Robert L. LaMorte; Douglas J. Hunsaker; Floyd J. Adamsen; Tom Thompson; Allan D. Matthias; Steven W. Leavitt; Andrew N. Webber (Photosynthesis Research, 2000)

Variation of pollen limitation in the early flowering Mediterranean geophyte Narcissus assoanus (Amaryllidaceae) - A. M. Baker; S. C. H. Barrett; J. D. Thompson (Oecologia, 2000)

Phase relations, singularities and thermobarometry of metamorphic assemblages containing phengite, chlorite, biotite, K-feldspar, quartz and H2O - G. D. H. Simpson; A. B. Thompson; J. A. D. Connolly (Contributions to Mineralogy and Petrology, 2000)

Hormonal regulation of physiological cell turnover and apoptosis - Rheem D. Medh; E. Brad Thompson (Cell and Tissue Research, 2000)

Development of a sampling method for the isolation of head kidney macrophages from fish at the pond‐side - M Crumlish; T T Dung; T Somsiri; V Inglis; K D Thompson (Journal of Fish Diseases, 2000)

How incubation temperature influences the physiology and growth of embryonic lizards - D. T. Booth; M. B. Thompson; S. Herring (Journal of Comparative Physiology B, 2000)

Effects of the nicotinic antagonist mecamylamine on inspection time - J. C. Thompson; C. Stough; D. Ames; C. Ritchie; P. J. Nathan (Psychopharmacology, 2000)

A DESIGN FOR A TWO‐DIMENSIONAL BOAT‐BOUND HYDROPHONE ARRAY FOR STUDYING HARBOR SEALS, PHOCA VITULINA - Sofie M. van Parijs; Gordon D. Hastie; Paul M. Thompson (Marine Mammal Science, 2000)

The effect of elevated atmospheric carbon dioxide levels on soil bacterial communities - K. D. Bruce; T. H. Jones; T. M. Bezemer; L. J. Thompson; D. A. Ritchie (Global Change Biology, 2000)
Summary The effect of elevated carbon dioxide levels on total bacterial communities was studied in a series of controlled and replicated model terrestrial ecosystems over a period of 38 weeks. The bacterial community was profiled using Denaturing Gradient Gel Electrophoresis (DGGE) analysis of bacterial 16S rRNA gene fragments amplified by the Polymerase Chain Reaction from DNA extracted directly from soil. Bacterial community DGGE profiles provided three major findings: (i) there was a high degree of profile similarity after ≈ 12 weeks (one plant generation); (ii) whilst overall DGGE profile was maintained over the 38 weeks (three plant generations), the banding patterns became more diverse with time; (iii) DGGE data provided no evidence for a shift in bacterial community structure resulting from exposure of the ecosystem to an increased atmospheric CO 2 level.

Plant Uptake Response to Metals and Nitrate in Simulated Uranium Mill Tailings Contaminated Groundwater - D. J. Baumgartner; E. P. Glenn; R. O. Kuehl; T. L. Thompson; J. F. Artiola; S. E. Menke; R. A. Saar; G. S. Moss; M. A. Algharaibeh (Water, Air, & Soil Pollution, 2000)

Ocean, ice, and atmosphere: interactions at the Antarctic continental margin, Antarctic Research Series, Volume 75, S.S. Jacobs and R.F. Weiss (Editors), American Geophysical Union (Washington D.C.), 1998. No. of pages: xi+382. Price US $75.00. ISBN 0 87590 910 8 (hardback). - Russell D. Thompson (International Journal of Climatology, 2000)

Evidence for factors regulating transfer cell-specific expression in maize endosperm - Gregorio Hueros; Joaquin Royo; Monika Maitz; Francesco Salamini; Richard D. Thompson (Plant Molecular Biology, 1999)

Arsenic in Well Water Supplies in Saskatchewan - T. S. Thompson; M. D. Le; A. R. Kasick; T. J. Macaulay (Bulletin of Environmental Contamination and Toxicology, 1999)

Laboratory Kinetic Studies of the Reactions of Cl Atoms with Species of Biogenic Origin: δ3-Carene, Isoprene, Methacrolein and Methyl Vinyl Ketone - Carlos E. Canosa-Mas; Hilary R. Hutton-Squire; Martin D. King; David J. Stewart; Katherine C. Thompson; Richard P. Wayne (Journal of Atmospheric Chemistry, 1999)

What We Know -- and Don't Know -- about Water Quality at Stream Crossings - Steven E. Taylor; Robert B. Rummer; Kyung H. Yoo; Richard A. Welch; Jason D. Thompson (Journal of Forestry, 1999)
Forest road stream crossings, including fords, culverts, and bridges, are primary contributors of sediment to forest streams. Information on the water quality impacts from each type of crossing is limited, but the available literature indicates that significant amounts of sediment are produced during installation of fords and culverts; construction and use of temporary bridges have the least impact on water quality. This review of our current state of knowledge on the water quality impacts from crossings shows that we need date for a wide variety of steam sizes, soil types, terrain, and climatological conditions so that policymakers can develop scientifically sound best management practices.

A molecular approach to the ecology of a mussel ( Mytilus edulis - M. trossulus ) hybrid zone on the east coast of Newfoundland, Canada - A. S. Comesaña; J. E. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Multiple origins of polyploidy and the geographic structure of Heuchera grossulariifolia - K. A. SEGRAVES; J. N. THOMPSON; P. S. SOLTIS; D. E. SOLTIS (Molecular Ecology, 1999)
Multiple origins of polyploidy from an ancestral diploid plant species were investigated using restriction site polymorphism and sequence variation in the chloroplast DNA (cpDNA) of Heuchera grossulariifolia (Saxifragaceae). Phylogenetic analysis indicated that autopolyploidy has arisen at least twice in the evolutionary history of this species and potentially up to as many as seven times. These results suggest a greater range of independent polyploid origins as compared to a previous study of H. grossulariifolia using cpDNA restriction sites that indicated a minimum of three independent origins. Moreover, most polyploid populations did not contain cpDNA haplotypes from a single origin, but rather combined haplotypes from at least two polyploid origins. Past migration among polyploid populations of independent origin or localized polyploid formation may explain the distribution of polyploid haplotypes within and among populations. The analysis also revealed a discrepancy between relatedness and geographical location. In nearly all sympatric populations of diploids and polyploids, polyploids had the same cpDNA haplotypes as diploids from a geographically remote population. This geographical discordance has several possible explanations, including small sample sizes, extinction of parental diploid haplotypes, chloroplast introgression, and homoplasy in the cpDNA sequence data. We conclude that the recurrent formation of polyploids is an important evolutionary mechanism in the diversification of H. grossulariifolia .

Variation in the breeding system of two sympatricDombeya species on La Runion island - L. Humeau; T. Pailler; J. D. Thompson (Plant Systematics and Evolution, 1999)

Species diversity and ecological range in relation to ploidy level in the flora of the Pyrenees - Christophe Petit; John D. Thompson (Evolutionary Ecology, 1999)

Activation of nuclear factor kappa B in Crohn's disease - R. D. Ellis; J. R. Goodlad; G. A. Limb; J. J. Powell; R. P. H. Thompson; N. A. Punchard (Inflammation Research, 1998)

Evaluation of muscle oxidative potential by 31 P-MRS during incremental exercise in old and young humans - Philip D. Chilibeck; Cheryl R. McCreary; Greg D. Marsh; Donald H. Paterson; Earl G. Noble; Albert W. Taylor; R. Terry Thompson (European Journal of Applied Physiology, 1998)

Probing termite social systems through allozyme and mtDNA analysis: a case study of Nasutitermes nigriceps and Nasutitermes costalis (Isoptera, Termitidae) - G. J. Thompson; P. D. N. Hebert (Insectes Sociaux, 1998)

Characterising food‐webs in two New Zealand streams - N. G. Jaarsma; S. M. de Boer; C. R. Townsend; R. M. Thompson; E. D. Edwards (New Zealand Journal of Marine and Freshwater Research, 1998)
The food‐web communities of two stony tributaries of the Taieri River in New Zealand were documented. We placed heavy emphasis on algal and macroinvertebrate taxonomy, identifying most taxa to species or morpho‐species level. Food‐web attributes were derived from symmetrical matrices using an Excel macro. The values of the food‐web attributes are generally consistent with generalities that have previously been reported in food‐web studies, although some hypothesisied relationships between connectance and food‐web size did not hold. The patterns detected were robust to the inclusion or exclusion of species that were identified in gut contents but not in field samples. The attributes strongly reflected the trophic status of the streams. Dempsters Creek was classified as autotrophic (based on high primary production and a high ratio of production to respiration) and displayed a larger food‐web size and longer food‐chains than those seen in Healy Creek, which was classified as hetero‐trophic (lower primary production and production to respiration ratio). The importance of dynamic environmental attributes such as production and disturbance in structuring food‐webs is emphasised in this study.

Substrate use during and following moderate- and low-intensity exercise: Implications for weight control - D. L. Thompson; K. M. Townsend; R. Boughey; K. Patterson; D. R. Bassett Jr (European Journal of Applied Physiology, 1998)

MODIFICATION AND DEPLOYMENT OF A SONOBUOY FOR RECORDING UNDERWATER VOCALIZATIONS FROM MARINE MAMMALS - Sofie M. van Parijs; Paul M. Thompson; Gordon D. Hastie; Birgit A. Bartels (Marine Mammal Science, 1998)

Olfaction in Persons with Alzheimer's Disease - Matthew D. Thompson; Kathleen Knee; Charles J. Golden (Neuropsychology Review, 1998)

Impact of elevated atmospheric CO 2 concentration on soil microbial biomass and activity in a complex, weedy field model ecosystem - Christian Kampichler; Ellen Kandeler; Richard D. Bardgett; T. Hefin Jones; Lindsey J. Thompson (Global Change Biology, 1998)
Although soil organisms play an essential role in the cycling of elements in terrestrial ecosystems, little is known of the impact of increasing atmospheric CO 2 concentrations on soil microbial processes. We determined microbial biomass and activity in the soil of multitrophic model ecosystems housed in the Ecotron (NERC Centre for Population Biology, Ascot, UK) under two atmospheric CO 2 concentrations (ambient vs. ambient + 200 ppm). The model communities consist of four annual plant species which naturally co‐occur in weedy fields and disturbed ground throughout southern England, together with their herbivores, parasitoids and soil biota. At the end of two experimental runs lasting 9 and 4.5 months, respectively, root dry weight and quality showed contradictory responses to elevated CO 2 concentrations, probably as a consequence of the different time‐periods (and hence number of plant generations) in the two experiments. Despite significant root responses no differences in microbial biomass could be detected. Effects of CO 2 concentration on microbial activity were also negligible. Specific enzymes (protease and xylanase) showed a significant decrease in activity in one of the experimental runs. This could be related to the higher C:N ratio of root tissue. We compare the results with data from the literature and conclude that the response of complex communities cannot be predicted on the basis of oversimplified experimental set‐ups.

The effects of climate change on landscape diversity: an example in Ontario forests - Ian D. Thompson; Michael D. Flannigan; B. Michael Wotton; Roger Suffling (Environmental Monitoring and Assessment, 1998)

Floral trait variation in fourCyclamen (Primulaceae) species - L. Affre; J. D. Thompson (Plant Systematics and Evolution, 1998)

Distyly and heteromorphic incompatibility in oceanic island species ofErythroxylum (Erythroxylaceae) - T. Pailler; L. Humeau; J. D. Thompson (Plant Systematics and Evolution, 1998)

Rotifers in relation to littoral ecotone structure in Lake Rotomanuka, North Island, New Zealand - Ian C. Duggan; John D. Green; Keith Thompson; Russell J. Shiel (Hydrobiologia, 1998)

Risk factors for bronchiolitis: Presentation of an on-going prospective clinical study - M. E. M Thompson; J. K. Nelson; C. McMaster, M. C. Stewart, M. D. Shie (Inflammation Research, 1997)

A promoter directing high level expression in pistils of transgenic plants - Michael Ficker; Thomas Wemmer; Richard D. Thompson* (Plant Molecular Biology, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Proton efflux in human skeletal muscle during recovery from exercise - G. J. Kemp; C. H. Thompson; D. J. Taylor; G. K. Radda (European Journal of Applied Physiology, 1997)

Distribution and abundance of choanoflagellates (Acanthoecidae) in the coastal cold ocean of Newfoundland, Canada - C. H. McKenzie; D. Deibel; R. J. Thompson; B. A. MacDonald; R. W. Penney (Marine Biology, 1997)

Specific Contributions of Politics, Economics, and Toxicology in Setting Socially Consensual Limit Values - H. H. Dieter; A. Grohmann; D. Thompson (Environmental Management, 1997)

Identification of Pentachloronitrobenzene in Ambient Air Extracts - T. S. Thompson; R. G. Treble; D. T. Waite; A. J. Cessna (Bulletin of Environmental Contamination and Toxicology, 1997)

Juvenile Survival in a Population of Neotropical Migrant Birds. Supervivencia de Juveniles en una Poblacion de Aves Migratorias Neotropicales - Angela D. Anders; Donald C. Dearborn; John Faaborg; Frank R. Thompson Iii (Conservation Biology, 1997)

Purine modulation of dizocilpine effects on spontaneous alternation - C. M. Fraser; A. Fisher; M. J. Cooke; I. D. Thompson; T. W. Stone (Psychopharmacology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Human breast cancer cell metastasis to long bone and soft organs of nude mice: a quantitative assay - V. Sung; D. A. Cattell; J. M. Bueno; A. Murray; J. A. Zwiebel; A. D. Aaron; E.W. Thompson (Clinical & Experimental Metastasis, 1997)

Molecular scatology: the use of molecular genetic analysis to assign species, sex and individual identity to seal faeces - J. Z. Reed; D. J. Tollit; P. M. Thompson; W. Amos (Molecular Ecology, 1997)
Seals and commercial fisheries are potential competitors for fish and cephalopods. Research into the diet of British seal species has been based on conventional dietary analyses, but these methods often do not allow assignment of species identity to scat samples. We present a protocol for obtaining DNA from seal scat (faecal) samples which can be used in polymerase chain reactions to amplify both nuclear and mitochondrial DNA. This can provide a method of identifying the species, sex and individual identity of the seal, from a particular scat sample. Combined with conventional dietary analyses these techniques will allow us to assess sources of variation in seal diet composition. Scat samples have been collected from intertidal haul‐out sites around the inner Moray Firth, north‐east Scotland. We have assessed methods to extract and purify faecal DNA, a combination of DNA from the individual seal, prey items, and gut bacteria, for use in PCR. Controls using faecal and blood samples from the same individual have enabled microsatellite primer sets from four pinniped species to be tested. Approximately 200 scat samples have been examined for species identity and individual matches. This study will provide essential information for the assessment of interactions between seals and commercial or recreational fisheries.

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Organochlorine pesticide contamination in neotropical migrant passerines - R. G. Harper; J. A. Frick; A. P. Capparella; B. Borup; M. Nowak; D. Biesinger; C. F. Thompson (Archives of Environmental Contamination and Toxicology, 1996)

Characterization of the effects of an airborne mixture of chemicals on the respiratory tract and smoothing polynomial spline analysis of the data - Lee Ann Boylstein; Stewart J. Anderson; Randolph D. Thompson; Yves Alarie (Archives of Toxicology, 1995)

Host behaviour and its influence on foraging and acceptance by the solitary parasitoid wasp,Venturia canescens (Hym: Ichneumonidae) - J. A. Harvey; D. J. Thompson (BioControl, 1995)

Computer programs for calculation of median effective dose (LD50 or ED50) using the method of moving average interpolation - Michelle M. Schaper; Randolph D. Thompson; Carrol S. Weil (Archives of Toxicology, 1994)

Genetic interrelationships of proteolyticClostridium botulinum types A, B, and F and other members of theClostridium botulinum complex as revealed by small-subunit rRNA gene sequences - R. A. Hutson; D. E. Thompson; P. A. Lawson; R. P. Schocken-Itturino; E. C. Bttger; M. D. Collins (Antonie van Leeuwenhoek, 1994)

Spartan Pearl: A widely adapted, high yielding white skin potato cultivar - D. S. Douches; R. W. Chase; G. H. Silva; R. Hammerschmidt; N. R. Thompson; R. B. Kitchen (American Journal of Potato Research, 1992)

Michigold: A yellow-fleshed potato cultivar for fresh market - R. W. Chase; N. R. Thompson; R. B. Kitchen; G. H. Silva; R. Hammerschmidt; D. S. Douches (American Journal of Potato Research, 1992)

Biodiversity in montane Britain: habitat variation, vegetation diversity and some objectives for conservation - D. B. A. Thompson; Alan Brown (Biodiversity and Conservation, 1992)

Effect of deoxynivalenol on neurotransmitters in discrete regions of swine brain - D. B. Prelusky; J. M. Yeung; B. K. Thompson; H. L. Trenholm (Archives of Environmental Contamination and Toxicology, 1992)

Evaluation of potential interactions involving trichothecene mycotoxins using the chick embryotoxicity bioassay - B. A. Rotter; B. K. Thompson; D. B. Prelusky; H. L. Trenholm (Archives of Environmental Contamination and Toxicology, 1991)

Expression of hollow heart in segregating tetraploid potato families - S. H. Jansky; D. M. Thompson (American Journal of Potato Research, 1990)

Host specificity and biology of the weevilNeohydronomus affinis [Coleoptera: Curculionidae] a biological control agent ofPistia stratiotes - C. R. Thompson; D. H. Habeck (BioControl, 1989)

Saginaw Gold: A yellow-fleshed potato cultivar with medium-high specific gravity and excellent chip and french fry quality after storage - R. Coffin; R. Chase; N. Thompson; G. Johnston; A. McKeown; M. K. Keenan; D. Craven; R. Kitchen; J. Wilson; R. Y. Yada (American Journal of Potato Research, 1989)

Dynamics of metal accumulation in the grasshopperChorthippus brunneus in contaminated grasslands - B. A. Hunter; L. M. Hunter; M. S. Johnson; D. J. Thompson (Archives of Environmental Contamination and Toxicology, 1987)

Applications of neutron activation analysis to the study of age-related neurological diseases - W. D. Ehmann; W. R. Markesbery; E. J. Kasarskis; D. E. Vance; S. S. Khare; J. D. Hord; C. M. Thompson (Biological Trace Element Research, 1987)

Biological trace-element measurements using synchrotron radiation - Robert D. Giauque; Joseph M. Jaklevic; Albert C. Thompson (Biological Trace Element Research, 1987)

DNA restriction-fragment variation in the gene family encoding high molecular weight (HMW) glutenin subunits of wheat - N. P. Harberd; D. Bartels; R. D. Thompson (Biochemical Genetics, 1986)

Purification and properties of arylsulfatase B from high- and low-activity mouse strains - William L. Daniel; Berthie M. Ruoff; D. Bruce Thompson; Julius B. Gore (Biochemical Genetics, 1985)

Purification and properties of arylsulfatase B from high- and low-activity mouse strains - William L. Daniel; Berthie M. Ruoff; D. Bruce Thompson; Julius B. Gore (Biochemical Genetics, 1985)

The toxicity and neuropathology of 2,4,5-tribromoimidazole and its derivatives in rats - R. D. Verschoyle; A. W. Brown; Carol A. Thompson (Archives of Toxicology, 1984)

Perturbation of lipid membranes by organic pollutants - E. D. Packham; J. E. Thompson; C. I. Mayfield; W. E. Inniss; J. Kruuv (Archives of Environmental Contamination and Toxicology, 1981)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Electron microscope observations on Acholeplasma laidlawii viruses - R. G. Milne; G. W. Thompson; D. Taylor-Robinson (Archives of Virology, 1972)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

The influence of temperature on the rate of root and sprout growth of potatoes - D. R. Isleib; N. R. Thompson (American Journal of Potato Research, 1959)

Sprout inhibition of bulk stored potatoes - N. R. Thompson; D. R. Isleib (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Potato handling equipment for use in experimental work - D. R. Isleib; N. R. Thompson (American Journal of Potato Research, 1957)

s of papers presented at Annual Meeting - F. Heiligman; J. R. Wagner; WM. G. Hoyman; Jack R. Wallin; D. R. Isleib; N. R. Thompson; Robert H. Johansen; Knutson Kenneth; Carl J. Eide; F. A. Krantz; Florian Lauer; F. I. Lauer; et al. (American Journal of Potato Research, 1957)